Salidroside alleviates sepsis-associated acute lung injury through modulation of the ERK/FoxO3a signaling axis and improvement of impaired autophagic flux - Xiangli Ma; Yurong Zhang; Zhenzhen Huang; Ling Zhang; Yujie Lin; Xu Fu; Peiwu Li (Molecular Biology Reports, 2026)

Contrasting redox-related physiological responses associated with HaGATA23 and HaGATA36 during Orobanche cumana parasitism in sunflower (Helianthus annuus L.) - Yan Fu; Ting Zhou; Shuo Zhang; Shuowei Su; Lei Shen; Ying Li; Wenya Zhang; Ahsan Ayyaz; Hongju Sun; Ling Xu (Plant Science, 2026)

Seafloor troughs offshore southwestern Taiwan revealed by AUV and ROV observations - Tzu-Ting Chen; Charles K. Paull; Char-Shine Liu; Chih-Chieh Su; Ho-Han Hsu; Liang-Fu Lin; Dave W. Caress; Roberto Gwiazda; Eve Lundsten; Shao-Yung Liu; Ling-Ji Mu; Arif Mirza (Geomorphology, 2026)

Damage evolution of thermal shock in granite for enhanced geothermal systems - Liuke Huang; Guolin Rong; Xingchuan Liao; Nailing Xiu; Haifeng Fu; Dingwei Weng; Ling Yu (Geothermics, 2026)

High-yield microbial synthesis of ectoine: advances in metabolic engineering, fermentation strategies, and food application prospects - Entong Zhu; Zixuan Tao; Yuetong Fu; Yang Liu; Xin Wang; Zeyu Yan; Yang Sun; Ling Jiang (Food Research International, 2026)

Influence mechanism of tritium exposure on the growth and microcystin synthesis of Microcystis aeruginosa under rising temperature - Xue Gong; Xin-wen Zhang; Ling-shu Xu; Chuan-dong Wang; Bao Zhang; Qian Fu; Qi-lin Dai; Jin-long Lai (Environmental Pollution, 2026)

NIR-induced photothermal effects for enhanced uranium uptake and anti-biofouling by PAO-based micromotors - Xinle Zhang; Linhui Fu; Ling Chen; Kai Feng; Jian Fu; Yiqi Zhang; Jiang Gong; Yuping Zhang; Ran Niu (Chemical Engineering Journal, 2026)

Urbanization drives rapid convergence of riverine greenhouse gas levels in the urban agglomeration, North China - Ling Wen; Zhengkui Ge; Yulin Qi; Dietrich A. Volmer; Chao Ma; Chunmei Chen; Zhifeng Yan; Pingqing Fu; Si-Liang Li (Agriculture, Ecosystems & Environment, 2026)

Decadal gelatinization and phenological advancement of small jellyfish in Laizhou Bay, Bohai Sea - Ping Fu; Shan Sun; Huichao Jiang; Jianlong He; Ling Cheng; Bo Su; Hongyan Xing; Yuanqing Ma; Lijuan Liu; Yuting Zhao; Juan Zhang; Xiaowen Zhang (Marine Pollution Bulletin, 2026)

Duplication and divergence: Two new Dmrt1 gene paralogs identified in autotetraploid Carassius auratus - Qian Xiao; Qingwen Xiao; Xu Huang; Yanlin Fu; Yuhan Yang; Chongqing Wang; Xiaowei Xu; Xidan Xu; Kun Zhang; Yue Zhou; Jinhai Bai; Zhengkun Liu; et al. (Aquaculture, 2026)

U-AsymSeg: Asymmetric dual-stream RGB-Polarization network for underwater semantic segmentation - Yiming Gao; Qi Ling; Ruxin Han; Hongming Chen; Yafei Wang; Guoliang Yuan; Xianping Fu (Ocean Engineering, 2026)

Development of a frequency-domain wave load mapping methodology and its initial application to a 15 MW semi-submersible floating wind turbine - Shuijin Li; Rutian Wan; Yichao Lv; Ling Wan; Jie Fu; Ben He; Yulong Li; Torgeir Moan (Ocean Engineering, 2026)

Multi-scale evolutionary forces shape the phylogeography of an Old World disjunct plant genus Girardinia (Urticaceae) - Zhi-Peng Li; Hai-Ling Qi; Fu-lv Liu; Ying Zhao; Alexandre K. Monro; Abdullah; Xiao-Yu Song; Yue-Hua Wang; Zeng-Yuan Wu; Jie Liu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Mechanisms and kinetics of impurity removal in amorphous fused quartz: decoupling chemical stability from lattice constraints - Hao Fu; Xiaotian Chen; Xuesong Jiang; Jifei Sun; Zongrong Zhou; Ling Wang; Boyuan Ban; Jian Chen (Minerals Engineering, 2026)

Fusion of hyperspectral and multisource remote sensing data using intelligent optimized ensemble learning to estimate the SOC content of seven mangrove species in China - Jun Sun; Weiguo Jiang; Ziyan Ling; Peng Hou; Zhijie Xiao; Zhe Yang; Ze Zhang; Bolin Fu; Lu Liu; Yuyang Li; Xu He (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Metal-polyphenol network-coated probiotic microcapsules: Enhancing Limosilactobacillus fermentum storage stability and yogurt characteristics - Yi-han Cai; Fang Huang; Si-ying Yan; Xiao-jin Lin; Shu-ling Huang; Shao-fu Feng; Jie-ying Chen; Yan-yan Huang; Xin-An Zeng; Xiang-ze Jia (International Dairy Journal, 2026)

Deep placement of reduced nitrogen input strengthens soil water–nitrogen coupling and root–shoot coordination to enhance grain yield in dryland maize - Fu Liu; Jing Ling; Lan Luo; Xiaozhou Li; Yunfei Ren; Yi Zhou; Xiangyang Zhao; Xiaogang Yin; Shikun Sun; Juan Han; Youcai Xiong; Yuncheng Liao; et al. (Field Crops Research, 2026)

The potential role of groundwater microplastics on arsenic cycling in alluvial aquifers: insights from links of DOM characteristics and microbial community - Shengfeng Liu; Chengcheng Li; Jochen Bundschuh; Xubo Gao; Huihui Li; Wanpeng Shi; Siyu Li; Ling Yi; Qinglong Fu; Yanxin Wang (Environmental Pollution, 2026)

Color-tunable and multi-stimuli-responsive room temperature phosphorescence based on an efficient supramolecular approach - Huan Yao; Yu-Ling Hu; Jun-Fu Chen; Han-Yu Luo; Wen-Jie Chen; Liu-Pan Yang; Li-Li Wang (Chemical Engineering Journal, 2026)

Pyridoxine and valproic acid co-exposure induces ER-mediated calcium dysregulation and cardiac toxicity in zebrafish - Wei-Hsiang Chen; Po-Yuan Chen; Wen-Yu Chung; Tein-Yu Chiu; Wei-Ling Lin; Chen-Yu Huang; Hui-Hua Chang; Chin-Wei Huang; Bing-Hung Chen; Lin Kang; Tzu-Fun Fu (Chemico-Biological Interactions, 2026)

Visualizing glyphosate: A low-toxicity Zn2+-Based fluorescent probe for rapid detection from field to organism - Yulong Liu; Peng Jiang; Ling Gao; Yang Chen; Anchen Wang; Xianming Zhang; Zishi Wang; Ying Fu; Fei Ye (Analytica Chimica Acta, 2026)

Rhizophagus intraradices differentially promotes growth and phosphorus uptake in Camellia oleifera under low versus adequate phosphorus supply - Wan-Lin Fu; Ying-Ning Zou; Shi-Qi Pu; Fang-Ling Wang; Zhi-Yan Xiao; Jun-Yong Cheng; Mei-Hua Yang; Mashael Daghash Alqahtani; Qiang-Sheng Wu (Rhizosphere, 2026)

Zn-La staged modification of reed biochar for adsorption of tetracycline hydrochloride and mechanism study - Zhengqi Liang; Xiongyan Gao; Yushan Li; Xu Liu; Boxing An; Yingying Zuo; Ling Wang; Jiahui Fu; Meili E (Journal of Water Process Engineering, 2026)

Extrusion-induced structural reorganization of starch-ca HMB complexes for modulating starch digestibility and controlling nutrient release - Dandan Wang; Lulu Li; Yifan Fu; Ling Xin; Huili Tong; Dong Liang; Qingmin Kong; Na Zhang; Xiaofei Liu (Food Research International, 2026)

Ecological and taxonomic significance of SEM‑based micromorphology in Gentiana (Gentianaceae) on the Qinghai‑Tibet Plateau - Ling Zheng; Yaqi Han; Xinyue He; Xiaoyu Zhou; Jingle Li; Peng-Cheng Fu (Flora, 2026)

Low-dose arsenate promotes high-efficiency anammox: From granular properties to synergistic metabolism - Que Wang; Xiao-Wei Xu; Zhang-Yi Wang; Hong-Yuan Liu; Lei Wang; Hui-Ming Fu; Ya-Min Liu; Peng Yan; Ling-Ling Wang; You-Peng Chen (Chemical Engineering Journal, 2026)

Synergistic engineering of oxygen vacancies and AuCu interface on ZnO for enhanced photocatalytic biomass valorization - Hao-Yu Chen; Wu-Dan Yang; Jie-Yang Dong; Ling-Bao Wu; Dan-Dan She; Ze-Kuan Zhang; Tian-Jun Gong; Qi Zhang; Yao Fu (Chemical Engineering Journal, 2026)

Vegetable waste into soil acts as slowly released water and fertilizer to improve current vegetable productivity with less chemical fertilization - Adnan Khan; Ling Zhao; Jing Wang; Yun-Li Xiao; Jian-Ming Li; Hua-Guo Zhu; Shi-Sheng Li; Meng-Ying Li; Habimana Evode; Chang Nan; Muhammad Ashraf; Fu-Jian Mei; et al. (Bioresource Technology, 2026)

Clay mineral-facilitated azo dye biodecolorization: Mineral-specific electron transfer pathway and microbial community response - Ying Zhang; Wei Yin; Tian-Lei Zhao; Yi-Ming Ding; Ling-Xiong Yuan; Qi-Zhi Yao; Sheng-Quan Fu; Gen-Tao Zhou (Applied Clay Science, 2026)

Exploring the therapeutic mechanism of kaempferol in acute lung injury: Network pharmacology and experimental validation - Zhu-ying Zhou; Chen-xi Zhang; Xiu-ling Wei; Chuan-fu Wu; Da-gui Chen; Fu-sheng Shang; Chun-ming Jiang (Tissue and Cell, 2026)

Biocontrol mechanism of Streptomyces sp. MEPF0303 against Sclerotium delphinii causing Dendrobium officinale southern blight revealed by multi-omics analysis - Qiao Liu; Yu-Jie Chen; Jing Shi; Yong-Jing Zhang; Hai-Lan Fu; Zi-Ling Tao; Tao Zhou; Zhi-wu Tan; Ji-Luan Zhang; Ji-Hong Jiang; Lu-Dan Li (Pesticide Biochemistry and Physiology, 2026)

Time-dependent citrate-mediated precipitation inhibition in uranium column leaching: Mechanistic insights into pore evolution and uranium migration - Xiaowei Zhou; Jing Sun; Qian Li; Guangyue Li; Shangze Li; Ling Xiao; Hong Shu; Haiying Fu; Ting Li; Yongdong Wang; Zhao Cui; Guosen Xie (Journal of Hazardous Materials, 2026)

Corrigendum to “Seafloor troughs offshore southwestern Taiwan revealed by AUV and ROV observations” [Geomorphology 512 (2026) 110490] - Tzu-Ting Chen; Charles K. Paull; Char-Shine Liu; Chih-Chieh Su; Ho-Han Hsu; Liang-Fu Lin; David W. Caress; Roberto Gwiazda; Eve Lundsten; Shao-Yung Liu; Ling-Ji Mu; Arif Mirza (Geomorphology, 2026)

Artificial intelligence-based modeling and quality evaluation of turmeric under full-spectrum artificial sunlight drying - Pratik Nayi; Seyed-Hassan Miraei Ashtiani; Fu-Yuan Ma; Navneet Kumar; Fung Ling Ng; Ho-Hsien Chen (Food Chemistry, 2026)

Experimental and numerical investigation on the shear mechanical behaviors and failure mechanisms of silty mudstone under seepage-stress coupling - Xiaowei Yu; Jiade Zhang; Hongyuan Fu; Ling Zeng; Hongri Zhang; Jingcheng Chen; Jie Liu (Bulletin of Engineering Geology and the Environment, 2026)

A regional hydrodynamic coefficient reconstruction workflow for internal-load recovery of a 15 MW semi-submersible floating wind turbine - Shuijin Li; Shuaibing Zhang; Ling Wan; Jie Fu; Ben He; Yibo Wang (Ocean Engineering, 2026)

Serum exosomes protect heat-stressed mouse 2-cell embryos: Enhanced antioxidant defense and base excision repair of oxidative DNA damage - Hong-Chuan Zhang; Si-Jing Qu; Xin-Lei Yan; Rui-Cong Wang; Shi-Yong Zhu; Rong-Feng Cao; Kai-Qiang Fu; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2026)

Molecular mechanisms underlying the maintenance of protein homeostasis in pearl gentian grouper under acute high-temperature stress - Qiu-Ting Yang; Ren-Xie Wu; Yan-Shan Liang; Ben-Ben Miao; Su-Fang Niu; Feng-Ling Lei; Fan-Li Long; Zhen-Bang Liang; Yu-Xin Shen; Yu Fu (Journal of Thermal Biology, 2026)

Symbiotic chlorine-resistant bacteria and fungi in urban building drinking water plumbing pipe biofilms - Zhen-Ning Luo; Tian-Yang Zhang; Huan He; Ren-Jie Pan; Yun-Qiao Zeng; Zhu Peng; Jun Shi; Qi Fu; Minyuan Pan; Chao Zeng; Qian Xiao; Ling Hu; et al. (Journal of Hazardous Materials, 2026)

Grazing season overrides intensity in driving plant subordinate species-mediated community dynamics across contrasting elevations of typical steppe - Yu-Wen Zhang; Lan Li; Zhao-Xia Guo; Zhao-Ling Da; Wen-Jun Wang; Xing-Qi Wang; Fu-Jiang Hou; Ji-Zhou Ren (Global and Planetary Change, 2026)

Autophagy attenuates the secondary senescence of endometrial stromal cells induced by Bisphenol S - Xuguang Mi; Jianhua Fu; Lei Liu; Lingshan Wang; Shiling Chen; Mengxue Wu; Chunxue Niu; Yan Wang; Lixin Cao; Lin Wang; Ling Deng; Xiaodan Lu; et al. (Chemico-Biological Interactions, 2026)

Evaluation and comparison of TCR repertoire differences between patients with cervical cancer and healthy individuals - Wenwen Gao; Cong Wang; Jiawen Jia; Yiqian Li; Ting Li; Ling Liu; Yi Zhang; Haibin Yu; Cuiping Yang; Xiaoli Fu; Yongbin Chen; Yan Cheng (Science China Life Sciences, 2026)

Effects of personality and body weight on foraging behavior and vigilance: a case study in a small rodent - Yu-Chuang Hui; Shu-Jing Gao; Xuan-Wen Li; Wei-Qi Chen; Yue-Yue Yang; Xue-Dong Bai; Qin Su; Fu-Shun Zhang; Li-Qing Wang; Ling-Ying Shuai (Behavioral Ecology and Sociobiology, 2026)

The Therapeutic Potential of Fractional CO2 Laser for Hyperpigmentation: Evidence From Network Meta-analysis, Clinical and Animal Studies - Haoran Guo; Hui Li; Ling Jiang; Chuhan Fu; Jianyun Lu; Zhen Tang; Jing Chen; Qinghai Zeng (Phenomics, 2026)

Monoterpenoids from the roots of Paeonia lactiflora Pall. and their neuroprotective activity - Bo Fu; Yi-Qiang Zhang; Jin-Ling Zhang; Si-Yi Wang; Jia-Tong Wu; Juan Pan; Wei Guan; Zhi-Chao Hao; Qing-Shan Chen; Li-Li Zhang; Hai-Xue Kuang; Yan Liu (Natural Product Research, 2026)

Shear Progressive Failure Mechanisms of Shale with Non-persistent Joints - Yuhao Xia; Lu Chen; Ling Zeng; Hongyuan Fu; Qiuhong Wu; Jintao Luo (Rock Mechanics and Rock Engineering, 2026)

Biofilm-based immobilized fermentation of Bacillus subtilis coupled with Ni2+-NTA in situ adsorption for efficient hydrolysis of silkworm pupa protein - Xin-Chen Li; Zhi-Ang Zhang; Yi-Nan Cao; Chao Deng; Fu-Ling Wang; Hai-Fei Zhang; Richard Ansah Herman; Le-Yun Yang; Jun Wang (Sustainable Chemistry and Pharmacy, 2026)

Natural water constituents boost pollutant removal in the O3/PAA system via Cu-doped LaFeO3 perovskite and in-situ formed metal complexes - Zhenyang Xu; Shuhan Fu; Zijing Ling; Shouling Li; Fengling Pan; Ning Xiao; Shuguang Wang; Tingting Zhang (Journal of Environmental Chemical Engineering, 2026)

Fly ash/natural clay composite monoliths for promising solar interfacial evaporation - Dahao Liu; Ke Zhang; Jie Wang; Yixuan Fu; Zhenxu Li; Lanlan Jiang; Lunxiang Zhang; Yongchen Song; Zheng Ling (Journal of Environmental Chemical Engineering, 2026)

Non-uniform gradient depressurization strategy for balancing heat transfer and gas production in Dual-Gas Co-Production systems - Xian Sun; Hang Zheng; Hui Yang; Fu-Jun Cheng; Zhen Pan; Wen-Chen Han; Hao-Xiang Sun; Yang Yu; Ling-Ban Wang; Chang-Yu Sun (Fuel, 2026)

On-demand amorphous calcium phosphate-mediated regeneration of dentin and enamel using ion-regulated hydroxypropyl methylcellulose and carboxymethyl chitosan hydrogels - Zihan Cui; Zhiwen Liu; Zhixin Zhang; Danni Wang; Taoyu Chen; Baiping Fu; Ling Zhu; Long Zhao; Zhe Wang (Carbohydrate Polymers, 2026)

Sevoflurane activates ATF4/NSUN7/PRKCD axis to induce neurotoxicity and cognitive impairment by promoting neuron mitochondrial fission - Qiang Fu; Ling Chen; Xiong Zeng; Cuilin Lan; Guanhua Wang; Shujia Li; Tingmin Lv; Hanwen Chen (Chemico-Biological Interactions, 2026)

Data driven analysis on changing patterns of reactive nitrogen deposition in East and Southeast Asia - Jiani Tan; Yan Zhang; Xuejun Liu; Yun Fat LAM; Mohd Talib Latif; Kasemsan Manomaiphiboon; Joshua S. Fu; Maggie Chel Gee Ooi; Ling Huang; Yangjun Wang; Hui Chen; Kun Zhang; et al. (Atmospheric Environment, 2026)

Genome-wide analysis of sunflower (Helianthus annuus) and Orobanche cumana reveals HaEXLA2 and HaEXLB2 as negative regulators of lignin-based resistance - Lei Shen; Yi Duan; Ying Li; Wenya Zhang; Yan Fu; Ting Zhou; Hongju Sun; Ahsan Ayyaz; Ling Xu (Plant Cell Reports, 2026)

Operational monitoring windows from cumulative rainfall to chlorophyll-a in subtropical reservoirs - Jingxin Wei; Peiliang Chen; Xingcheng Fu; Jie Ling; Bingqing Xiao; Xuedong Xie; Bozhu Huang; Jingyi Cen; Songhui Lu (Environmental Monitoring and Assessment, 2026)

Two new compounds from the roots of Paeonia lactiflora Pall. and their anti-inflammatory effects - Bo Fu; Jin-Ling Zhang; Jia-Tong Wu; Si-Yi Wang; Yi-Qiang Zhang; Juan Pan; Wei Guan; Zhi-Chao Hao; Hai-Xue Kuang; Qing-shan Chen; Li-Li Zhang; Bing-You Yang; et al. (Natural Product Research, 2026)

Species-specific accumulation and biomagnification of PFASs in aquatic and terrestrial organisms from the Xisha Islands - Yu-Quan Zhang; Jun Xiang; Jiao-feng Gu; Peng Zeng; Qi-Fei Peng; Yong-Fu Chen; Yu-Feng Hu; Li-cheng Wang; Hang Zhou; Ling Mo (Marine Pollution Bulletin, 2026)

Analysis of the morphological structure and metabolic characteristics of Moniezia in sheep - Qian Mu; Wan-Ling Yao; Bao-Shan Wang; Wen-Zhu Chai; Fu-Hua Liu; Zhen Huang; Yong-Cheng Meng; Jing Pan; Xi-Ping Fan; Wan-Hong He; Wang-Dong Zhang (Veterinary Parasitology, 2026)

Bioactive edestin peptides from hemp (Cannabis sativa L.) seeds improve exercise performance under hypobaric hypoxia - Rui Zhang; Jie Liu; Liang-Liang Chen; Jia-Qi Liu; Xiao-Qian Jin; Zi-Xian Fu; Jun-Bin Xiong; Bin Jia; Jun-Ling Shi; Da-Chuan Yin (Food Research International, 2026)

Preparation of cancer cell membrane-coated Gambogic acid-loaded pH-sensitive liposomes to enhance targeted anti-hepatocellular carcinoma effect - Yi-Feng Zhang; Kun Chen; Yu-Qing Zhu; Lin Liu; Xiang-Tao Kong; Yan Dai; Xiu-Juan Fu; Ya-Ling Li; Ming-Hua Liu; Dan Zhang (Drug Delivery and Translational Research, 2026)

Effect of experimental parameters on saturated permeability and soil-water characteristic curves of modified carbonaceous mudstone - Caiying Chen; Ling Zeng; Hongyuan Fu; Jue Li (Bulletin of Engineering Geology and the Environment, 2026)

Habitat complexity and spatial navigation: linking habitat to cognitive strategy in cyprinid fishes - Wu-Xin Li; Qing-Yin Wei; Ling-Qing Zeng; Shi-Jian Fu (Behavioral Ecology and Sociobiology, 2026)

A spectral multiaxial fatigue reliability approach for riser girth welds based on the master S-N curve - Long Zhang; Tianfeng Zhao; Yuxiang Yang; Chao Fu; Jiatong Ling; Depeng Liu (Ocean Engineering, 2026)

Geochemistry of tourmaline in granitic rocks from the Zharigana and Caolong areas, Northern Tibet: Implications for the identification of lithium-mineralizing plutons - Ling Ma; Jin-Sheng Zhou; Qiang Wang; Lin Ma; Jin-Heng Liu; Wu-Fu Li; Bing-Zhang Wang; Chun-Tao Wang; Jian-Dong Liu; Xin-Yuan Zhang; Mao-Rui Liu; Zhi-Wei Yu; et al. (Lithos, 2026)

Mechanistic insights into the enhanced degradation of hydroxychloroquine by singlet oxygen in PMS and PMS/Cl2 systems: A comparative study - Zi-Han Feng; Zhen-Zhen Li; Dong-Su Bi; Fu-Xiang Tian; Ling-Yao Meng; Yan-Ting Jia; Yu-Qiong Gao; Xiao-Jun Hu (Journal of Environmental Management, 2026)

Enhancing water quality and ecological sustainability through intelligent sustainable landscape fountains - Yuan-Hsiou Chang; Hsiao-ling Lu; Tsai-Fu Chuang; Chien-Hsun Chang; Chieh-Hsi Chen; Chien-Che Huang (Ecohydrology & Hydrobiology, 2026)

Plant-Based Protein Fermentation Medium Optimization for Antimicrobial Cell-Free Supernatant Production by Lactiplantibacillus plantarum K014 Against Cutibacterium acnes - Yee Ling Kong; Joo Shun Tan; Choon Fu Goh (Probiotics and Antimicrobial Proteins, 2026)

Population pharmacokinetic modeling and Monte Carlo simulation–based dosing optimization of trimethoprim–sulfamethoxazole in critically ill patients - Min Wang; Chen Li; Xiangxiang Fu; Fangling Wang; Xiaojun Zhou; Bingli Zhang; Wenya Xu; Liqiu Liang; Zhenlin Lei; Hengxing Qu; Ling Xie; Lili Zhong; et al. (European Journal of Clinical Pharmacology, 2026)

Study on uniaxial compression characteristics and constitutive model of carbonaceous mudstone soil-rock mixture with rock block proportion and dry-wet cycle - Hong-yuan Fu; Hai-tao Yang; Ling Zeng; Jing-cheng Chen; Yan Wang; Hong-ri Zhang (Bulletin of Engineering Geology and the Environment, 2026)

Proteome-wide mapping of cysteine persulfidation in deep-sea hyperthermophilic archaea - Ling Fu; Xuegong Li; Shaowei Liu; Yunhan Zhang; Jing Yang (Extremophiles, 2026)

Metabolic Engineering of Selenocysteine Biosynthesis and Insertion Pathway in Lactococcus Lactis - Jing-Jing Peng; Yao Qin; Shi-Yang Yue; Ping Shi; Ling-Yu Wang; Chen-Xing Liu; Yu-Hui Fang; Xiao-Dong Pei; Fu-Tian Yu; Xin-Bi Huang; Xiao-Ling Liu; Cheng-Hua Wang (Biological Trace Element Research, 2026)

QSAR-enhanced machine learning for mechanistic insights and real-time prediction of DBPs in drinking water distribution systems - Dai-Xu Zhang; Tian-Yang Zhang; Zhen-Ning Luo; Zhu Peng; Zheng-Xiong Zheng; Yun-Qiao Zeng; Qi Fu; Ling Hu; Bing Geng; Chao-Yi Tong; Yu-Lin Tang; Bin Xu (Water Research, 2026)

Comprehensive XRD study of enhancing Al removal rate by microstructure refinement and phase transformation in quartz powder purification process - Hao Fu; Xuesong Jiang; Xiaotian Chen; Zhenyi Hu; Jifei Sun; Zongrong Zhou; Ling Wang; Boyuan Ban; Jian Chen (Minerals Engineering, 2026)

Dynamic remodeling of intramuscular structural proteins and its impact on abalone muscle quality during post-mortem cold storage - Hua Liu; Tian-Bo Zhang; Fu-Hao Zhang; Le-Chang Sun; Duanquan Lin; Tengchuan Jin; Ling-Jing Zhang; Jia-Yin Huang; Min-Jie Cao; Yu-Lei Chen (Food Chemistry, 2026)

Prolonged low pH reprograms carbon and nitrogen metabolism and micronutrient use in Symbiodinium kawagutii and reveals indicators for reef water quality management - Fu-Fang Wen; Qing-Ling Ma; Hao-Ran Guo; Yan Huang; Da-Wei Li; Wei-Dong Yang; Hong-Ye Li; Li-Gong Zou (Environmental Research, 2026)

Solar-driven one-pot synthesis of freezing-tolerant and self-healing nanocellulose eutectogels for sustainable flexible electronics - Chaoqiang Fu; Sanwei Hao; Jun Yang; Jifei Zhang; Jialong Wen; Wenfeng Ren; Bing Wang; Ling-Ping Xiao; Changyou Shao; Runcang Sun (Chemical Engineering Journal, 2026)

Cation off-size engineering for high-performance oxygen vacancy-rich air electrode - Senran Hao; Ling Fu; Hailong Liao; Haojie Zhu; Zhipeng Liu; Jie Xiao; Yuan Zhang; Bin Chen; Heping Xie (Chemical Engineering Journal, 2026)

Multimodal MRI reveals hypothalamic structural-functional alterations associated with bone mineral density loss in postmenopausal women - Xiyong Dai; Zhijie Gao; Lei Gao; Chengwei Fu; Shanshan Wu; Zhaoxian Yan; Ling-Feng Zeng; Yue Zhang; Bo Liu (Brain Imaging and Behavior, 2026)

Proanthocyanidin B2 regulates epidermal growth factor receptor (EGFR) and activates the PI3K/AKT pathway to promote the in vitro maturation of sheep oocytes - Yucheng Liu; Jingjing Wang; Zhenliang Zhang; Jiachen Bai; Houru Li; Zhanmin Lv; Lei Gao; Jianhong Ni; Shouliang Lu; Changbin Liu; Guiping Hai; Weijun Liu; et al. (Theriogenology, 2026)

MsTIFY10a gene from alfalfa negatively regulates drought and salt tolerance in transgenic tobacco - Qi Chen; Yan Zhang; Ying Tian; Jing Xu; Qing-Wen Fu; Zhen-Yi Li; Feng-Ling Shi; Cui-Ping Gao; Zhi-Qiang Zhang (Journal of Plant Physiology, 2026)

Insight into the antioxidant mechanism of astaxanthin geometric isomers by quantum chemical calculations and molecular simulations - Yanbo Chen; Ling Liu; Xiaohan Fu; Tianyue Zhou; Shuge Tang (Food Chemistry, 2026)

Study on the thermal insulation efficiency and ecological conservation effects of intelligent sustainable green walls - Hsiao-ling Lu; Yuan-Hsiou Chang; Tsai-Fu Chuang; You-En Zhong; Zhi-Jia Feng (Energy and Buildings, 2026)

Fixation of atmospheric nitrogen on present-day Mars during dust events - Wenshuo Mao; Xiaohui Fu; Zhongchen Wu; Jiang Zhang; Zongcheng Ling; Yang Liu; Yu-Yan Sara Zhao; Jiacheng Liu; He Cui; Hitesh G. Changela; Yuheng Ni; Lifang Li; et al. (Earth and Planetary Science Letters, 2026)

Evolution of tactoid structures and pore water distribution during wetting in saturated clay aggregates driven by montmorillonite-water interaction - Kai-wen Tong; Chang-fu Wei; Yong-gui Chen; Zi-yu Ding; Hao Wang; Ya-kun Tian; Rong Gui; Ling-ling Wu; Zhi-jun Zhang; Lin Hu (Computers and Geotechnics, 2026)

Multiscale modeling and swelling behaviors of Wyoming sodium montmorillonite systems - Zhi-jun Zhang; Jin-xiang Deng; Chang-fu Wei; Ya-kun Tian; Lin Hu; Min Wang; Ling-ling Wu; Kai-wen Tong (Computers and Geotechnics, 2026)

Geochemical signatures of mud and core gases from the Milun Fault Scientific Drilling (MiDAS), Taiwan: Implications for fluid pathways and crustal degassing - Ching-Chou Fu; Kuo-Hang Chen; Kuo-Wei Wu; Pei-Ling Wang; Ai-Ti Chen; Vivek Walia; Kuo-Fong Ma (Chemical Geology, 2026)

Optimizing the WAAS-Kriging method for estimating grid ionospheric delay error and accuracy over low-latitude regions - Yunri Fu; Ling Yang; Shaojun Feng; Yunzhong Shen; Nan Zhi; Liping Fu (GPS Solutions, 2026)

Genetic origins and climate‐induced erosion in economically important Asian walnuts - Peng‐Zhen Fan; Guang‐Fu Zhu; Moses C. Wambulwa; Richard I. Milne; Zeng‐Yuan Wu; Ya‐Huang Luo; Robabeh Shahi Shavvon; Alistair S. Jump; Debabrata Maity; Lian‐Ming Gao; Hai‐Ling Qi; Hong‐Yu Wu; et al. (Conservation Biology, 2026)
The global climate is undergoing unprecedented changes, posing significant threats to species persistence. However, the spatiotemporal impacts on genetic diversity remain poorly understood, hindering species conservation and management. Walnuts, generally referred to as Juglans regia and J. sigillata , are economically vital in Asia, but little is known about their genetic origins and how the species will be affected by future climate change. Using 31 microsatellites, we genotyped 5282 individuals from 233 populations of walnuts in Asia. We assessed genetic diversity patterns and demographic history and investigated potential future genetic erosion risks. Genetic diversity of walnuts was high in the Himalaya and Hengduan Mountains. The 2 species diverged during the Pleistocene (around 1.41 Ma BP), and J. regia contained 2 genetic groups (JR1 and JR2). The JR2 group had the lowest diversity and likely arrived in northern China around 9.77 ka BP, perhaps via human transport. The Western Himalaya likely served both as a glacial refugium and the center of origin for J. regia , and the Eastern Himalaya appears to have been the refugium for J. sigillata . The 2 species appear to have hybridized in the Central Himalaya and the Sichuan basin and surroundings, forming two distinct hybrid zones. Our results indicate that genetic diversity will be reduced by up to 9.03% due to range loss under future climate change and dramatic genetic structure turnover in the Himalaya and Hengduan Mountains. In situ conservation in the Himalaya is essential for safeguarding genetic diversity and adaptive potential in Asian walnuts, while ex situ preservation of genetically unique wild germplasm, coupled with its integration into breeding programs, will enhance climate resilience. The findings advance our understanding of the origin of Asian walnuts and how future climatic change may affect their genetic diversity, offering a model for conservation and breeding strategies in other tree species facing similar threats.

Crisis resolution pathways enhancement for building carbon emission based on dynamic QCA: Evidence from China - Jinmei Wang; Qing Yang; Ling He; Xingxing Liu; Lingmei Fu; Yandi Zheng (Sustainable Cities and Society, 2026)

Nor-halimane and spiro-labdane diterpenoids with anti-inflammatory activity from Leucas ciliata Benth - Jia-Cai Kuang; Fu-Ling Cen; Xuan Zhang; Xu-Hua Nong; Xue-Ming Zhou; Xiao-Bao Li; Zhang-Xin Yu; Guang-Ying Chen (Phytochemistry, 2026)

UVB enhances SLC6A15-mediated phenylalanine transport to promote melanogenesis - Shu Zhou; Yujie Ouyang; Yibo Hu; Xixia Dai; Ling Jiang; Chuhan Fu; Yaqing Wen; Jiangfeng Huang; Keyi Zhang; Jing Chen; Qinghai Zeng (Journal of Photochemistry and Photobiology B: Biology, 2026)

From passive prevention to proactive intervention: An AI-assisted integrated governance system for algal bloom monitoring and control - Minjuan Lin; Yihao Xu; Jia Peng; Yaoyang Chen; Yulong Zhu; Xuanye Fu; Yi Zhu; Ling Lin (Environmental Research, 2026)

Metal coordination-hydrogen bonding synergistic cross-linked MXene for 3D-printed micro-supercapacitors in self-powered sensing systems - Haiyang Fu; Na Li; Yi Yuan; Zhaoyu Wang; Ling Wang; Simin Chai; Tengfei Duan; Jianxiong Xu (Chemical Engineering Journal, 2026)

Terrestrial in situ cosmogenic nuclide production rate scaling models: Theory, progress, and prospects - Jie Zhou; Weijian Zhou; Yunchong Fu; Feng Xian; Du Wang; Xianlin Yang; Guocheng Dong; Li Zhang; Ling Tang; Guoqing Zhao; Mengyu Zang (Science China Earth Sciences, 2026)

The persistent threat of Niphades castanea to China’s chestnut across three major river basins - Bin Mao; Yue Fu; Ya-Bo Liu; Hui-Ling Yang; Yun-Li Xiao (New Forests, 2026)

Ion exchange-based magnetic micro-cleaners harness multiple effects to enhance antibiotics removal - Ling Chen; Linhui Fu; Xinle Zhang; Jiang Gong; Jinping Qu; Ran Niu (Water Research, 2025)

Enhancing water quality and sustainable resource utilization through an AIoT-enabled intelligent circular agriculture system - Hsiao-ling Lu; Yuan-Hsiou Chang; Tsai-Fu Chuang; Syuan-Ru Chen; Zhe-Dian Wu (Journal of Environmental Chemical Engineering, 2025)

Coconut-shell biochar fixed-bed for groundwater remediation: Co-removal of microplastics and perfluorooctanoic acid - Xinle Han; Jing Xu; Yanfeng Shi; Lixingzi Wu; Ling Fu; Weina Xue; Yanhao Zhang; Xu Zhang; Xuli Jing; Zhibin Zhang (Journal of Environmental Chemical Engineering, 2025)

Presence of a queen (Apis mellifera) reduces the sensitivity of worker bees to environmental risks - De Fang Niu; Qiu Lan Zheng; Bin Yuan; Xiao Ling Su; Cui Ping Zhang; Yuan Yuan Lu; Ping Liu; Fu Liang Hu; Huo Qing Zheng (Journal of Asia-Pacific Entomology, 2025)

Synergistic construction of an annual 2 m mangrove species dataset from 2016 to 2023 using structural features and hybrid stacked deep learning models—Beibu Gulf, Guangxi, China - Jun Sun; Weiguo Jiang; Ziyan Ling; Bolin Fu; Ze Zhang; Zhijie Xiao; Xingling Mu (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Postbiotics alleviate cognitive impairment and neuroinflammation via gut-brain axis and TLR4/MyD88/NLRP3 pathway - Longgang Jia; Ling Xiao; Xiaoyan Song; Xiaoxiao Zhang; Xuemei Han; Wu Liang; Tianmin Fu; Yufeng Xie; Yanping Wang; Weitao Geng (Food Research International, 2025)

Analysis of the AP2/ERF transcription factor family in Eriobotrya japonica and its role in exogenous melatonin-mediated regulation of salt stress - Ling Zhu; Fuhua Liu; Xin Lin; Tianyu Fu; Lin Zou; Yuanhai Pan; Rong Zou; Yang Zhao; Hanyao Zhang (Functional & Integrative Genomics, 2025)

Network pharmacology, molecular docking and experimental validation to elucidate the anti-ulcerative colitis mechanism of Rosa roxburghii Tratt. leaves - Ming-Liang Luo; Shuang Zhang; Qing-Yong Wang; Ling-Wei Fu; Li-Juan Xiang; Chang Lin; Xin Yin (Natural Product Research, 2025)

Per- and polyfluoroalkyl substances in tissues of intermediate egrets (Ardea intermedia) from the South China Sea - Ling Mo; Jun Xiang; Ming-Yang Wang; Yu-Quan Zhang; Qin-Wei Hao; Qi-Fei Peng; Yong-Fu Chen; Yu-Feng Hu; Jing Zheng; Qiao Xing; Bin Tang; Li-Cheng Wang (Marine Pollution Bulletin, 2025)

How to improve the environmental friendliness of the thermal power industry: A perspective on constructing cross-regional collaborative emission reduction mechanisms tailored to local conditions - Yuting Fu; Changhui Yang; Jennifer Shang; G.G. Hegde; Ling Wang (Sustainable Cities and Society, 2025)

A beneficial exploration and recommendations for the use of hydrophobic materials in ecological protection of strongly weathered carbonaceous mudstone slopes - Huanyi Zha; Ling Zeng; Hongyuan Fu; Xiang Qiu; Peng Zhuo (Journal of Cleaner Production, 2025)

Pretrain-finetune neural operator for multi-fidelity surrogate modeling of structural dynamic systems - Pei-Lin Li; Shi-Fu Liu; Yi-Qing Ni; Jian-Ming Ling; You-Wu Wang (Engineering Structures, 2025)

Electrochemical exfoliation of poly(triazine imide)-coated graphene oxide for the in-situ synthesis of composite proton exchange membranes with enriched phosphoric acid channels - Qingting Liu; Ying Zhou; Bei Wang; Zhiwei Ling; Xudong Fu; Rong Zhang; Shengfei Hu; Gang Xiao; Xiao Li; Feng Zhao; Jun Yang (Chemical Engineering Journal, 2025)

Efficient tanshinone metabolic engineering in Salvia miltiorrhiza through modified multiplex CRISPR/Cas9 system - Han Zheng; Qi Yao; Qi Liu; Badalahu Tai; Yi Ye; Ling Li; Yaojie Zhang; Yuyang Zhao; Xiaokai Gao; Shuai Liu; Xueqing Fu; Muyao Yu; et al. (Chemical Engineering Journal, 2025)

Characterization of Global and Local Strains with Unsaturated Claystone in Triaxial Compression Using X-Ray Micro-tomography and Digital Volume Correlation - Hai-Ling Shi; Thomas Rougelot; Jian-Fu Shao; Minh-Ngoc Vu; Jean Talandier (Rock Mechanics and Rock Engineering, 2025)

Salinity gradients induced multistability shifts of microbial communities in coastal tidal flats of Jiangsu Province - Jiating Fan; Linqiong Wang; Pengxiao Fu; Hong Ling; Zhe Zhao (Marine Biology, 2025)

Crushing characteristics and energy dissipation modeling of Single-Particle-Size carbonaceous mudstone as roadbed fill - Yan Wang; Hong-yuan Fu; Jian-Ping Song; Ling Zeng; Tao Li; Jian-Ping Xiong; Hong-Ri Zhang; Wen-Guang Wang; You-Jun Li; Jing-Cheng Chen (Bulletin of Engineering Geology and the Environment, 2025)

Plastic film mulching ensures maize climate resilience: A perspective of temperature suitability and optimal sowing period window - Jing Wang; Ling Zhao; Bao-Zhong Wang; Fei Mo; Ning Wang; Shu-Tong Liu; Yuan Song; Ai-Tian Ren; Fu-Jian Mei; Yang Wang; Qi Lu; You-Cai Xiong (Soil and Tillage Research, 2025)

Inorganic acid and ammonia emission factors in semiconductor processes - Fu-Yun Chen; Ming-Peng Yeh; Sher Ling Lee; Tony Chen; Tzu-Sou Chuang; Hui-Hsin Tseng; Kuo-Lun Tung (Science of The Total Environment, 2025)

The mechanisms of MTOCs maturation in human and mouse oocytes - Hao Gu; Ling Wu; Mingru Yin; Xingzhu Du; Jing Fu; Fangzhou Xu; Zhiqi Ye; Xuelin Zhang; Huixia Jing; Yuxi Luo; Wenzhi Li; Xiaoxi Sun; et al. (Science Bulletin, 2025)

New natural products from Rhododendron ciliicalyx subsp. Lyi - Chun-Lin Guo; Si-Xuan Liu; Lu Zhang; Ling Li; Yong-Fu Lu; Si-Yang Dai; Chang Li; Yue-Hu Pei (Phytochemistry Letters, 2025)

Algal-bacterial symbiosis strengthens the treatment of high-salinity phenolic wastewater and its molecular mechanism - Xiao-Xiao Dou; Bin-Di Mao; Ang Li; Jun-Jie Gu; Xiao-Ling Zhang; Chun-Wan Fu; Xin-Jie Zhang; Bang-Jie Lan; Jia-Wei Xu; Bin-Xin Zhang; Hong-Jie Zheng; Feng Gao (Journal of Hazardous Materials, 2025)

Macrophage and keratinocyte cell assays suggest that the supercritical CO2 extract of black soybean possesses anti-inflammatory and skin barrier-protective effects - Ying Wu; Jia-Ying Wu; Jing-Xuan Bai; Xiao-Qi Wang; Amy Sze-Man Li; Xiao-Yun Fan; Rui-Xuan Han; Li Wang; Xiaobing Dou; Xiu-Qiong Fu; Zhi-Ling Yu (Food Research International, 2025)

Establishment of a gill-derived cell line in Sebastes schlegelii with practicability in studies of bacterial pathogen-host interaction - Xin Zhang; Yan Ling Sun; Qiang Fu; Chao Li; Hui Jun Huo (Fish & Shellfish Immunology, 2025)

Biohybrid microneedle delivering engineered probiotics for synergistic tumor gas/photothermal-immunotherapy - Wenxin Fu; Junhong Ling; A.M. Omer; Xiao-kun Ouyang; Lin Mei; Nan Wang (Chemical Engineering Journal, 2025)

Harnessing built-in electric fields for enhanced electron transfer in biosensor for precise digital health assessment - Tian-Run Lv; Yaqiong Yang; Jia-Chen Zhang; Ling Qi; Ming-Jie Yin; Yong Li; Ken Tye Yong; Quan-Fu An (Chemical Engineering Journal, 2025)

Photothermal-driven micromotor for enhanced lithium extraction from salt-lake brines - Shihao Ding; Wenqian Xing; Ling Chen; Linhui Fu; Xinle Zhang; Zhen Luo; Qianqian Li; Mengting Qin; Jiang Gong; Jinping Qu; Ran Niu (Chemical Engineering Journal, 2025)

Sources and potential health indicators in urban aerosols revealed by gas chromatography-mass spectrometry combined with nitrogen chemiluminescence detector: evidence from a megacity (Tianjin) of China - Jingying Ma; Yulin Qi; Yufu Han; Jinfeng Ge; Ling Wen; Xiaoli Fu; Wei Hu; Zongbo Shi; Dietrich A. Volmer; Pingqing Fu (Atmospheric Environment, 2025)

Effects of physicochemical factors on transport and retention of polystyrene microplastics (PS-MPs) in homogeneous and heterogeneous saturated porous media - Lixingzi Wu; Yanfeng Shi; Ling Fu; Xinle Han; Yanhao Zhang; Xu Zhang; Weina Xue; Xuli Jing; Jing Xu; Zhibin Zhang (Environmental Geochemistry and Health, 2025)

Conditional Generative Adversarial Networks Enhance Atmospheric Thermodynamic Profile Retrieval from Ground-Based Microwave Radiometer Measurements - Disong Fu; Xia Li; Jingmiao Zhu; Dazhi Yang; Ruiting Liu; Hongrong Shi; Guangyu Gao; Xinlei Han; Xiang’ao Xia; Yunjie Xia; Maoling Ayitikan; Kai Cheng; et al. (Journal of Meteorological Research, 2025)

Correction to: Links between personality, metabolic rates, brain size, and spatial learning ability of goldfish (Carassius auratus) under two conditions of spatial learning - Wu-Xin Li; Shi-Jian Fu; Ling-Qing Zeng (Behavioral Ecology and Sociobiology, 2025)

Evaluating the ecological and agricultural benefits of intelligent sustainable green energy floating gardens: impacts on microorganisms and vegetable growth - Yuan-Hsiou Chang; Hsiao-ling Lu; Tsai-Fu Chuang; Hong-Bin Lai; Yi-Zhen Yu (Environmental Science and Pollution Research, 2025)

AhR-mediated histone lactylation drives cellular senescence during benzo[a]pyrene-evoked chronic obstructive pulmonary disease - Li-Hong Chen; Jun-Ping Wei; Meng-Die Li; Xiu Lu; Yi-Cheng Ma; Yu Wang; Ling Zheng; Jun Fei; Wei Cao; De-Xiang Xu; Jin Yang; Hui Zhao; et al. (Journal of Hazardous Materials, 2025)

Pressure makes diamonds: Enhanced permeation resistance to petroleum hydrocarbons of a novel in-situ mixed wall material - Zhe-Yuan Jiang; Xian-Lei Fu; Yu-Ling Yang; Wei-Yi Xia; Min Wang; Heng Zhuang; Zi-Han Lu; Yan-Jun Du (Journal of Hazardous Materials, 2025)

Neurotoxicity of chronic nano-neodymium oxide exposure in zebrafish: Behavioral and molecular insights - Bao-Fu Zhang; Xing-Zhe Wu; Jin-Xia Wang; Yan-Ling Liao; Zi-Xin Cai; Yiyun Liu; De-Sheng Pei (Journal of Hazardous Materials, 2025)

Association of long-term PM2.5 and its components exposure with ovarian hyperstimulation syndrome risk in assisted reproductive technology patients - Jia-Liang He; Rui-Ling Liu; Yu-Ling Hu; Quan-Zi Yao; Zhi-Lei Xu; Li-Hong Geng; Tong Wang; Xin Luo; Ying-Ling Yao; Yong-Jia Zhang; Xue-Jiao Wang; Zhao-Hui Zhong; et al. (Environmental Pollution, 2025)

Pre-carbonization facilitates closed pore formation in asphalt-derived hard carbon for high-plateau-capacity sodium storage - Chong Xu; Dongyuan Zhang; Guang Ma; Shuang Liu; Gong Cheng; Junjie Fu; Ye Wang; Runyi Xu; Chen Ling; Sai Che; Yongpeng Cui; Yongfeng Li (Chemical Engineering Journal, 2025)

Analgesic Effects of Acupressure on Jing-jiaji Acupoints in a Rat Model of Cervical Spondylotic Radiculopathy - Shang-Hong Jiang; Song Yang; Ling Meng; Ling-Yao Xie; Jia-Ni Yang; Si-Qi Li; Ke-Ying Liao; Zhi-Fang Qiu; Yao-Yao Xiao; Man-Di Fu; Zhi-Li Liu; Xue-Yu Jiang (Molecular Neurobiology, 2025)

A nanozyme colorimetric sensor combined with cloud-based machine learning algorithm-assisted WeChat mini program for intelligent identification of Chinese green tea - Wanjun Long; Siyu Wang; Yangcheng Ling; Yuting Guan; Huiru Zhang; Hengye Chen; Wei Lan; Yuanbin She; Haiyan Fu (Food Research International, 2025)

A strain work constitutive model for structured soils - Ling Xu; Xinqi Guan; Hongjian Liao; Yingpeng Fu (Computers and Geotechnics, 2025)

Role of macrophage ATP metabolism disorder in SiO2‑induced pulmonary fibrosis: a review - Hui-jie Hu; Yuan-yuan Fu; Shu-ling Du; Yu-han Zhang; Zhao-qiang Zhang; Gui-zhi Han (Purinergic Signalling, 2025)

Insulin like growth factor binding protein 7 activate JNK/ERK signaling to aggravate uranium-induced renal cell cytotoxicity - Ling Peng; Xi Chen; An-qun Wang; Gang Xie; Bin Zhang; Jia-fu Feng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Discovery of large-scale natural hydrogen leakage in the Zhangbei Basin, North China - Jianliang Jia; Minjie Lu; Bingchuan Yin; Zhuangwei Luo; Ling Liu; Qianning Tian; Gang Fu; Yanming Liu; Yanming Wan; Huiqun Yang (Science Bulletin, 2025)

Effect of hydrochemical conditions on transport of HFPO-DA in saturated quartz sand and limestone porous media - Yanfeng Shi; Xinle Han; Lixingzi Wu; Ling Fu; Weina Xue; Xuli Jing; Jing Xu; Zhibin Zhang; Botao Ding (Environmental Geochemistry and Health, 2025)

Discovery of structurally intriguing diterpenoids as anti-neuroinflammatory agents from mangrove plant Excoecaria agallocha L. via inhibiting macrophage polarization and inflammasome - Jun-Yi Li; Ming-Bin Chen; Ting-Ting Fu; Fei-Fei Liu; Jin Liu; Cong-Jun Xu; Jing Zhou; Yong Rao; Zhong-Ping Jiang; Ling Huang (Phytochemistry, 2025)

Selective salt separation and resource recovery via nanofiltration in coal-to-ethylene glycol wastewater - Zheng-Jun Fu; Bo-Zhi Chen; Kai Yu; Jian-Guo Hu; Pengli Chen; Hui-Qin Zhang; Mei-Ling Liu; Shi-Peng Sun (Journal of Water Process Engineering, 2025)

Enhanced cathodic performance for simultaneous removal of Cr (VI) and norfloxacin: The synergistic effect and electron transfer triggered by high-entropy spinel oxide - Yu-Xin Guo; De-Wang Wei; Shang-Mei Fu; Ling-Zhen Miao; Lu Ying; Lei Wu; Jie Zhu (Journal of Environmental Chemical Engineering, 2025)

Clay/carbon composite aerogels for effective solar-driven water desalination and treatment - Huiquan Liu; Wen Luo; Shuai Wang; Yixuan Fu; Zhenxu Li; Yongchen Song; Lunxiang Zhang; Changrui Shi; Zheng Ling (Journal of Environmental Chemical Engineering, 2025)

The nuclear receptor gene SfE75 regulates the molting of Sogatella furcifera - Yi-Ming Wang; Yan-Yu Wang; Ming-Fu Gong; Shi-Yan Zhang; Jiang-Ling Chen; Xin Li; Cao Zhou; Hong Yang (Journal of Asia-Pacific Entomology, 2025)

New maps of mafic mineral abundances in global mare units on the Moon - Yuzhen Wang; Haijun Cao; Jian Chen; Changqing Liu; Xuejin Lu; Chengxiang Yin; Xiaohui Fu; Le Qiao; Guang Zhang; Chengbao Liu; Peng Zhang; Zongcheng Ling (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

The effect of catalyst preparation methods on biomass hydrothermal liquefaction: Exploring cleaner and more efficient pathways for catalytic hydrothermal liquefaction of biomass - Gui-zhong Deng; Xiao-dong Tang; Jing-jing Li; Si-hao Ling; Fu-xiang Yang; Shun-guo Wang (Fuel, 2025)

The role of clay in hydrate-based carbon emission reduction: Phenomenon, mechanisms, and application - Huiquan Liu; Shuai Wang; Yixuan Fu; Changrui Shi; Yongchen Song; Lunxiang Zhang; Cong Chen; Mingjun Yang; Zheng Ling (Fuel, 2025)

Climate suitability determines optimal yielding of dryland maize: A validation on timely sowing as an ancient wisdom - Jing Wang; Ling Zhao; Meng Hao; Ning Wang; Qing-Hui Wen; Fu-Jian Mei; Aziz Khan; Bao-Zhong Wang; Xiao-Lin Zhang; Wei Wang; Chang-Lang Yang; Fei Mo; et al. (Field Crops Research, 2025)

Species-specific bioaccumulation and biotransformation of two novel brominated flame retardants in fish: Insights from isotope fractionation - Ling Mo; Guang-Yu Liao; Bin Tang; Cheng-Zhong Fu; Dong-Jing Zhou; Dong-Wei Du; Wei-Keng Luo; Rong-Fa Xu; Ming-Zhong Ren; Jing Zheng (Environmental Research, 2025)

The effect and mechanisms of nano cerium dioxide (Nano-CeO2) on cardiovascular development in zebrafish (Danio rerio) - Yiyun Liu; Yan-Ling Liao; Jin-Xia Wang; Bao-Fu Zhang; Qi-Ping Tang; Yuan Ding; Si-Jia Zuo; Qin-Hong Zhou; De-Sheng Pei (Environmental Pollution, 2025)

Reversing anther thermotolerance by manipulating the cis-elements in the promoter of a high-temperature upregulated gene Casein Kinase I in upland cotton - Yanlong Li; Yinuo Fu; Yaoyao Li; Rui Zhang; Jing Yang; Huanhuan Ma; Ling Min; Xianlong Zhang (Science China Life Sciences, 2025)

The application of multi-arc volumetric modulated arc therapy and fixed-field intensity modulated radiotherapy in the treatment of gynecologic cancer with large planning target volume - Jia-Ling Song; Yi-Zhao Zhang; Zhi-Long Zhang; Zheng-Feng Fu; Peng-Fei Sun (Physical and Engineering Sciences in Medicine, 2025)

Links between personality, metabolic rates, brain size, and spatial learning ability of goldfish (Carassius auratus) under two conditions of spatial learning - Wu-Xin Li; Shi-Jian Fu; Ling-Qing Zeng (Behavioral Ecology and Sociobiology, 2025)

Epidemiological status and genome characteristics of canine parvovirus in China from 2022 to 2024 - Haoqi Li; Hu Zhou; Linfeng Li; Xiaohu Han; Qinghua Shang; Chengguang Zhang; Ming Zhou; Zhen F. Fu; Jianqing Zhao; Ling Zhao (Archives of Virology, 2025)

Study on seeding delay time and lag distance of automatic section control system for maize seeder - Lin Ling; Hanqing Li; Yuejin Xiao; Weiqiang Fu; Jianjun Dong; Liwei Li; Rui Liu; Xinguang Huang; Guangwei Wu; Zhijun Meng; Bingxin Yan (Computers and Electronics in Agriculture, 2025)

Construction and evaluation of recombinant rabies virus encoding three copies codon-optimized G genes as inactivated rabies vaccine in dogs and cats - Ying Wu; Haoqi Li; Zongmei Wang; Tao Pei; Qinghua Shang; Jianqing Zhao; Ming Zhou; Zhen F. Fu; Chengguang Zhang; Ling Zhao (Veterinary Microbiology, 2025)

PRDX1 affects acrylamide-induced neural damage through the PTEN/AKT signaling pathway - Dong-Xue Fu; Ya-Ting Lei; Hai-Bo Guo; Ting Chen; Xiang-Ying Gao; Xiao-Li Wang; Xiang Huang; Ling-Ling Song; Sheng-Yuan Wang; Qin-Xue Dai (NeuroToxicology, 2025)

Immune function in mice enhanced by lamb soup colloidal nanoparticles: Plasma immune, metabolomics, signaling pathways - Jianing Fu; Shaobo Li; Ling Liu; Li Chen; Dequan Zhang (Food Research International, 2025)

Sensitive detection of monosultap using a BSA-Cu nanocluster-based turn-off-on fluorescent sensor - Siying Che; Gaoqiong Deng; Tingyong Ling; Haiyan Fu; Yuanbin She (Food Control, 2025)

Microplastics in groundwater: Environmental fate and possible interactions with coexisting contaminants - Shengfeng Liu; Chengcheng Li; Jochen Bundschuh; Xubo Gao; Xing Gong; Huihui Li; Mengyun Zhu; Ling Yi; Wenxuan Fu; Fengze Yu (Environmental Pollution, 2025)

Mechanochemical treatment boosted microwave-assisted sulfonation of softwood lignin for the fabrication of dye dispersant - Xu Fu; Ling-Ping Xiao; Bo-Wen Meng; Wen-Jie Li; Run-Cang Sun (Chemical Engineering Journal, 2025)

Slowing wind increases soil carbon emissions in a fragmented subtropical forest: a study combining field and model experiments - Hao-Hao Wu; Ling-Ling Zhang; Ai-Min Liao; Hua-Wu Wu; Xiao-Ming Lai; Hai-Xia Zhang; Ye Xia; Yang Cao; Zi-Chun Zhu; Zhen-Ming Ji; Cong-Sheng Fu (Plant and Soil, 2025)

Effects of 2-hydroxypropyl-β-cyclodextrin and 28-homobrassinolide on the physiological characteristics, gene expression and terpenoid indole alkaloid accumulation in Catharanthus roseus cambial meristematic cell cultures - Fangfang Fu; Haihua Li; Li Ling; Jiahe Li; Yifei Chen; Weijie Hu; Jiayu Li; Lin Ou; Zhaoxi Chen; Jun Li; Pengfei Zhou (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Accurately estimating and revealing the patterns of leaf C:N:P stoichiometry with remote sensing and neural network methods in a karst area - Wen He; Yuefeng Yao; Yanqiong Li; Ling Yu; Longkang Ni; Bolin Fu; Jinjun Huang; Donxing Li (Computers and Electronics in Agriculture, 2025)

Karst water quality, source of pollution, and health risk assessment in China - Gongzhe Peng; Xubo Gao; Aqsa Naseem; Yunfei Zhang; Xiangjie Wang; Wenxuan Fu; Fengze Yu; Siyuan Ma; Wanpeng Shi; Ling Yi; Chengcheng Li; Wei Liu; et al. (Science of The Total Environment, 2025)

10Be records of the Matuyama-Brunhes polarity reversal in the northeastern Chinese loess Plateau - Ling Tang; Weijian Zhou; Xisheng Wang; Feng Xian; Xianghui Kong; Yajuan Du; Jie Zhou; Guoqing Zhao; Yunchong Fu; Ning Chen (Quaternary Science Reviews, 2025)

Numerical study of deformation inhomogeneity and its effect on mechanical properties of the heavy-wall offshore pipeline fabricated by different processes - Ling-zhi Xu; Gui-ying Qiao; Ying-long Ma; Yu Gu; Kai Xu; Xiao-wei Chen; Fu-ren Xiao (Ocean Engineering, 2025)

Highly efficient and convenient QuEChERS using ZIF-67 derived magnetic nanoporous carbon for determination of carbamate pesticides in various vegetable and fruit samples - Zi-Ling Li; Xiao-Run Qi; Yi-Heng Xu; Jia-Qi Zhao; Gui-Fu Zuo; Man-Man Wang (Food Chemistry, 2025)

Flexible surface acoustic wave technology for enhancing transdermal drug delivery - Jikai Zhang; Duygu Bahar; Hui Ling Ong; Peter Arnold; Meng Zhang; Yunhong Jiang; Ran Tao; Luke Haworth; Xin Yang; Chelsea Brain; Mohammad Rahmati; Hamdi Torun; et al. (Drug Delivery and Translational Research, 2025)
Transdermal drug delivery provides therapeutic benefits over enteric or injection delivery because its transdermal routes provide more consistent concentrations of drug and avoid issues of drugs affecting kidneys and liver functions. Many technologies have been evaluated to enhance drug delivery through the relatively impervious epidermal layer of the skin. However, precise delivery of large hydrophilic molecules is still a great challenge even though microneedles or other energized (such as electrical, thermal, or ultrasonic) patches have been used, which are often difficult to be integrated into small wearable devices. This study developed a flexible surface acoustic wave (SAW) patch platform to facilitate transdermal delivery of macromolecules with fluorescein isothiocyanates up to 2000 kDa. Two surrogates of human skin were used to evaluate SAW based energized devices, i.e., delivering dextran through agarose gels and across stratum corneum of pig skin into the epidermis. Results showed that the 2000 kDa fluorescent molecules have been delivered up to 1.1 mm in agarose gel, and the fluorescent molecules from 4 to 2000 kDa have been delivered up to 100 µm and 25 µm in porcine skin tissue, respectively. Mechanical agitation, localised streaming, and acousto-thermal effect generated on the skin surface were identified as the main mechanisms for promoting drug transdermal transportation, although micro/nanoscale acoustic cavitation induced by SAWs could also have its contribution. SAW enhanced transdermal drug delivery is dependent on the combined effects of wave frequency and intensity, duration of applied acoustic waves, temperature, and drug molecules molecular weights. Graphical Abstract Graphical Abstract: Flexible surface acoustic wave technology for enhancing transdermal drug delivery

Flame-retardant effect of scalable all clay composite films - Yixuan Fu; Zhaoyi Wang; Huiquan Liu; Ke Zhang; Lunxiang Zhang; Yongchen Song; Peng Wu; Yanghui Li; Zheng Ling (Applied Clay Science, 2025)

Dietary supplementation of Litsea cubeba oil promotes growth and intestinal immunity in GIFT tilapia - Fu-Yan Chen; Ying Bai; Gan Yang; Han-Jing Yan; Liu-Yang Li; Zhi-Mou Liu; Ju-Ping Wen; Zhen-Bin Wang; Jun-Hong Xia; Meng-Ling He (Aquaculture, 2025)

Adjusting the pattern of source separation and recycling can substantially mitigate environmental impacts and promote carbon neutrality in China - Mange Zhang; Minmin Zhou; Hui Ling; Haixia Fu; Qingsong Hu; Yanchao Bai; Zhigang Wang; Wengang Zuo; Yunlong Li; Binxian Gu (Environmental Impact Assessment Review, 2025)

Kaempferol attenuates cyclosporine-induced renal tubular injury via inhibiting the ROS-ASK1-MAPK pathway - Yaowu Zhang; Qijing Wu; Huali Fu; Jieya Pang; Yiyuan Zhang; Hui Zhou; Ling Zhuang; Xiaobo Zhang; Lianhua Chen; Qianqian Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Electroacupuncture Promotes the Generation of Intestinal Treg Cells After Ischemic Stroke by Foxp3 Acetylation Regulation - Yonglin Chen; Ling Ouyang; Xinyi Yang; Bufan Wu; Lingling Meng; Jialin Gu; Yaling Wang; Juan Li; Jingjing Zhang; Xinyue Jing; Shengfeng Lu; Lanying Liu; et al. (Molecular Neurobiology, 2025)

Morphology and molecular analysis of Heterodera camelliae n. sp. (Nematoda: Heteroderinae), a new species of cyst‑forming nematode parasitizing tea plants in China - Chun-Hui Ni; Qian-Ying Li; Zai-Fu Yang; Chun-Ling Xu; Hui Xie (European Journal of Plant Pathology, 2025)

Chinese loess 10Be records for the Jaramillo polarity subchron - Weijian Zhou; Yajuan Du; Xiaolong Zhou; Xianghui Kong; Feng Xian; Ling Tang; Jie Zhou; Guoqing Zhao; Yunchong Fu; Mengyu Zang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Enhanced photocatalytic activation of peroxymonosulfate by modifying single Fe atoms and Fe atomic clusters for oxytetracycline degradation under high salinity conditions - Mingming Zhang; Cui Lai; Fuhang Xu; Shiyu Liu; Yukui Fu; Ling Li; Xuerong Zhou (Journal of Environmental Chemical Engineering, 2025)

Catalytic detoxification of mitoxantrone by graphitic carbon nitride (g-C3N4) supported Fe/Pd bimetallic nanoparticles - Qianyu Xu; Haoyang Fu; Jiyuan Gu; Liyu Lei; Lan Ling (Journal of Environmental Sciences, 2025)

Rapid formation of carbon dioxide hydrate governed by the natural nano-clay for effective carbon dioxide capture - Huiquan Liu; Shuai Wang; Changrui Shi; Yongchen Song; Yixuan Fu; Zhen Li; Lunxiang Zhang; Cong Chen; Mingjun Yang; Zheng Ling (Fuel, 2025)

Microbial and chemical diversity analysis reveals greater heterogeneity of Liubao tea than ripen Pu-erh tea - Hao-Yi Yan; Meng-Fu Chen; Yi-Chen Hu; Ya-Shuai Kong; Tie-Jun Ling (Food Research International, 2025)

Protective effect of Apelin-13 on oxygen and glucose deprivation induced-damage in retinal ganglion cells cultured in vitro - Li Dai; Linlin Luo; Ya Zhang; Min Fu; Ling Yu (Journal of Molecular Histology, 2025)

The Efficacy of Cardiac Contractility Modulation for Treating Patients with Heart Failure - NingNing Zheng; YongBing Fu; MingZhu Xu; Lin Ling; TingBo Jiang; Feng Xue (Cardiovascular Engineering and Technology, 2025)

Analysis of a Hail Process in Foshan, Guangdong Province Using an Advanced Phased-Array Radar System and Development of a New Early Warning Index - Ling Yang; Jie Fu; Zhaoming Li; Shuqing Ma; Wanyi Wei; Yang Liu (Journal of Meteorological Research, 2025)

Natural or man-made disaster? Lessons from the extreme rain and flood disaster in Zhengzhou, China on "2021.7.20″ - Yan Zhu; Yun Liu; Ling Zhu; Min Liu; Zhiqiang Xie; Junxu Chen; Xingfeng Fu; Qisheng Wang; Zhanhui Wang; Qingyun Du (Sustainable Cities and Society, 2025)

How climate risks relate to Chinese green finance markets in time-frequency domains? A consideration of extreme market conditions - Rongyan Liu; Lingyun He; Ling Chen; Yating Fu (Journal of Cleaner Production, 2025)

Absorption and transport mechanism of colloidal nanoparticles (CNPs) in lamb soup based on Caco-2 cell - Jianing Fu; Shaobo Li; Meizhen Xu; Ling Liu; Li Chen; Dequan Zhang (Food Chemistry, 2025)

Elevated CO2 alters antibiotic resistome in soil amended with sulfamethazine via chemical-organic fertilization - Fen Xu; Qian Xiang; Mei-Ling Xu; Laura J. Carter; Wen-Chao Du; Chun-Wu Zhu; Fu-Xun Ai; Ying Yin; Rong Ji; Hong-Yan Guo (Environmental Research, 2025)

Efficient hydrogen production and optional power generation through coal-assisted water electrolysis - Ling Fu; Senran Hao; Hailong Liao; Wenrui Liu; Yuan Zhang; Haojie Zhu; Tao Liu; Bin Chen; Heping Xie (Chemical Engineering Journal, 2025)

Activation of 5-HT6 Receptors in the Ventrolateral Orbital Cortex Produces Anti-Anxiodepressive Effects in a Rat Model of Neuropathic Pain - Yu-Long Zhao; Hui-Yuan Yi; Sani Sa’idu Baba; Yi-Xiao Guo; Xiao-Cui Yuan; Xue-Mei Hou; Ling-Li Liang; Fu-Quan Huo (Molecular Neurobiology, 2025)

Joint Retrieval of PM2.5 Concentration and Aerosol Optical Depth over China Using Multi-Task Learning on FY-4A AGRI - Bo Li; Disong Fu; Ling Yang; Xuehua Fan; Dazhi Yang; Hongrong Shi; Xiang’ao Xia (Advances in Atmospheric Sciences, 2025)

First report of Viola philippica Cav. leaf spot caused by Pseudomonas viridiflava in China - Yao Fu; Yan Wang; Ling Jin; Hanyu Luan; Yunyao Wang (Journal of Plant Pathology, 2024)

Are the impacts of uncertainties on clean and conventional energy markets symmetrical? A fresh comparison analysis based on direction, quantile, and time-domain - Ling Chen; Lingyun He; Rongyan Liu; Yating Fu (Environment, Development and Sustainability, 2024)

Roles of boron in preventing cadmium uptake by Capsicum annuum root tips: Novel insights from ultrastructural investigation and single-cell RNA sequencing - Baifei Huang; Yingying Huang; Chuang Shen; Ling Fan; Huiling Fu; Zhilin Liu; Yingfang Sun; Bin Wu; Jirong Zhang; Junliang Xin (Science of The Total Environment, 2024)

Metabolic engineering of Escherichia coli for upcycling of polyethylene terephthalate waste to vanillin - Yang Li; Xiao-Min Zhao; Si-Qi Chen; Zhao-Yuan Zhang; Qi-Sheng Fu; Shu-Min Chen; Sheng Chen; Jing Wu; Ke-Wei Xu; Ling-Qia Su; Zheng-Fei Yan (Science of The Total Environment, 2024)

Hydrogeochemical differences drive distinct microbial community assembly and arsenic biotransformation in unconfined and confined groundwater of the geothermal system - Ling-Zhi Zhang; Shi-ping Xing; Fu-Yi Huang; Wei Xiu; Jonathan R. Lloyd; Christopher Rensing; Yi Zhao; Huaming Guo (Science of The Total Environment, 2024)

Assessing the discrepant role of anions in the transformation of reactive oxygen species in H2O2 and PDS system: A comparative kinetic analysis - Ling Li; Min Cheng; Hao Sun; Huan Yi; Shiyu Liu; Mingming Zhang; Yukui Fu; Xuerong Zhou; Fuhang Xu; Dengsheng Ma; Guangming Zeng; Zhengjian Yang; et al. (Journal of Hazardous Materials, 2024)

Ion-exchange induced multiple effects to promote uranium uptake from nonmarine water by micromotors - Linhui Fu; Kai Feng; Qianqian Li; Mengting Qin; Jing Yang; Xinle Zhang; Ling Chen; Jiang Gong; Jinping Qu; Ran Niu (Journal of Hazardous Materials, 2024)

Recent progress of piezoelectric materials applied in photocatalytic CO2 reduction: A review - Yi-fu Liu; Rui-tang Guo; Sheng-hui Guo; Ling-qi Yu; Ji-song Yan; Wei-guo Pan (Journal of Environmental Chemical Engineering, 2024)

Insights into novel phosphorus-doped biochar for tetracycline removal: Non-radical oxidation and adsorption - Xi Fu; Xiaojun Niu; Dongqing Zhang; Ling Li; Xingyao Ye; Shan Liao; Maoyu Li; Chuting Lao; Deye Chen; Yu Lin; Zhiquan Yang (Journal of Environmental Chemical Engineering, 2024)

HyperDehazing: A hyperspectral image dehazing benchmark dataset and a deep learning model for haze removal - Hang Fu; Ziyan Ling; Genyun Sun; Jinchang Ren; Aizhu Zhang; Li Zhang; Xiuping Jia (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Optimizing starch content prediction in kudzu: Integrating hyperspectral imaging and deep learning with WGAN-GP - Huiqiang Hu; Yunlong Mei; Yiming Zhou; Yuping Zhao; Ling Fu; Huaxing Xu; Xiaobo Mao; Luqi Huang (Food Control, 2024)

Real-time monitoring of activated sludge flocs via enhanced mask region-based Convolutional Neural networks - Tie-Fu Xu; Cai-Ling He; Guo-Tao Wang; Bo-Wen Li; Yu Tao (Environmental Research, 2024)

Biomimetic Stylophora pistillata-like NiMoO4/NiFeS crystalline–amorphous phase boundary activated lattice oxygen mechanism for efficient electrochemical water oxidation - Weikai Fan; Chaofan Liu; Jiang Wu; Hao Zhou; Tao Jia; Yang Ling; Ping He; Qunzhi Zhu; Zaiguo Fu; Mingze Ou; Jia lin; Zhongwei Chen (Chemical Engineering Journal, 2024)

Activating copper by creating low-coordinated copper sites for antibiotic detoxification through Electrocatalytic hydrodechlorination reaction - Xiangyi Tang; Fei Shen; Wei Fan; Jianhui Liu; Lingpiao Chen; Yinan Liu; Liang Ao; Xiaoshu Lv; Wenyang Fu; Yan Zou; Ling Chen; Yan Jiang; et al. (Chemical Engineering Journal, 2024)

Highly stable zinc anodes enabled by a dual-function additive of in-situ film formation and electrostatic shielding - Rui-han Ji; Hao Fu; Qing Wen; Pei-Yao Li; Pei Yang; Yu-Jing Chen; He-zhang Chen; Jia-feng Zhang; Ling-jun Li; Jie-xi Wang; Qing Wu; Xia-hui Zhang; et al. (Chemical Engineering Journal, 2024)

Clay composition heterogeneity in sediments from mountainous catchments with contrasting bedrock lithology in SE China coast - Ling Wang; Xing Jian; Haowei Mei; Xiaotian Shen; Hanjing Fu (CATENA, 2024)

High efficiency removal of antibiotic resistance gene with designer zinc-finger protein - Jianghao Yu; Meng Fang; Lulu Shi; Jiaming Zhu; Chengzhang Fu; Youming Zhang; Hai Xu; Ling Li; Yu Shen; Mingyu Wang (Bioresource Technology, 2024)

A novel inactivated oral rabies vaccine with the incorporation of U-OMP19 enhances the immunogenicity by reducing viral proteins degradation and activating dendritic cells in a mouse model - Zonghui Zeng; Di Wu; Jingyi Xiong; Jianqing Zhao; Chuan Liang; Qiong Wu; Chengli Huang; Rui Zhou; Zhen F. Fu; Ling Zhao; Ming Zhou (Veterinary Microbiology, 2024)

Z-Ligustilide restricts rabies virus replication by inducing ferroptosis through the ACSL4-LPCAT3-POR pathway - Jianqing Zhao; Qianruo Wang; Zhenkun Liu; Meixin Sun; Rui Zhou; Zhen F. Fu; Ling Zhao; Ming Zhou (Veterinary Microbiology, 2024)

Detrital muscovite 40Ar/39Ar geochronology and provenance of Cenozoic deposits in the Qaidam basin, northern Tibetan Plateau and comparison with detrital zircon and apatite records - Shuhuai Ye; Xing Jian; Ling Fu; Wei Zhang; Xiaotian Shen; Ping Guan (Marine and Petroleum Geology, 2024)

Highly effective fluorescence detection of UO22+ ions by an anionic Na/Eu heterometallic metal–organic framework with Lewis basic chelating sites - Feng Guo; Xue-Ling Han; Duo-Fu Li; Chun-Yang Li; Dong-Ping Li; Zhi-Kang Yao; Li-Ping Wang; Yong-Xiu Li (Chemical Engineering Journal, 2024)

Scalable MXene/Sepiolite film-based hydrovoltaic generators with outstanding output power - Weijing Yuan; Huiquan Liu; Yixuan Fu; Yang Zhang; Haoqi Huo; Lunxiang Zhang; Mingjun Yang; Yanghui Li; Cong Chen; Yongchen Song; Zheng Ling (Chemical Engineering Journal, 2024)

Link Brain-Wide Projectome to Neuronal Dynamics in the Mouse Brain - Xiang Li; Yun Du; Jiang-Feng Huang; Wen-Wei Li; Wei Song; Ruo-Nan Fan; Hua Zhou; Tao Jiang; Chang-Geng Lu; Zhuang Guan; Xiao-Fei Wang; Hui Gong; et al. (Neuroscience Bulletin, 2024)
Knowledge about the neuronal dynamics and the projectome are both essential for understanding how the neuronal network functions in concert. However, it remains challenging to obtain the neural activity and the brain-wide projectome for the same neurons, especially for neurons in subcortical brain regions. Here, by combining in vivo microscopy and high-definition fluorescence micro-optical sectioning tomography, we have developed strategies for mapping the brain-wide projectome of functionally relevant neurons in the somatosensory cortex, the dorsal hippocampus, and the substantia nigra pars compacta. More importantly, we also developed a strategy to achieve acquiring the neural dynamic and brain-wide projectome of the molecularly defined neuronal subtype. The strategies developed in this study solved the essential problem of linking brain-wide projectome to neuronal dynamics for neurons in subcortical structures and provided valuable approaches for understanding how the brain is functionally organized via intricate connectivity patterns.

NUS1 Variants Cause Lennox-Gastaut Syndrome Related to Unfolded Protein Reaction Activation - Nan-Xiang Shen; Xiao-Chong Qu; Jing Yu; Cui-Xia Fan; Fu-Li Min; Ling-Ying Li; Ming-Rui Zhang; Bing-Mei Li; Jie Wang; Na He; Wei-Ping Liao; Yi-Wu Shi; et al. (Molecular Neurobiology, 2024)

A collaborative governance model for electric vehicle charging infrastructure incorporating policy evaluation and feedback - Yiting Zhang; Henry J. Liu; Shuai Ling; Dan Wang; Yifan Fu; Xueqing Wang (Utilities Policy, 2024)

Contamination characteristics and dietary intake risk of brominated flame retardants in fishes around a typical e-waste dismantling site in Southern China - Shanqi Zhou; Zhihua Qiao; Siyuan Ling; Mengru Fu; Yanna Han; Cheng Peng; Wei Zhang; Juying Lei (Science of The Total Environment, 2024)

Comparative RNA-seq analysis of tomato (Solanum lycopersicum L.) provides insights into natural and postharvest ripening - Xiuming Zhao; Fujun Li; Jun Ding; Xiaodong Fu; Jing Shang; Xiangrong Kong; Xiaoan Li; Ling Li; Xinhua Zhang (Postharvest Biology and Technology, 2024)

Experimental investigation of the matching boundary and optimization strategy of a variable geometry turbocharged direct-injected hydrogen engine - Feng-yu Lai; Bai-gang Sun; Zhi-fu Zhang; Shi-wei Zhang; Kang-da Wang; Xue-ming Ju; Qing-he Luo; Ling-zhi Bao; Felix Leach (Fuel, 2024)

Positively charged loose nanofiltration membranes via the assembly of amino-quinone networks for efficient dye/salt separation - Tian Gao; Ping Fu; Wan-Long Li; Wan-Ting Lin; Yuan-Hui Yu; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Desalination, 2024)

Bi-allelic missense variants in MEI4 cause preimplantation embryonic arrest and female infertility - Zhiqi Pan; Weijie Wang; Ling Wu; Zhongyuan Yao; Wenjing Wang; Yao Chen; Hao Gu; Jie Dong; Jian Mu; Zhihua Zhang; Jing Fu; Qiaoli Li; et al. (Human Genetics, 2024)

The distribution and key influential factors of antibiotic resistance genes in agricultural soils polluted by multiple heavy metals - Xin Huang; Xin Zhao; Li Fu; Gang Yang; Ling Luo (Environmental Geochemistry and Health, 2024)

A universal electrochemical-modulated surface-enhanced Raman scattering platform for the sensitive detection of charged molecules - Huiqiao Liu; Jinjin Fu; Jiakun Zhang; Yulian Dong; Ling Yang; Juntao Cao; Yong Lei; Kangzhe Cao (Analytica Chimica Acta, 2024)

Simultaneous removal of Cd(II) and phosphate by nanoscale zero-valent iron from solution: Co-sorption and implication of corrosion - Haoyang Fu; Jie Sheng; Chenliu Tang; Wei-xian Zhang; Lan Ling (Chemosphere, 2024)

Integrated tea polyphenols and polydopamine functionalized graphene anode for improved bioelectricity generation and Cr(VI) reduction in microbial fuel cells - Deliang Guo; Xinru Wang; Qikai Fu; Ling Li; Runze Li; Xiaolin Xu; Xiongfang An (Chemosphere, 2024)

The crosslinking sites and molecular conformation of gelatin hydrogel modified by transglutaminase - Yunke Yang; Ling Mao; Hai Chen; Liang Ma; Yu Fu; Yuhao Zhang (Food Hydrocolloids, 2024)

Preparation of modified atmosphere and moisture packaging membranes by blending quaternized polyether ether ketone with polyvinylidene fluoride and its application in grape packaging - Wenlian Liu; Wenjie Fu; Ling Zhang; Liang Zhu (Food Packaging and Shelf Life, 2024)

Epinephelus coioides Sec3 promotes Singapore grouper iridovirus infection by negatively regulates immune response - Yu-Rong Lei; Jia-Yang He; Xue-Mei Fu; Cui-Fen Huang; Yun-Xiang Lin; Li-Ling Dai; Zi-An Chen; Ze-Peng Zhang; Fu-Min Liu; Qi-Wei Qin; Hong-Yan Sun (Fish & Shellfish Immunology, 2024)

Preparation of water-soluble dietary fiber from bamboo shoots by fungi fermentation and its supplementation in biscuits - Ying Shen; Ling Yang; Hong Peng; Limin Shen; Guiming Fu; Yin Wan; Yuhuan Liu; Xiaodan Wu; Hongli Zheng (Food and Bioproducts Processing, 2024)

Rare earth element enrichment process of bioapatite in deep-sea REY-rich sediments - Hao Wang; Zhenggang Li; Yanhui Dong; Bin Fu; Xiaohu Li; Jie Li; Fengyou Chu; Weiyan Zhang; Zhiming Zhu; Jihao Zhu; Ling Chen (Chemical Geology, 2024)

Physiological and behavioral responses to social isolation and starvation in a social fish - Dan-Dan Xu; Chun-Hua Wang; Jin-Qiu Bi; Huan Luo; Shi-Jian Fu; Bin Li; Ling-Qing Zeng (Applied Animal Behaviour Science, 2024)

Activation of GPR30 Ameliorates Cerebral Ischemia–Reperfusion Injury by Suppressing Ferroptosis Through Nrf2/GPX4 Signaling Pathway - Yong-qiang Zhang; Ting Sun; Zhen Zhao; Jing Fu; Le Yang; Yuan Xu; Jing-feng Zhao; Xiu-ling Tang; An Liu; Ming-gao Zhao (NeuroMolecular Medicine, 2024)

RTP4 restricts lyssavirus rabies infection by binding to viral genomic RNA - Baokun Sui; Jiaxin Zheng; Juanjuan Zhao; Zhenfang Fu; Ming Zhou; Ling Zhao (Veterinary Microbiology, 2024)

Establishment of a callus induction system of Saxifraga stolonifera Meerb. and its response to different elicitors - Lin Song; Ta Zhao; Chun-Li Luo; Jin-Ling Li; Song-Shu Chen; Dan-Dan Li; Jin Liang; Hong-Chang Liu; Fu-Lai Luo; Ming-Jin Huang; Hua-Lei Wang (South African Journal of Botany, 2024)

Are cretaceous intermediate–mafic igneous rocks from the northern South China Sea indicative of the slab rollback of the Paleo-Pacific Plate? - Ling Zhong; Ming-Cai Hou; Fei Wang; Ying Xia; Fu-Hao Xiong; Hai-Yang Cao (Lithos, 2024)

Detection of allophane by the Zhurong rover indicates water-limited alteration at Utopia Planitia, Mars - Enming Ju; Changqing Liu; Jian Chen; Xiaojia Zeng; Yanqing Xin; Ping Liu; Xiaohui Fu; Zongcheng Ling (Earth and Planetary Science Letters, 2024)

Cross-linked g-C3N4 nanofibers enable thermal stable composite membranes for high-performance loose nanofiltration - Wan-Ting Lin; Ping Fu; Wan-Long Li; Yuan-Hui Yu; Zi-Lu Zhang; Hong-Yu Fan; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Chemical Engineering Journal, 2024)

Sensitivity of atmospheric peroxyacetyl nitrate (PAN) formation and its impact on ozone pollution in a coastal city - Nan Fu; Li-Ming Cao; Shi-Yong Xia; Le-Wei Zeng; Li He; Ling-Yan He; Xiao-Feng Huang (Atmospheric Environment, 2024)

Individual and group behavioral responses to nutritional state and context in a social fish - Ling-Qing Zeng; Hong Ling; Shi-Jian Fu; De-Yong Pu; Shaun S. Killen (Behavioural Processes, 2024)

Over-expression of SgRVE1 from fine-stem stylo (Stylosanthes guianensis var. intermedia) up-regulates CBF gene expression and enhances cold tolerance in Arabidopsis - Cong-Cong Wang; Chen Liang; Han-Ying Li; Huai-An Huang; Liang-Liang He; Cui-Ling Liu; Zhi-Hao Wu; Chun-Sheng Gui; Ci Ren; Yi-Hua Wang; Hao-Yu Yang; Dan-Wen Zhong; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

The phosphate-solubilising fungi in sustainable agriculture: unleashing the potential of fungal biofertilisers for plant growth - Shih-Feng Fu; Vignesh Kumar Balasubramanian; Chih-Ling Chen; Thuy Trang Tran; Jothi Basu Muthuramalingam; Jui-Yu Chou (Folia Microbiologica, 2024)

Beauveria bassiana (Ascomycota: Hypocreales) spores carried by Scleroderma guani (Hymenoptera: Bethylidae): a novel strategy for improving the control efficiency of Semanotus bifasciatus (Coleoptera: Cerambycidae) in the field - Jian-Yong Zeng; Jia-Wei Bai; Hua-Ling Wang; Xiao-Yu Su; Xue-Fei Wang; Ning-Ning Fu; Hui-Ping Li (BioControl, 2024)

Five coexisting brominated flame retardants in a water-sediment-Vallisneria system: Bioaccumulation and effects on oxidative stress and photosynthesis - Mengru Fu; Zhihua Qiao; Shanqi Zhou; Yanna Han; Siyuan Ling; Cheng Peng; Wei Zhang; Jinhong Wu (Science of The Total Environment, 2024)

Structurally diverse isoquinoline alkaloids from the barks of Alangium salviifolium (L. f.) Wangerin and their cytotoxicity - Yan-Mei Wei; Xuan Zhang; Fu-Ling Cen; Yi-Yi Du; Yuan-Ling Liu; Qiao-Yuan Han; Zhang-Xin Yu; Guang-Ying Chen (Phytochemistry, 2024)

Plastid engineering with an efficient RNAi delivery system based on bacteriophage MS2 virus-like particles enhances plant resistance to cotton bollworm - Chunmei Jiang; Jinqiu Fu; Fujun Li; Kai Xia; Shengchun Li; Ling Chang; Ralph Bock; Jiang Zhang (Molecular Plant, 2024)

Geologic context of Chang'e-6 candidate landing regions and potential non-mare materials in the returned samples - Ziyi Jia; Jian Chen; Jiaqi Kong; Le Qiao; Xiaohui Fu; Zongcheng Ling (Icarus, 2024)

Electronic-rich large conjugated molecules dispersing through ionic liquid solution process for fluorescent detection of iodine gas - Yue-Ru Zhou; Shuang-Long Wang; Lei Zhang; Jie Fu; Ling He; Guo-Hong Tao (Chemical Engineering Journal, 2024)

Tough and biodegradable C-lignin cross-linked polyvinyl alcohol supramolecular composite films with closed-looping recyclability - Tao Gui; Ling-Ping Xiao; Shuang-Lin Zou; Yue Zhang; Xu Fu; Chang-Hao Liu; Run-Cang Sun (Chemical Engineering Journal, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Investigation of the Inhibitory Effects of Illicium verum Essential Oil Nanoemulsion on Fusarium proliferatum via Combined Transcriptomics and Metabolomics Analysis - Cui-Qiong Ling; Hong-Xin Liao; Jin-Rui Wen; Hong-Yan Nie; Li-Yan Zhang; Fu-Rong Xu; Yong-Xian Cheng; Xian Dong (Current Microbiology, 2024)

Research on the dynamic resilience characteristics of carbonaceous mudstone soil-rock mixture under wet-dry cycles - Qiyi Yang; Wei Wen; Ling Zeng; Hongyuan Fu; Lu Chen; Hanbing Bian; Hongri Zhang (Bulletin of Engineering Geology and the Environment, 2024)

Cotransport of nanoplastics and plastic additive bisphenol AF (BPAF) in unsaturated hyporheic zone: Coupling effects of surface functionalization and protein corona - Xin Ling; Guanghua Lu; Leibo Zhang; Jiaqi Zhang; Heyun Fu; Zhenhua Yan (Water Research, 2024)

Recent progresses on emerging biosensing technologies and portable analytical devices for detection of food allergens - Danqing Zhu; Shiqian Fu; Xiru Zhang; Qianyu Zhao; Xinyan Yang; Chaoxin Man; Yujun Jiang; Ling Guo; Xianlong Zhang (Trends in Food Science & Technology, 2024)

The delaying effect of Clausena lansium extract on pear ring rot is related to its antifungal activity and induced disease resistance - Wen-Wu Song; Xiao-Xiang Fu; Duan-Tao Cao; Xiao-Gui Liang; Su-Ling Xiao; Min-Xuan Yuan; Ying-Jin Huang; Qing-Hong Zhou; Hong-Yi Wei; Jun-Wen Wang; Wen-Wen Peng (Postharvest Biology and Technology, 2024)

Genomic analysis of Cobetia sp. D5 reveals its role in marine sulfur cycling - Xiao-Mei Geng; Shi-Ning Cai; Hai-Xia Zhu; Zhi-Gang Tang; Chun-Yang Li; Hui-Hui Fu; Yi Zhang; Hai-Yan Cao; Peng Wang; Mei-Ling Sun (Marine Genomics, 2024)

Research on the economic agents' green co-evolution of China: Framework, model, and application - Ling Chen; Lingyun He; Rongyan Liu; Yating Fu; Quanhui Yang (Journal of Cleaner Production, 2024)

Sulfation, characterization, antibacterial activity, and action mechanism of rice bran polysaccharides - Bing-Jie Chen; Yong-Jin Qiao; Gang Yu; Xiao Wang; Yi Zhang; Ling-Lin Fu (Food Bioscience, 2024)

Identifying modifiable factors and their joint effect on brain health: an exposome-wide association study - Liang-Yu Huang; Yi-Jun Ge; Yan Fu; Yong-Li Zhao; Ya-Nan Ou; Yi Zhang; Ling-Zhi Ma; Shi-Dong Chen; Ze-Xin Guo; Jian-Feng Feng; Wei Cheng; Lan Tan; et al. (GeroScience, 2024)

Damage constitutive model for soft rocks and its experimental verification on silty mudstone considering cyclic rock‒water interactions - Xiao-Wei Yu; Hong-Yuan Fu; Ling Zeng; Jie Liu; Xing-Yu Qiu (Bulletin of Engineering Geology and the Environment, 2024)

LIPUS regulates the progression of knee osteoarthritis in mice through primary cilia-mediated TRPV4 channels - Sha Wu; Haiqi Zhou; Huixian Ling; Yuyan Sun; Ziyu Luo; ThaiNamanh Ngo; Yuanyuan Fu; Wen Wang; Ying Kong (Apoptosis, 2024)
Osteoarthritis (OA) is a common disease in middle-aged and elderly people. An imbalance in calcium ion homeostasis will contribute to chondrocyte apoptosis and ultimately lead to the progression of OA. Transient receptor potential channel 4 (TRPV4) is involved in the regulation of intracellular calcium homeostasis. TRPV4 is expressed in primary cilia, which can sense mechanical stimuli from outside the cell, and its abnormal expression is closely related to the development of OA. Low-intensity pulsed ultrasound (LIPUS) can alleviate chondrocyte apoptosis while the exact mechanism is unclear. In this project, with the aim of revealing the mechanism of action of LIPUS, we proposed to use OA chondrocytes and animal models, LIPUS intervention, inhibition of primary cilia, use TRPV4 inhibitors or TRPV4 agonist, and use Immunofluorescence (IF), Immunohistochemistry (IHC), Western Blot (WB), Quantitative Real-time PCR (QP) to detect the expression of cartilage synthetic matrix and endoplasmic reticulum stress markers. The results revealed that LIPUS altered primary cilia expression, promoted synthetic matrix metabolism in articular chondrocytes and was associated with primary cilia. In addition, LIPUS exerted a active effect on OA by activating TRPV4, inducing calcium inward flow, and facilitating the entry of NF-κB into the nucleus to regulate synthetic matrix gene transcription. Inhibition of TRPV4 altered primary cilia expression in response to LIPUS stimulation, and knockdown of primary cilia similarly inhibited TRPV4 function. These results suggest that LIPUS mediates TRPV4 channels through primary cilia to regulate the process of knee osteoarthritis in mice.

Inhibition of Microglial Activation Ameliorates Inflammation, Reduced Neurogenesis in the hippocampus, and Impaired Brain Function in a Rat Model of Bilirubin Encephalopathy - Yan Zhang; Siyu Li; Ling Li; Hongmei Huang; Zhou Fu; Ziyu Hua (Journal of Neuroimmune Pharmacology, 2024)

Identification of volatile compounds and their bioactivities from unpolar fraction of Alpinia oxyphylla Miq. and mining key genes of nootkatone biosynthesis - Fapetu Kemi Busayo; Jin-Ling Yang; Xu-Po Ding; Ya-Li Wang; Cui-Juan Gai; Fei Wu; Hao-Fu Dai; Wen-Li Mei; Hui-Qin Chen (Natural Product Research, 2024)

Alkaloids from the stems of Fissistigma maclurei Merr. inhibit the proliferation of synoviocytes - Mu-Tao Liang; Xiao-Zheng Zhang; Zi-Hao Chen; Chuan-Shan Fu; Duo-Jiang Li; Guo-Ze Chen; Ji-Ling Yi; Xue-Ming Zhou (Natural Product Research, 2024)

Mechanism of surface oxygen-containing species promoted electrocatalytic CO2 reduction - Zhanzhao Fu; Yixin Ouyang; Mingliang Wu; Chongyi Ling; Jinlan Wang (Science Bulletin, 2024)

Environmental concentrations of acetaminophen and its metabolites promote the spread of antibiotic resistance genes through pheromone signaling pathway - Xinyue Fu; Xiaobo Yang; Xiaoli Lin; Li Zhu; Panpan Yang; Feng Wang; Zhiqiang Shen; Jingfeng Wang; Yun Ling; Zhigang Qiu (Chemical Engineering Journal, 2024)

A novel ionic-liquid-mediated covalent organic framework as a strong electrophile for high-performance iodine removal - Jie Fu; Jia-Ying Liu; Yue-Ru Zhou; Lei Zhang; Shuang-Long Wang; Song Qin; Maohong Fan; Guo-Hong Tao; Ling He (Chemical Engineering Journal, 2024)

A new substrate equalization method for optimizing the influent conditions and fluid flow patterns of a multifed upflow anaerobic sludge blanket reactor with mature anammox granules - Bao-Shan Xing; Xi-Fang Tang; Ling-Hu Li; Yu-Lin Fu; Jia-Yi Liu; Ya-Ge Wang; Xin-Xin Sun; Yu-You Li; Rong Chen; Ren-Cun Jin (Bioresource Technology, 2024)

Cactodera guizhouensis n. sp. (Nematoda: Heteroderinae), a new species of cyst-forming nematode parasitizing potato in Guizhou, China - Chun-Hui Ni; Yu-Jia Xie; Si-Hua Yang; Zai-Fu Yang; Chun-Ling Xu; Hui Xie (European Journal of Plant Pathology, 2024)

Advances in ionogels for proton-exchange membranes - Yilin Zhou; Bei Wang; Zhiwei Ling; Qingting Liu; Xudong Fu; Yanhua Zhang; Rong Zhang; Shengfei Hu; Feng Zhao; Xiao Li; Xujin Bao; Jun Yang (Science of The Total Environment, 2024)

The association between artificial light at night and gestational diabetes mellitus: A prospective cohort study from China - Junhao Liao; Chuan Yu; Jiarui Cai; Run Tian; Xingyue Li; Hong Wang; Lin Li; Guishuang Song; Leyao Fu; Xinxi Li; Qiaoyue Ge; Ling Zhang; et al. (Science of The Total Environment, 2024)

Cadmium disrupts spermatogenic cell cycle via piRNA-DQ717867/p53 pathway - Jiaoyang Wei; Juan Dai; Xiaofan Shi; Ruixue Zhao; Guoqing Fu; Rui Li; Chao Xia; Ling Zhang; Ting Zhou; Huaiji Wang; Yuqin Shi (Reproductive Toxicology, 2024)

Dual-functional metal-organic frameworks-based hydrogel micromotor for uranium detection and removal - Xinle Zhang; Ling Chen; Linhui Fu; Kai Feng; Jiang Gong; Jinping Qu; Ran Niu (Journal of Hazardous Materials, 2024)

Existing levels of biodiversity and river location may determine changes from small hydropower developments - Qingyi Luo; Shuyin Li; Tsuyoshi Kinouchi; Naicheng Wu; Xiaocheng Fu; Chang Ling; Qinghua Cai; Ming-Chih Chiu; Vincent H. Resh (Journal of Environmental Management, 2024)

Electrospinning-assisted construction of rapid proton conduction channels in halloysite nanotube-encapsulated ionic liquid-embedded sulfonated poly(ether ether ketone) proton exchange membranes - Chunyong Xiong; Zhiwei Ling; Bei Wang; Yang Yu; Qingting Liu; Xudong Fu; Chonggang Wu; Rong Zhang; Shengfei Hu; Xujin Bao; Jun Yang (Fuel, 2024)

Nrf2-mediated ferroptosis of spermatogenic cells involved in male reproductive toxicity induced by polystyrene nanoplastics in mice - Xufeng Fu; Hang Han; Hong Yang; Bo Xu; Wenjie Dai; Ling Liu; Tiantian He; Xing Du; Xiuying Pei (Journal of Zhejiang University-SCIENCE B, 2024)

GNSS ionospheric integrity monitoring based on RBF-NN: constructing single-epoch snapshot GIVD and GIVE maps - Ling Yang; Yunri Fu; Jincheng Zhu; Yunzhong Shen; Chris Rizos (Journal of Geodesy, 2024)

Mortality risk of people living with HIV under hypothetical intervention scenarios of PM2.5 and HIV severity: a prospective cohort study - Shujuan Yang; Chuanteng Feng; Teng Fei; Dan Wu; Liao Feng; Fengshun Yuan; Yao Fu; Hua Ma; Bin Yu; Li Liu; Yizhuo Li; Yiping Li; et al. (Science of The Total Environment, 2024)

Hedscandines A-C, three undescribed indole alkaloids from Hedyotis scandens with their anti-MRSA activity - Yu-Jun Wang; Xue Chen; Yong Yin; Wei Zhou; Pei-Fu Zhou; Ling-Gao Zeng; Chang-Hua Hu; Guo-Ping Yin (Phytochemistry, 2024)

Bio-based ionic liquid filter with enhanced electrostatic attraction for outside filtration and inside collection of viral aerosols - Guo-Hao Zhang; Qiu-Hong Zhu; Lei Zhang; Lei Li; Jie Fu; Shuang-Long Wang; Wen-Li Yuan; Ling He; Guo-Hong Tao (Journal of Hazardous Materials, 2024)

Radiocarbon chronology of sediments with implications for climatic events in Lop Nur, NW China - Yuda Chui; Weijian Zhou; Peng Cheng; Ling Yang; Xingxing Liu; Jianghu Lan; Guoqing Zhao; Shugang Wu; Yunchong Fu; Xiaohu Xiong; Wei Gong (Journal of Asian Earth Sciences, 2024)

Enhancement of ester biosynthesis in blueberry wines through co-fermentation via cell–cell contact between Torulaspora delbrueckii and Saccharomyces cerevisiae - Yu Wang; Yu Fu; Qi Zhang; Yue Zhu; Qin Yang; Chen Bian; Lu-Lu Zhao; Qi Chen; Hai-Jun Bi; Xiao-Hui Yang; Xue-Ling Gao (Food Research International, 2024)

Bond strength prediction of FRP bars to seawater sea sand concrete based on ensemble learning models - Pei-Fu Zhang; Mudassir Iqbal; Daxu Zhang; Xiao-Ling Zhao; Qi Zhao (Engineering Structures, 2024)

Correction to: Pre-Injection of Small Interfering RNA (siRNA) Promotes c-Jun Gene Silencing and Decreases the Survival Rate of Axotomy-Injured Spinal Motoneurons in Adult Mice - Ying-qin Li; Fa-huan Song; Ke Zhong; Guang-yin Yu; Prince Last Mudenda Zilundu; Ying-ying Zhou; Rao Fu; Ying Tang; Ze-min Ling; Xiaoying Xu; Li-hua Zhou (Journal of Molecular Neuroscience, 2024)

Influence of speed measurement method on performance of an electric-drive maize precision planter - Lin Ling; Guangwei Wu; Changkai Wen; Yuejin Xiao; Weiqiang Fu; Jianjun Dong; Jianhong Ding; Zhijun Meng; Bingxin Yan (Biosystems Engineering, 2024)

Metabolic coupling of arsenic, carbon, nitrogen, and sulfur in high arsenic geothermal groundwater: Evidence from molecular mechanisms to community ecology - Ling-Zhi Zhang; Shi-ping Xing; Fu-Yi Huang; Wei Xiu; Christopher Rensing; Yi Zhao; Huaming Guo (Water Research, 2024)

Cholesterol depletion inhibits rabies virus infection by restricting viral adsorption and fusion - Qingxiu Hou; Caiqian Wang; Jingyi Xiong; Haoran Wang; Zhihui Wang; Juanjuan Zhao; Qiong Wu; Zhen F. Fu; Ling Zhao; Ming Zhou (Veterinary Microbiology, 2024)

Regional background ozone estimation for China through data fusion of observation and simulation - Zhixu Sun; Jiani Tan; Fangting Wang; Rui Li; Xinxin Zhang; Jiaqiang Liao; Yangjun Wang; Ling Huang; Kun Zhang; Joshua S. Fu; Li Li (Science of The Total Environment, 2024)

PPARβ/δ-ANGPTL4 axis mediates the promotion of mono-2-ethylhexyl phthalic acid on MYCN-amplified neuroblastoma development - Yiyun Liu; Naima Hamid; Rakia Manzoor; Bao-Fu Zhang; Yan-Ling Liao; Jin-Xia Wang; De-Sheng Pei (Science of The Total Environment, 2024)

AaABCG20 transporter involved in cutin and wax secretion affects the initiation and development of glandular trichomes in Artemisia annua - Xueqing Fu; Han Zheng; Yuting Wang; Hang Liu; Pin Liu; Ling Li; Jingya Zhao; Xiaofen Sun; Kexuan Tang (Plant Science, 2024)

Two new monoterpenoids from the roots of Paeonia lactiflora and their neuroprotective activities - Bo Fu; Jin-Ling Zhang; Xin Meng; Jia-Tong Wu; Yan Liu; Yu-Qing Wang; Yi-Qiang Zhang; Juan Pan; Wei Guan; Rui-Feng Fan; Anam Naseem; Hai-Xue Kuang; et al. (Phytochemistry Letters, 2024)

Ultrathin RhCu bimetallenes for the selective electro-oxidation of glycerol - Qing-Ling Hong; Yue Zhao; Xuan Ai; Yu Ding; Fu-Min Li; Pei Chen; Pu-Jun Jin; Yu Chen (Chemical Engineering Journal, 2024)

Recommendations on benchmarks for photochemical air quality model applications in China — NO2, SO2, CO and PM10 - Hehe Zhai; Ling Huang; Chris Emery; Xinxin Zhang; Yangjun Wang; Greg Yarwood; Joshua S. Fu; Li Li (Atmospheric Environment, 2024)

Human Bone Marrow Derived-Mesenchymal Stem Cells Treatment for Autoimmune Premature Ovarian Insufficiency - Wen-Qing Ma; Ai-Ping Zhuo; Yuan-Ling Xiao; Meng Gao; Yu-Tao Yang; Li-Chao Tang; Yan-Hong Wu; Dan Tian; Xia-Fei Fu (Stem Cell Reviews and Reports, 2024)

Damage Evolution During Rock Dynamic Compression Revealed by Wavelet Analysis of Acoustic Emission Signals - Ling Yang; Bangbiao Wu; Ying Xu; Yan Fu; Kaiwen Xia (Rock Mechanics and Rock Engineering, 2024)

Evaluation of 3D crustal seismic velocity models in southwest China: Model performance, limitation, and prospects - Xin Wang; Ling Chen; Qi-Fu Chen (Science China Earth Sciences, 2024)

Hydrogen sulfide promoted cell differentiation, antioxidant ability, and flavonoids accumulation in Ginkgo biloba L. suspension cells - Jin-ling Lu; Yu-chen Hu; Ying Chen; Rui Liu; Jing-jing Di; Ting-ting Feng; Fu-liang Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

A high-efficient protoplast transient system for screening gene editing elements in Salvia miltiorrhiza - Jin Shao; Bowen Peng; Yaojie Zhang; Xin Yan; Xinghao Yao; Xinyi Hu; Ling Li; Xueqing Fu; Han Zheng; Kexuan Tang (Plant Cell Reports, 2024)

TAT-W61 peptide attenuates neuronal injury through blocking the binding of S100b to the V-domain of Rage during ischemic stroke - Jia Liang; Hui Li; Chang‑Dong Liu; Xiao‑Yan Zhou; Yan‑Yan Fu; Xiang-Yu Ma; Dan Liu; Yu-Ling Chen; Qian Feng; Zhen Zhang; Xiang-Ru Wen; Guang Zhu; et al. (Journal of Molecular Medicine, 2024)

Bilirubin impairs neuritogenesis and synaptogenesis in NSPCs by downregulating NMDAR-CREB-BDNF signaling - Yan Zhang; Siyu Li; Ling Li; Hongmei Huang; Zhou Fu; Ziyu Hua (In Vitro Cellular & Developmental Biology - Animal, 2024)

Atmospheric CO2 controls on the MIS 6 glaciation: 10Be chronology of moraines in the Haizishan area, southeastern Tibetan Plateau - Guocheng Dong; Weijian Zhou; Feng Xian; Yunchong Fu; Li Zhang; Ling Tang; Pengkai Ding (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Detrital zircon geochronology and provenance of Cenozoic deposits in the Qaidam basin, northern Tibetan plateau: An overview with new data, implications and perspectives - Xing Jian; Ping Guan; Ling Fu; Wei Zhang; Xiaotian Shen; Hanjing Fu; Ling Wang (Marine and Petroleum Geology, 2024)

A cytosine analogue 5-azacitidine improves the accumulation of licochalcone A in licorice Glycyrrhiza inflata - Xiaoling Ma; Ningxin Jiang; Jingxian Fu; Yuping Li; Lijun Zhou; Ling Yuan; Ying Wang; Yongqing Li (Journal of Plant Physiology, 2024)

Self-assembled Fe3O4-NH2 @g-C3N4 composite for magnetic solid-phase extraction of benzophenones in sea water and lake water coupled with LC-MS/MS determination - Man-Man Wang; Zi-Ling Li; Han Wu; Ke-Yan Chen; Fan Guo; Gui-Fu Zuo; Yu He; Xue-Bo Yin (Journal of Hazardous Materials, 2024)

Regional feed-in tariff mechanism for photovoltaic power generation in China considering tradable green certificate revenue - Yuting Fu; Changhui Yang; Liangao Zhang; Ling Wang; Kai Jiang (Journal of Cleaner Production, 2024)

Boron promoted Fe3+/peracetic acid process for sulfamethazine degradation: Efficiency, role of boron, and identification of the reactive species - Yanhong Zhang; Guangbing Liu; Yuzhu Xue; Lichun Fu; Yawei Qian; Minhui Hou; Xiang Li; Chen Ling; Ying Zhang; Yuwei Pan (Journal of Environmental Sciences, 2024)

Sulfur isotopic systematics of hydrothermal precipitates in the Okinawa Trough: Implication for the effect of sediments and magmatic volatiles - Hao Wang; Zhenggang Li; Bin Fu; Jie Li; Fengyou Chu; Yanhui Dong; Jihao Zhu; Zhimin Zhu; Ling Chen; Xiaohu Li (Chemical Geology, 2024)

Moraxella haemolytica sp. nov., isolated from a goat with respiratory disease - Fu-Xiang Li; Wen-Hua Zhao; Zhan-Hong Li; Jian-Ling Song; Hua-Feng Gao (Archives of Microbiology, 2024)

Strategies for improving the stability of perovskite for photocatalysis: A review of recent progress - Hanxi Li; Cui Lai; Zhen Wei; Xuerong Zhou; Shiyu Liu; Lei Qin; Huan Yi; Yukui Fu; Ling Li; Mingming Zhang; Fuhang Xu; Huchuan Yan; et al. (Chemosphere, 2023)

How does social learning influence Chinese farmers’ safe pesticide use behavior? An analysis based on a moderated mediation effect - Dakuan Qiao; Lei Luo; Chaoyue Chen; Ling Qiu; Xinhong Fu (Journal of Cleaner Production, 2023)

RETRACTED: Application of Ag nanoparticles decorated on graphene nanosheets for electrochemical sensing of CEA as an important cancer biomarker - Ming Yan; Ling-ling Fu; Hong-chao Feng; Melika Namadchian (Environmental Research, 2023)

Research on cooperative's information services, farmers' cognition, and fertilizer reduction behavior: evidence from China - Xiaoyu Liu; Junlan Xiang; Ling Qiu; Xinhong Fu; Yuying Liu (Environment, Development and Sustainability, 2023)

Human dental pulp stem cells have comparable abilities to umbilical cord mesenchymal stem/stromal cells in regulating inflammation and ameliorating hepatic fibrosis - Peixing Chen; Yanchun Lin; Wenbo Lin; Yun Li; Ting Fu; Yuanyue Liu; Tian Guan; Man Xin; Ling Ye; Peiluan Wang; Haoyu Zeng; Kaitao Yao (Human Cell, 2023)

Observations on the embryonic development of the mud crab, Scylla paramamosain - Li-Kun Xu; Ke-Yi Ma; Feng-Ying Zhang; Wei Wang; Ling-Bo Ma; Zhong-Wen Jin; Ming Zhao; Wei Chen; Yin Fu; Chun-Yan Ma; Zhi-Qiang Liu (Frontiers in Marine Science, 2023)
To investigate the embryonic development of the mud crab Scylla paramamosain , we analyzed three critical parameters: egg color of, embryo morphology (through conventional and laser scanning confocal microscopy), and the distribution of cell divisions. During embryonic development, the egg color exhibited a progressive transition, shifting from orange to reddish-orange, then to brown, before ultimately darkening to black. Each embryo displayed a spherical shape, measuring approximately 280 μm in diameter, characterized by a smooth surface devoid of any depressions. The embryonic cell division was in the form of mixed oogenesis, comprised of complete division in the early stage, spiral oogenesis in the middle stage and surface division in the late stage. It is noteworthy that the blastopore appeared at the position where the transparent area and cell aggregation just appeared under the microscope, and the blastomere was a characteristic of the embryo entering the gastrulation stage. After entering the gastrulation stage, the cells aggregated towards the blastopore and formed two symmetrical cell clusters, which formed a V-shape with the void of the classic blastopore. When the transparent region occupied approximately 1/5 of the embryo ’ s volume, the embryo entered the nauplius stage, and the thoracic and abdominal armor, as well as the optic lobe and abdominal limb primordia, could be clearly distinguished. The appearance of the compound eye pigment band indicated the stage of compound eye pigment formation. At this time, the transparent area accounted for 1/4 of the embryo and a large number of ganglia appeared. The change of the compound eye pigment band from red to black was also one of the reasons for the blackening of the egg color of the crabs. The data obtained through this study have potential applications in the determination of embryonic development status and obtaining of high-quality seeds for S. paramamosain culture.

Effect of the addition of biochar and wood vinegar on the morphology of heavy metals in composts - Fu Xuehan; Guo Xiaojun; Xu Weiguo; Zhou Ling (Environmental Science and Pollution Research, 2023)

Deriving fine-scale patterns of sea surface temperature in coral reef habitats using the Landsat 8 thermal infrared sensor - Xiu-Ling Zuo; Ke-Fu Yu; Bin-Ni Qin; Xiao-Peng Duan; Zuo-Fang Yao; Fen-Zhen Su (Frontiers in Marine Science, 2023)
The available sea surface temperature (SST) products are too coarse to assess the fine-scale (<1 km) SST variations related to coral bleaching. In this study, we proposed an optimal SST inversion model using Landsat 8 thermal infrared sensor (TIRS) images to derive fine-scale SST patterns in the coral reef habitats of the Xisha Islands, South China Sea. Our study included two parts: 1) six SST inversion models were developed using the radiative transfer method and the split window (SW) algorithm in the hot season and cool season, from which the optimal SST inversion model was determined; and 2) the optimal model was applied to 47 Landsat 8 TIRS images to derive the SST spatial and temporal pattern among the geomorphic zones of six reefs in hot and cool season conditions. Compared with the measured sea temperature data and the verified MODIS SST products, the SST6 model using the SW algorithm was optimal, with an RMSE of approximately 0.64°C in the hot season. The average SST results usually had a pattern of reef flat > lagoon > reef slope/offshore sea. The reef flat was usually approximately 0.05°C–0.2°C hotter than the lagoon in the hot season. The SST in the lagoon also increased from south to north and the shallow lagoon was usually warmer than the deep lagoon in the hot season. Our results suggested that scleractinian corals in the reef flat and the lagoon were more susceptible to bleaching-level thermal stress than other geomorphic zones. During the cool season, the SST fluctuated markedly among coral reefs and geomorphic zones.

Effect of common low-molecular-weight organic acid on the photodegradation of sertraline by ferrihydrite - Ziyan Zhou; Dingding Wu; Hao Wu; Boming Fu; Xinhao Wang; Jingyi Ling; Xin Jin; Cheng Gu (Chemosphere, 2023)

The factors controlling antibiotic resistance genes in different treatment processes of mainstream full-scale wastewater treatment plants - Zimu Wang; Li Fu; Ji-Dong Gu; Shihuai Deng; Chengyi Huang; Ling Luo (Science of The Total Environment, 2023)

Logistics density, E-commerce and high-quality economic development: An empirical analysis based on provincial panel data in China - Shaolong Zeng; Qinyi Fu; Fazli Haleem; Yiyang Han; Ling Zhou (Journal of Cleaner Production, 2023)

Aroma enhancement of blueberry wine by postharvest partial dehydration of blueberries - Yu Wang; Qi Zhang; Meng-Yao Cui; Yu Fu; Xiao-Han Wang; Qin Yang; Yue Zhu; Xiao-Hui Yang; Hai-Jun Bi; Xue-Ling Gao (Food Chemistry, 2023)

Association between prenatal exposure to per- and polyfluoroalkyl substances and neurodevelopment in children: Evidence based on birth cohort - Xin-xin Gao; Qian-lin Zuo; Xi-hang Fu; Ling-ling Song; Man-qiu Cen; Jing Wu (Environmental Research, 2023)

Laccase-triggered one-step fabrication of positively charged phenolic acid-amine networks for nanofiltration - Ping Fu; Di Zhou; Wan-Long Li; Wan-Ting Lin; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Desalination, 2023)

Synergistic signal amplification of a 3D Dual-Core DNA nanomachine and PCNs@AuPdCe hybrid nanozymes for ultrasensitive electrochemical detection of Cell-free DNA - Yafei Fu; Jie Li; Dechao Niu; Gangyi Yang; Mengliu Yang; Huawei Shen; Ling Li (Chemical Engineering Journal, 2023)

Optical and electrical dual-mode tactile sensor with interlinked interfaces recording normal force and slip for closed-loop robotics - Kedong Shang; Changliu He; Jian Zhou; Peng Ling; Xulei Lu; Chunqiao Fu; Yong Zhang; Chuan Tang; Linmao Qian; Tingting Yang (Chemical Engineering Journal, 2023)

CD44 targeting nanodrug based on chondroitin sulfate for melanoma therapy by inducing mitochondrial apoptosis pathways - Yan Li; Huiwen Hou; Zengmei Liu; Wen Tang; Jie Wang; Lu Lu; Jiaai Fu; Didi Gao; Feiyan Zhao; XinQing Gao; Peixue Ling; Fengshan Wang; et al. (Carbohydrate Polymers, 2023)

The Critical Role of Equilibrative Nucleoside Transporter-2 in Modulating Cerebral Damage and Vascular Dysfunction in Mice with Brain Ischemia-Reperfusion - Hui-Ling Chiang; Kuo-Chen Wu; You-Yin Chen; Chin-Jui Ho; Han-Lin Wang; Yu-Hua Fu; Wen-Yu Chen; Chun-Jung Lin (Pharmaceutical Research, 2023)

Coupling the digital twin technology and life cycle assessment: Carbon dioxide emissions from polysilicon production - Shengqiang Yang; Zhiqiang Yu; Wenhui Ma; Lin Ma; Chaochun Li; Ling Fu; Ming Li; Zewen Zhao; Yuchen Yang (Sustainable Production and Consumption, 2023)

Insight into the selection of oxidant in persulfate activation system: The effect of the target pollutant properties - Xuerong Zhou; Eydhah Almatrafi; Shiyu Liu; Huchuan Yan; Dengsheng Ma; Shixian Qian; Lei Qin; Huan Yi; Yukui Fu; Ling Li; Mingming Zhang; Fuhang Xu; et al. (Journal of Hazardous Materials, 2023)

The epigenetic regulator Set9 harmonizes fungal development, secondary metabolism, and colonization capacity of Aspergillus flavus - Ling Hao; Mengjuan Zhang; Chi Yang; Xiaohua Pan; Dandan Wu; Hong Lin; Dongmei Ma; Yanfang Yao; Wangzhuo Fu; Jiarui Chang; Yanling Yang; Zhenhong Zhuang (International Journal of Food Microbiology, 2023)

Occurrence and carcinogenic risk assessment of N-nitrosamines in some dried aquatic products in China - Siting Huang; Wusheng Fu; Qinmei Fang; Lei Ni; Renjin Zheng; Ling Yong; Zheng Huang; Jie Pang; Zhong Lin; Honglin Lin; Rongde Dai (Food Control, 2023)

A partially Fe-substituted perovskite electrode for enhancing Zn-CO2 batteries - Hailong Liao; Heping Xie; Shuo Zhai; Ling Fu; Yuan Zhang; Senran Hao; Bin Chen; Chuanxin He; Zongping Shao (Chemical Engineering Journal, 2023)

Experimental study on unloading failure characteristics and damage evolution rules of deep diorite based on triaxial acoustic emission tests - Yang Li; Jianxin Fu; Nai Hao; Weidong Song; Ling Yu (Geosciences Journal, 2023)

Accelerated verification method for the reliability of the motor drive mechanism of the corn precision seed-metering device - Changkai Wen; Jing Zhang; Kan Zheng; Hanqing Li; Lin Ling; Zhijun Meng; Weiqiang Fu; Bingxin Yan (Computers and Electronics in Agriculture, 2023)

Biorthogonal wavelet energy entropy method with different time windows for strong interference processing of GPR signals - Liang Zhang; Sheng Zhang; Tonghua Ling; Fu Huang (Journal of Applied Geophysics, 2023)

Laboratory synthesis, spectroscopic characteristics, and conversion relationships of five calcium sulfate double salts relevant to Mars - Enming Ju; Erbin Shi; Yanqing Xin; Haijun Cao; Changqing Liu; Ping Liu; Jian Chen; Xiaohui Fu; Zongcheng Ling (Icarus, 2023)

Maternal di-(2-ethylhexyl) phthalate exposure elicits offspring IFN-λ upregulation: Insights from birth cohort, murine model, and in vitro mechanistic analysis - Fu-Chen Kuo; Mei-Lan Tsai; Shin-Ting Wu; Sih-Syuan Li; Chia-Fang Wu; Shu-Lin Wang; Michael W.Y. Chan; Jau-Ling Suen; Ming-Tsang Wu; Chih-Hsing Hung (Food and Chemical Toxicology, 2023)

A high-resolution inventory of ammonia emissions from agricultural fertilizer application and crop residue in Taiwan - Chia-Hua Hsu; Fang-Yi Cheng; Chi-Ling Chen; Dong-Hong Wu; Tzu-Ying Chen; Kuo-Fu Liao; Wen-Lung Lay; Yi-Ting Zhang (Atmospheric Environment, 2023)

Large‐scale exploration of nitrogen utilization efficiency in Asia region for rice crop: Variation patterns and determinants - Yuming Sun; Limin Gao; Xusheng Meng; Jian Huang; Junjie Guo; Xuan Zhou; Guohai Fu; Yang Xu; Leslie G. Firbank; Min Wang; Ning Ling; Xumeng Feng; et al. (Global Change Biology, 2023)
Improving rice nitrogen utilization efficiency (NUtE) is imperative to maximizing future food productivity while minimizing environmental threats, yet knowledge of its variation and the underlying regulatory factors is still lacking. Here, we integrated a dataset with 21,571 data compiled by available data from peer‐reviewed literature and a large‐scale field survey to address this knowledge gap. The overall results revealed great variations in rice NUtE, which were mainly associated with human activities, climate conditions, and rice variety. Specifically, N supply rate, temperature, and precipitation were the foremost determinants of rice NUtE, and NUtE responses to climatic change differed among rice varieties. Further prediction highlighted the improved rice NUtE with the increasing latitude or longitude. The indica and hybrid rice exhibited higher NUtE in low latitude regions compared to japonica and inbred rice, respectively. Collectively, our results evaluated the primary drivers of rice NUtE variations and predicted the geographic responses of NUtE in different varieties. Linking the global variations in rice NUtE with environmental factors and geographic adaptability provides valuable agronomic and ecological insights into the regulation of rice NUtE.

Seismicity characteristics of secondary faults in the Zhangjiakou-Bohai tectonic zone - Jin-Meng Bi; Fu-Yang Cao; Ling-Qin Meng (Applied Geophysics, 2023)

Inhibitory Mechanism of EGCG on Advanced Glycation End Products Formation During Low-Temperature Vacuum Heating of Russian Sturgeon - Yue-Wen Chen; Min Zhang; Jing-Jing Fu; Jian-Ling Wei; Wen-Qiang Cai; Xiu-Ping Dong (Journal of Aquatic Food Product Technology, 2023)

Legacy and novel brominated flame retardants in a lab-constructed freshwater ecosystem: Distribution, bioaccumulation, and trophic transfer - Shanqi Zhou; Mengru Fu; Siyuan Ling; Zhihua Qiao; Kailun Luo; Cheng Peng; Wei Zhang; Juying Lei; Bingsheng Zhou (Water Research, 2023)

Tiliroside induces ferroptosis to repress the development of triple-negative breast cancer cells - Chuang Hu; Jian-Fu Zhao; Yi-Ming Wang; Xian-lin Wu; Ling Ye (Tissue and Cell, 2023)

Decoupled local climate and chemical weathering intensity of fine-grained siliciclastic sediments from a paleo-megalake: An example from the Qaidam basin, northern Tibetan Plateau - Ling Wang; Xing Jian; Hanjing Fu; Wei Zhang; Fei Shang; Ling Fu (Sedimentary Geology, 2023)

Genomic analysis of Marinomonas algicola SM1966T reveals its role in marine sulfur cycling - Min Zhang; Xiao-Di Wang; Yue Lin; Shu-Yan Wang; Shan Zhang; Jin Cheng; Mei-Ling Sun; Peng Wang; Hui-Hui Fu; Chun-Yang Li; Nan Zhang (Marine Genomics, 2023)

SWD1 epigenetically chords fungal morphogenesis, aflatoxin biosynthesis, metabolism, and virulence of Aspergillus flavus - Xiaohua Pan; Ling Hao; Chi Yang; Hong Lin; Dandan Wu; Xuan Chen; Mengjuan Zhang; Dongmei Ma; Yu Wang; Wangzhuo Fu; Yanfang Yao; Shihua Wang; et al. (Journal of Hazardous Materials, 2023)

Ultrafine silica aerogels microspheres for adaptive thermal management in large-temperature-fluctuation environment - Ling Liu; Jia Fu; Xueyan Hu; Dengsen Yuan; Jin Wang; Qingwen Li (Chemical Engineering Journal, 2023)

Effect of humic acid-modified attapulgite on polycyclic aromatic hydrocarbon adsorption and release from paddy soil into the overlying water in a rice-crab coculture paddy ecosystem and the underlying process - Nan Sun; Jin Liu; Bo-Wei Qi; Li-Li Lu; Hui-Ling Du; Shuang Li; Chang-Qing Li; Si-Wen Jiang; Zi-Jian Wang; An-Pei Yang; Guang-Lei Zhu; Tian-Yi Wang; et al. (Chemosphere, 2023)

Transcriptional regulatory network of high-value active ingredients in medicinal plants - Han Zheng; Xueqing Fu; Jin Shao; Yueli Tang; Muyao Yu; Ling Li; Luqi Huang; Kexuan Tang (Trends in Plant Science, 2023)

Characterization of microbial contamination of retail washed and unwashed shell eggs in Taiwan - Shu-Chen Hsu; Hsiu-Ling Chen; Chin-Fu Chou; Wen-Chun Liu; Chen-Ting Wu (Food Control, 2023)

Combined effects of light pollution and vegetation height on behavior and body weight in a nocturnal rodent - Ling-Ying Shuai; Li-Qing Wang; Yang Xia; Jin-Yu Xia; Kang Hong; Ya-Nan Wu; Xin-Yi Tian; Fu-Shun Zhang (Environmental Pollution, 2023)

Cytotoxic steroids from the stems of Strophanthus divaricatus - Hong-Ling Ran; Sheng-Zhuo Huang; Hao Wang; Li Yang; Cui-Juan Gai; Rui-Jun Duan; Hao-Fu Dai; Ya-Li Guan; Wen-Li Mei (Phytochemistry, 2023)

Complete genome sequence of Bacillus cereus 2-6A, a marine exopolysaccharide-producing bacterium isolated from deep-sea hydrothermal sediment of the Pacific Ocean - Xuan Zou; Chuan-Lei Suo; Xiao-Mei Geng; Chun-Yang Li; Hui-Hui Fu; Yi Zhang; Peng Wang; Mei-Ling Sun (Marine Genomics, 2023)

Composition, metabolism and postharvest function and regulation of fruit cuticle: A review - Gang-Shuai Liu; Hong-Li Li; Zhen-Zhen Peng; Rui-Ling Liu; Yan-Chao Han; Yun-Xiang Wang; Xiao-Dan Zhao; Da-Qi Fu (Food Chemistry, 2023)

Superior triethylamine sensing platform based on MOF activated by carbon dots for photoelectric dual-mode in biphasic system - Xue-Chun Yang; Sha-Qi Fu; Qian-Li Li; Zheng Jiao; Jing-Tai Zhao; Yun Guo; Zhi-Jun Zhang; Song Gao; Ling-Li Cheng (Chemical Engineering Journal, 2023)

Ndufa4 Regulates the Proliferation and Apoptosis of Neurons via miR-145a-5p/Homer1/Ccnd2 - Fang Fu; Chen Chen; Kun Du; Lu-shan Li; Ru Li; Ting-ying Lei; Qiong Deng; Dan Wang; Qiu-xia Yu; Xin Yang; Jin Han; Min Pan; et al. (Molecular Neurobiology, 2023)
The Dandy–Walker malformation (DWM) is characterized by neuron dysregulation in embryonic development; however, the regulatory mechanisms associated with it are unclear. This study aimed to investigate the role of NADH dehydrogenase 1 alpha subcomplex 4 (NDUFA4) in regulating downstream signaling cascades and neuronal proliferation and apoptosis. Ndufa4 overexpression promoted the proliferation of neurons and inhibited their apoptosis in vitro, which underwent reverse regulation by the Ndufa4 short hairpin RNAs. Ndufa4 -knockout (KO) mice showed abnormal histological alterations in the brain tissue, in addition to impaired spatial learning capacity and exploratory activity. Ndufa4 depletion altered the microRNA expressional profiles of the cerebellum: Ndufa4 inhibited miR-145a-5p expression both in the cerebellum and neurons. miR-145a-5p inhibited the proliferation of neurons and promoted their apoptosis. Ndufa4 promoted and miR-145a-5p inhibited the expression of human homer protein homolog 1 and cyclin D2 in neurons. Thus, Ndufa4 promotes the proliferation of neurons and inhibits their apoptosis by inhibiting miR-145a-5p, which directly targets and inhibits the untranslated regions of Homer1 and Ccnd2 expression.

Sediment sources and their impacts on a check dam-controlled watershed, Loess Plateau, China - Lu-lu Bai; Peng Shi; Wen Wang; Zhan-bin Li; Kun-xia Yu; Peng Li; Ling-zhou Cui; Rong-jian Shen; Mu-hong Guan; Xin-chun Du; Xun-le Zhang; Wen-fu Chen (Journal of Mountain Science, 2023)

Interleukin-1β suppresses rabies virus infection by activating cGAS-STING pathway and compromising the blood-brain barrier integrity in mice - Di Wu; Jinxiao Wang; Chengli Huang; Jianqing Zhao; Zhen F. Fu; Ling Zhao; Ming Zhou (Veterinary Microbiology, 2023)

Response of microbial taxonomic and nitrogen functional attributes to elevated nitrate in suburban groundwater - Ling-Zhi Zhang; Wei He; Fu-Yi Huang; Wei He; Pengpeng Zhou; Cuibai Chen; Christopher Rensing; Kristian Koefoed Brandt; Jiangtao He; Fei Liu; Yi Zhao; Huaming Guo (Science of The Total Environment, 2023)

Experimental and simulation study on hydroxyl group promoting low-temperature oxidation of active groups in coal - Xun Zhang; Bing Lu; Jing Zhang; Xiang Fu; Hanzhong Deng; Ling Qiao; Cong Ding; Fei Gao (Fuel, 2023)

Effects of Torulaspora delbrueckii co-fermented with Saccharomyces cerevisiae on physicochemical and aromatic profiles of blueberry fermented beverage - Yu Wang; Xiao-Yan Qi; Yu Fu; Qi Zhang; Xiao-Han Wang; Meng-Yao Cui; Ying-Ying Ma; Xue-Ling Gao (Food Chemistry, 2023)

Effect of tea polyphenols on sturgeon myofibrillar protein structure in the in vitro anti-glycation model mediated by low temperature vacuum heating - Dan-li Jin; Jian-ling Wei; Fan-yu He; Ting-ting Chai; Shao-tian Ren; Jing-jing Fu; Yue-wen Chen (Food Chemistry, 2023)

Disintegration behavior and mechanism of carbonaceous mudstone under acidic corrosion and wetting-drying cycles - Hong-yuan Fu; Huan-Yi Zha; Ling Zeng; Qian-feng Gao (Bulletin of Engineering Geology and the Environment, 2023)

Multiscale Combined Action and Disturbance Characteristics of Pre-summer Extreme Precipitation Events over South China - Hongbo Liu; Ruojing Yan; Bin Wang; Guanghua Chen; Jian Ling; Shenming Fu (Advances in Atmospheric Sciences, 2023)

Transcriptional regulatory network of high-value active ingredients in medicinal plants - Han Zheng; Xueqing Fu; Jin Shao; Yueli Tang; Muyao Yu; Ling Li; Luqi Huang; Kexuan Tang (Trends in Plant Science, 2023)

Multiple urban resilience evaluation of resource-based cities’ sustainable transformation effect - Zongrun Wang; Haiqin Fu; Ling Zhou (Resources, Conservation and Recycling, 2023)

Timing and seismic origin of the historic Luanshibao rock avalanche in the Maoyaba basin, SE Tibetan Plateau: New evidence from 10Be exposure-ages - Jiangtao Wang; Weijian Zhou; Guocheng Dong; Feng Xian; Yunchong Fu; Li Zhang; Ling Tang; Pengkai Ding; Guoqing Zhao (Quaternary Geochronology, 2023)

AaWIN1, an AP2/ERF protein, positively regulates glandular secretory trichome initiation in Artemisia annua - Chen Wang; Tiantian Chen; Yongpeng Li; Hang Liu; Wei Qin; Zhangkuanyu Wu; Bowen Peng; Xiuyun Wang; Xin Yan; Xueqing Fu; Ling Li; Kexuan Tang (Plant Science, 2023)

Bio-inspired ZnWO4−x exhibiting vacancy-driven UV-to-NIR photodegradation of antibiotics in wastewater - Maurice I. Osotsi; Xin Ling; Siqi Fu; Yuqin Xiong; Wang Zhang; Zhang Di (Journal of Environmental Chemical Engineering, 2023)

Dual polymer electrochromic sunglasses with black to anti-blue-ray conversion based on new anti-blue-ray transparent polymer - Haichang Fu; Yixiao Tang; Feng Zhan; Ling Zhang; Wang Zhan; Yujie Dong; Weijun Li; Cheng Zhang (Chemical Engineering Journal, 2023)

Late diagenetic alteration of carbonate evidenced by carbonate-deficient siliciclastic laminae - Xubin Wang; Lin Dong; Tong Li; Ziyi Wang; Changhu Zhang; Zhijun Jin; Jinhua Fu; Rukai Zhu; Kun Ling; Tianyu Wang (Chemical Geology, 2023)

Cesium exposure and pulmonary function decline: Potential mediating role of oxidative stress in chronic obstructive pulmonary disease patients - Min-Min Tang; Xue-Feng Hou; Jing Sun; Jia-Yi Cheng; You-Peng Deng; Meng-Die Li; Ling Liu; Dong-Xu Hua; Jin Yang; Ya-Lin Jiang; Lin Fu; Hui Zhao (Atmospheric Pollution Research, 2023)

Spinal MCP-1 Contributes to Central Post-stroke Pain by Inducing Central Sensitization in Rats - Fei Yang; Jun-Jie Jing; Si-Yin Fu; Xiu-Zhu Su; Yu-Ling Zhong; Dong-Sheng Chen; Xiao-Zhi Wu; Yi-Qing Zou (Molecular Neurobiology, 2023)

Overbounding residual zenith tropospheric delays to enhance GNSS integrity monitoring - Ling Yang; Yunri Fu; Jincheng Zhu; Yunzhong Shen; Chris Rizos (GPS Solutions, 2023)

GSK2795039 prevents RIP1-RIP3-MLKL-mediated cardiomyocyte necroptosis in doxorubicin-induced heart failure through inhibition of NADPH oxidase-derived oxidative stress - Xiao-Juan Zhang; Lu Li; Ai-Ling Wang; Hong-Xia Guo; Hui-Ping Zhao; Rui-Fang Chi; Hui-Yu Xu; Li-Guo Yang; Bao Li; Fu-Zhong Qin; Jia-Pu Wang (Toxicology and Applied Pharmacology, 2023)

Unveiling the roles of dissolved organic matters derived from different biochar in biochar/persulfate system: Mechanism and toxicity - Xuerong Zhou; Cui Lai; Eydhah Almatrafi; Shiyu Liu; Huchuan Yan; Shixian Qian; Hanxi Li; Lei Qin; Huan Yi; Yukui Fu; Ling Li; Mingming Zhang; et al. (Science of The Total Environment, 2023)

Geochemical characteristics of shales from Upper Carboniferous Yanghugou formation in Weiningbeishan area, China: Implication for provenance, source weathering and tectonic setting - Yu Ma; Hongze Yang; Yanyun Ma; Yongping Wang; Wenzhong Wu; Na An; Shuofeng Tian; Ling Ma; Deliang Fu (Marine and Petroleum Geology, 2023)

N-doped porous bowl-like carbon with superhigh external surface area for ultrafast degradation of bisphenol A: Key role of site exposure degree - Tailu Dong; Chen Ling; Lichun Fu; Yuzhu Xue; Yuwei Pan; Ying Zhang; Changqing Zhu (Journal of Hazardous Materials, 2023)

Accelerated sulfate radical generation from peroxymonosulfate by ZIF-67-derived Co3O4 encapsulated in g-C3N4: A gift from in situ growth - Jinping Liang; Ling Fu; Kai Gao; Ping Zhang; Xiaoguang Duan; Xiaobo Gong; Li Cai (Chemical Engineering Journal, 2023)

Identification and Characterization of Bacillus subtilis B9: A Diazotrophic Plant Growth-Promoting Endophytic Bacterium Isolated from Sugarcane Root - Yi-ning Di; Ling Kui; Pratiksha Singh; Lu-feng Liu; Lin-yan Xie; Li-lian He; Fu-sheng Li (Journal of Plant Growth Regulation, 2023)
Plant endophytic microorganisms, which can enhance plant growth and resistance to biotic and abiotic stresses, are untapped resources with large potential applications for crop production. However, the endophytic community is influenced by multiple factors, such as host genetics, the environment, and other microbes. Thus, it is important to characterize well-adapted endophytes from native crops. We isolated 43 endophytic bacteria from sugarcane cultivar Yunzhe-99-91. All these 43 isolates were examined in vitro for nitrogenase activity and the ability to dissolve phosphorus and produce siderophore. One of these strains, B9, identified as Bacillus subtilis and showed maximum plant growth promotion, was selected for detailed studies. B9 promoted the production of organic acids such as propionic acid, acetic acid, malic acid and citric acid, and the production of phytohormones, including indole-3-acetic acid, cytokinin, 6-benzyladenine, and zeatin. Moreover, B9 significantly promoted the growth of sugarcane plantlets and increased the content of nitrogen, phosphorus, and potassium in the seedlings by 29.26%, 50.78%, and 15.49%, respectively. The photosynthetic rate, root development, and chlorophyll content were also improved with varying degrees compared to the non-inoculated control. The cotyledon and hypocotyl of sugarcane gems germinated faster when co-cultured with the B9 strain compared with control group. Colonization assay showed that B9 was mainly colonized in the roots, followed by the stems and leaves. In conclusion, the positive interaction between endophytic strain B9 and sugarcane may provide long-lasting benefits and a direction for developing and utilizing B9 as a biofertilizer for sugarcane cultivation to decrease fertilizer application.

Recent advances in application of heterogeneous electro-Fenton catalysts for degrading organic contaminants in water - Wenjing Chen; Danlian Huang; Cui Lai; Yukui Fu; Wenfang Chen; Haoyang Ye; Huan Yi; Bisheng Li; Ling Li; Fanzhi Qin; Hong Qin; Lei Qin (Environmental Science and Pollution Research, 2023)

Occurrence, spatial distribution, and risk assessment of brominated flame retardants in farmland soils of typical provinces in China - Mabinty Sarah Tholley; Lartey Young George; Mengru Fu; Zhihua Qiao; Gehui Wang; Siyuan Ling; Cheng Peng; Wei Zhang; Chunmei Ye; Fang Liu; Jie Yang (Chemosphere, 2023)

Ediacaran stratigraphy and paleogeography in the north Yangtze Block, South China - Zhidong Gu; Hua Jiang; Ling Fu; Baoming Zhang; Xiufen Zhai; Guixia Liu; Qiufen Li (Sedimentary Geology, 2023)

A new phragmalin-type limonoid from the roots of Trichilia sinensis - Shou-Bai Liu; Jin-Ling Yang; Hui-Qin Chen; Cheng-min Yang; Hao Wang; Cai-Hong Cai; Jing-Zhe Yuan; Wen-Li Mei; Hao-Fu Dai (Phytochemistry Letters, 2023)

Environmental fate of five brominated flame retardants co-exposure in a water-sediment-zebrafish microcosm system: Enrichment, removal, and metabolism mechanisms - Zhihua Qiao; Yawen Wang; Cong Lu; Siyuan Ling; Shanqi Zhou; Mengru Fu; Kailun Luo; Cheng Peng; Wei Zhang; Bingsheng Zhou (Journal of Cleaner Production, 2023)

Analysis of lunar wrinkle ridges regarding the maximum displacement–length scaling relationship and relevant geological factors - Chenfan Li; Bo Li; Xiaohui Fu; Le Qiao; Zongcheng Ling; Jianguo Yan; Shaojie Qu; Shengbo Chen (Icarus, 2023)

Microwave bag cooking affects the quality, glucosinolates content and hydrolysate production of broccoli florets - Wenxiu Zheng; Wenhao Wang; Desheng Fu; Tianyu Zhang; Zhengrui Liang; Ling Yan; Changhong Liu; Lei Zheng (Food Research International, 2023)

Phospholipase A2 induces acute kidney injury by complement mediated mitochondrial apoptosis via TNF-α/NF-κB signaling pathway - Xin Tang; Tiantian Wei; Mingjing Guan; Peiyun Li; Yajun Pu; Lixin Cheng; Zhifeng Zhou; Ping Fu; Ling Zhang (Food and Chemical Toxicology, 2023)

Insights into reactive species generation and organics selective degradation in Fe-based heterogeneous Fenton-like systems: A critical review - Ling Li; Zhuo Yin; Min Cheng; Lei Qin; Shiyu Liu; Huan Yi; Mingming Zhang; Yukui Fu; Xiaofeng Yang; Xuerong Zhou; Guangming Zeng; Cui Lai (Chemical Engineering Journal, 2023)

Monitoring of tree tilt motion using lorawan-based wireless tree sensing system (IoTT) during super typhoon Mangkhut - Wai Yi Chau; Yu-Hsing Wang; Siu Wai Chiu; Pin Siang Tan; Mei Ling Leung; Hoi Lun Lui; Jimmy Wu; Yun Man Lau; Kuan-Fu Liu; Billy Chi Hang Hau (Agricultural and Forest Meteorology, 2023)

RNA-seq for comparative transcript profiling in leaves of strawberry seedlings under salinity stress - Rui Zhang; Qiuli Du; Wenzhe Zhao; Long Yang; Dongmei Li; Xiude Chen; Wei Xiao; Xiling Fu; Chao Yang; Ling Li (Plant Biotechnology Reports, 2023)

Water microecology is affected by seasons but not sediments: A spatiotemporal dynamics survey of bacterial community composition in Lake Changshou—The largest artificial lake in southwest China - Ai-ling Chen; Fu-qing Xu; Xia Su; Fu-pan Zhang; Wan-chao Tian; Shang-jie Chen; Fang Gou; Zhi-lin Xing; Jin-xin Xiang; Juan Li; Tian-tao Zhao (Marine Pollution Bulletin, 2023)

Light-shading reaction microfluidic PMMA/paper detection system for detection of cyclamate concentration in foods - Chan-Chiung Liu; Chien-Hsuan Ko; Lung-Ming Fu; Yi-Ling Jhou (Food Chemistry, 2023)

Efficient enrichment of iodine by supported ionic liquid with three effective adsorption sites: Heteroatoms, fused aromatic rings and ionic bond - Yu-Qin Xiang; Yuan-Hao Wang; Hao Chen; Jie Fu; Qiu-Hong Zhu; Xiao-Lan Yang; Xin-Hong Xu; Song Qin; Ling He; Guo-Hong Tao (Chemical Engineering Journal, 2023)

Coupled carbon structure and iron species for multiple periodate-based oxidation reaction - Ling Xiang; Eydhah Almatrafi; Hailan Yang; Haoyang Ye; Fanzhi Qin; Huan Yi; Yukui Fu; Xiuqin Huo; Wu Xia; Hong Li; Ming Yan; Chengyun Zhou; et al. (Chemical Engineering Journal, 2023)

An S-scheme CdS/K2Ta2O6 heterojunction photocatalyst for production of H2O2 from water and air - Cui Lai; Mengyi Xu; Fuhang Xu; Bisheng Li; Dengsheng Ma; Yixia Li; Ling Li; Mingming Zhang; Danlian Huang; Lin Tang; Shiyu Liu; Huchuan Yan; et al. (Chemical Engineering Journal, 2023)

Lanthanoid hydrogen-bonded organic frameworks: Enhancement of luminescence by the coordination-promoted antenna effect and applications in heavy-metal ion sensing and sterilization - Yun-Lan Li; Hai-Ling Wang; Zhi-Chuan Chen; Zhong-Hong Zhu; Yan-Cheng Liu; Rui-Yun Yang; Fu-Pei Liang; Hua-Hong Zou (Chemical Engineering Journal, 2023)

Correction to: Modeling landslide susceptibility using data mining techniques of kernel logistic regression, fuzzy unordered rule induction algorithm, SysFor and random forest - Tingyu Zhang; Quan Fu; Chao Li; Fangfang Liu; Huanyuan Wang; Ling Han; Renata Pacheco Quevedo; Tianqing Chen; Na Lei (Natural Hazards, 2023)

Association between pyrethroid exposure and risk of depressive symptoms in the general US adults - Hui-ru Li; Xi-hang Fu; Ling-ling Song; Man-qiu Cen; Jing Wu (Environmental Science and Pollution Research, 2023)

Social isolation does not alter the relationship between flexibility in metabolic rate and growth in grass carp (Ctenopharyngodon idella) under changing food availability - Chun-Yan Sun; Shi-Jian Fu; Ling-Qing Zeng (Journal of Comparative Physiology B, 2023)

Modeling landslide susceptibility using data mining techniques of kernel logistic regression, fuzzy unordered rule induction algorithm, SysFor and random forest - Tingyu Zhang; Quan Fu; Chao Li; Fangfang Liu; Huanyuan Wang; Ling Han; Renata Pacheco Quevedo; Tianqing Chen; Na Lei (Natural Hazards, 2022)

Derivation of new resistance principle on flow-induced morphological response of flexible vegetation - Feng-Cong Jia; Wei-Jie Wang; Ling-Hua Liu; Jin-Jin Li; Ai-Ping Huang; Jing Zhang; Yi-Cheng Fu; Yang Yu (Environmental Science and Pollution Research, 2022)

Infestation and distribution of chigger mites on Confucian white-bellied rat (Niviventer confucianus) in Southwest China - Yan-Ling Chen; Xian-Guo Guo; Wen-Yu Song; Tian-Guang Ren; Lei Zhang; Rong Fan; Cheng-Fu Zhao; Zhi-Wei Zhang; Wen-Ge Dong; Xiao-Bin Huang (Biologia, 2022)

Enhanced Fluoride Stabilization by Modified Layered Double Hydroxides for the Remediation of Soil Pollution: Performance and Mechanism - Dong-ling Wang; Yu-han Fu; Jin-yan Yang (Water, Air, & Soil Pollution, 2022)

Application of regional citrate anticoagulation in patients at high risk of bleeding during intermittent hemodialysis: a prospective multicenter randomized controlled trial - Xiaoyan Tang; Dezheng Chen; Ling Zhang; Ping Fu; Yanxia Chen; Zhou Xiao; Xiangcheng Xiao; Weisheng Peng; Li Cheng; Yanmin Zhang; Hongbo Li; Kehui Li; et al. (Journal of Zhejiang University-SCIENCE B, 2022)

Fine mapping of a stripe rust resistance gene YrZM175 in bread wheat - Jingchun Wu; Dengan Xu; Luping Fu; Ling Wu; Weihao Hao; Jihu Li; Yan Dong; Fengju Wang; Yuying Wu; Zhonghu He; Hongqi Si; Chuanxi Ma; et al. (Theoretical and Applied Genetics, 2022)

Improving pre-harvest sprouting resistance in rice by editing OsABA8ox using CRISPR/Cas9 - Kai Fu; Weihan Song; Cheng Chen; Changling Mou; Yunshuai Huang; Fulin Zhang; Qixian Hao; Ping Wang; Tengfei Ma; Yaping Chen; Ziyan Zhu; Min Zhang; et al. (Plant Cell Reports, 2022)

Use of sodium alginate as a novel cementitious material to improve the engineering properties of disintegrated carbonaceous mudstone - Huanyi Zha; Hongyuan Fu; Ling Zeng; Xiaobo Zhu; Chuankun Jia (Bulletin of Engineering Geology and the Environment, 2022)

Wheat genomic study for genetic improvement of traits in China - Jun Xiao; Bao Liu; Yingyin Yao; Zifeng Guo; Haiyan Jia; Lingrang Kong; Aimin Zhang; Wujun Ma; Zhongfu Ni; Shengbao Xu; Fei Lu; Yuannian Jiao; et al. (Science China Life Sciences, 2022)

Development of an Escherichia coli whole cell biocatalyst for the production of hyperoside - Guo-Si Li; Fu-Cheng Zhu; Pei-Pei Wei; Fang-Li Gu; Qi-Ling Xu; Meng-Hua Ma (Biotechnology Letters, 2022)

Spatiotemporal Variations of Microwave Land Surface Emissivity (MLSE) over China Derived from Four-Year Recalibrated Fengyun 3B MWRI Data - Rui Li; Jiheng Hu; Shengli Wu; Peng Zhang; Husi Letu; Yu Wang; Xuewen Wang; Yuyun Fu; Renjun Zhou; Ling Sun (Advances in Atmospheric Sciences, 2022)

Awareness for Endoscopic Screening Among Accompanying Children of Hospitalized Esophageal Cancer Patients in Henan - Lian Qun Zhang; Xian Juan Du; Fu You Zhou; Pei Nan Chen; Hai Ling Wang; Li Sun; Xiu Ling Li (Journal of Cancer Education, 2022)

Hypoxia-induced oxidative stress and apoptosis in gills of scaleless carp (Gymnocypris przewalskii) - FuJu Chen; Xiaodong Ling; YuTian Zhao; ShengYun Fu (Fish Physiology and Biochemistry, 2022)

Fengyun-4 Geostationary Satellite-Based Solar Energy Nowcasting System and Its Application in North China - Chunlin Huang; Hongrong Shi; Ling Gao; Mengqi Liu; Qixiang Chen; Disong Fu; Shu Wang; Yuan Yuan; Xiang’ao Xia (Advances in Atmospheric Sciences, 2022)

TREM-2 mediates dendritic cell–induced NO to suppress Th17 activation and ameliorate chronic kidney diseases - Ching-Cheng Lin; Ti-Yung Chang; Yong-Chen Lu; Yun-Syuan Wu; Wei Huang; Wei-Chi Lo; Guan-Fu Liu; Wei-Chan Hsu; Pamela S. Ohashi; Tak W. Mak; Jong-Ling Fuh; Hui-Chen Chen; et al. (Journal of Molecular Medicine, 2022)

Rapid triage for ischemic stroke: a machine learning-driven approach in the context of predictive, preventive and personalised medicine - Yulu Zheng; Zheng Guo; Yanbo Zhang; Jianjing Shang; Leilei Yu; Ping Fu; Yizhi Liu; Xingang Li; Hao Wang; Ling Ren; Wei Zhang; Haifeng Hou; et al. (EPMA Journal, 2022)
Background Recognising the early signs of ischemic stroke (IS) in emergency settings has been challenging. Machine learning (ML), a robust tool for predictive, preventive and personalised medicine (PPPM/3PM), presents a possible solution for this issue and produces accurate predictions for real-time data processing. Methods This investigation evaluated 4999 IS patients among a total of 10,476 adults included in the initial dataset, and 1076 IS subjects among 3935 participants in the external validation dataset. Six ML-based models for the prediction of IS were trained on the initial dataset of 10,476 participants (split participants into a training set [80%] and an internal validation set [20%]). Selected clinical laboratory features routinely assessed at admission were used to inform the models. Model performance was mainly evaluated by the area under the receiver operating characteristic (AUC) curve. Additional techniques—permutation feature importance (PFI), local interpretable model-agnostic explanations (LIME), and SHapley Additive exPlanations (SHAP)—were applied for explaining the black-box ML models. Results Fifteen routine haematological and biochemical features were selected to establish ML-based models for the prediction of IS. The XGBoost-based model achieved the highest predictive performance, reaching AUCs of 0.91 (0.90–0.92) and 0.92 (0.91–0.93) in the internal and external datasets respectively. PFI globally revealed that demographic feature age, routine haematological parameters, haemoglobin and neutrophil count, and biochemical analytes total protein and high-density lipoprotein cholesterol were more influential on the model’s prediction. LIME and SHAP showed similar local feature attribution explanations. Conclusion In the context of PPPM/3PM, we used the selected predictors obtained from the results of common blood tests to develop and validate ML-based models for the diagnosis of IS. The XGBoost-based model offers the most accurate prediction. By incorporating the individualised patient profile, this prediction tool is simple and quick to administer. This is promising to support subjective decision making in resource-limited settings or primary care, thereby shortening the time window for the treatment, and improving outcomes after IS.

Astragalus Polysaccharides Reduce High-glucose-induced Rat Aortic Endothelial Cell Senescence and Inflammasome Activation by Modulating the Mitochondrial Na+/Ca2+ Exchanger - Xin-Yu Miao; Xiao-Xiao Zhu; Zhao-Yan Gu; Bo Fu; Shao-Yuan Cui; Yuan Zu; Ling-Jun Rong; Fan Hu; Xiang-Mei Chen; Yan-Ping Gong; Chun-Lin Li (Cell Biochemistry and Biophysics, 2022)

Theoretical model and its experimental verification on nonlinear flow through a rough fracture of silty mudstone under low water head - Hongyuan Fu; Huangbin Jiang; Xiang Qiu; Ling Zeng; Qian-Feng Gao (Bulletin of Engineering Geology and the Environment, 2022)

Deformation characteristics and thresholds of the Tanjiawan landslide in the Three Gorges Reservoir Area, China - Fu-ling Zhang; Mao-lin Deng; Qing-lin Yi; Shu-qiang Lu; Wei-jun Zheng; Hai-feng Huang; Xing Zhu (Journal of Mountain Science, 2022)

Diel variation in anti-predation behavior of a ground squirrel and relationships between vigilance and escape - Ling-Ying Shuai; Mei-Ting Liu; A.-Ping Zhu; Yuan-Yuan Cao; Fu-Shun Zhang (Behavioral Ecology and Sociobiology, 2022)

A novel anticancer property of Lycium barbarum polysaccharide in triggering ferroptosis of breast cancer cells - Xing Du; Jingjing Zhang; Ling Liu; Bo Xu; Hang Han; Wenjie Dai; Xiuying Pei; Xufeng Fu; Shaozhang Hou (Journal of Zhejiang University-SCIENCE B, 2022)

Analysis of factors affecting the reservoir quality of deepwater gravity flow tight sandstone: a case study of the Chang 6 oil reservoir of the Yanchang Formation in the Huaqing area, China - Zhaobing Chen; Ling Fu; Chuangfei Zhou; Jianrong Gao; Xinshe Liu; Xinjing Chen; Yushuang Zhu; Yuhang Chen (Arabian Journal of Geosciences, 2022)

New paraconic acids from the endophytic fungus Xylariaceae sp. J4 - Chao Yuan; Xue-Chun Shu; Lin Fan; Ying-Bo Zhang; Ling-Liang Guan; Fu-Lai Yu; Xiao-Lu Chen; Gang Li (Natural Product Research, 2022)

Bagging-based machine learning algorithms for landslide susceptibility modeling - Tingyu Zhang; Quan Fu; Hao Wang; Fangfang Liu; Huanyuan Wang; Ling Han (Natural Hazards, 2022)

New monoterpenoids from the stigmas of Crocus sativus - Qing-Wei Fang; Wen-Wei Fu; Jin-Ling Yang; Yue Lu; Jiang-Cheng Chen; Pei-Ying Wu; Xue Zhang; Hong-Xi Xu (Journal of Natural Medicines, 2022)

Identification of bacterial blight resistance genes in rice landraces from Yunnan Province, China - Caimei Zhao; Fuyou Yin; Ling Chen; Dingqin Li; Suqin Xiao; Qiaofang Zhong; Bo Wang; Xue Ke; Jian Fu; Xiang Li; Yue Chen; Lingxian Wang; et al. (Australasian Plant Pathology, 2022)
Bacterial blight (BB), a serious bacterial disease caused by pathogen Xanthomonas oryzae pv. oryzae ( Xoo ) affects rice growth and yield. Yunnan Province is regarded as a center of rice diversity in China and indeed the world, and has abundant rice landrace resources, which may offer prospective candidate donors in rice improvement and breeding. In this study, a set of 200 rice landraces were evaluated to determine their resistance to 10 pathogenic Xoo strains resistance by the leaf-clipping method. The results indicated that the tested rice landraces had different resistance levels against different Xoo strains. Multiple comparisons showed that the Xoo strain PXO99 was virulent to the tested rice landraces. Sixty-six rice landraces conferred resistance against at least one Xoo strain. These resistant rice landraces screened were then performed the presence of 14 cloned BB resistance genes by closely linked molecular markers and designed specific primers. The results showed that none of these resistant accessions contained xa13 , Xa21 , Xa27 , and Xa45(t) homologous fragments, while 9, 24, 4, 7, 9, 15, 1, 5, 4 and 27 accessions contained Xa1 , Xa2/Xa31(t) , Xa14 , Xa3/Xa26 , Xa4 , xa5 , Xa7 , Xa10 , Xa23 and xa25 homologous fragments, respectively. Sequence analysis further revealed that nucleotide variations around functional nucleotide polymorphisms region were observed within these accessions containing the Xa1 , Xa2/Xa31(t) , Xa14 , Xa3/Xa26 , Xa4 , xa5 , Xa10 , Xa23 and xa25 homologous fragments. These results along with phenotypic resistance spectrum supported that these accessions carried nine resistance homologous genes. Only one accession (Qishanggu_Wenshan) carried the Xa7 resistance gene. We also found that some resistant rice landraces, especially Xilandigu_Baoshan, and Laoyaling_Lincang without the above resistance genes, which mediated broad spectrum resistance to multiple Xoo strains, were identified as potential sources for breeding rice lines resistance to BB.

Biogeography of culturable marine bacteria from both poles reveals that ‘everything is not everywhere’ at the genomic level - Qi‐Long Qin; Zhi‐Bin Wang; Qian‐Qian Cha; Sha‐Sha Liu; Xue‐Bing Ren; Hui‐Hui Fu; Mei‐Ling Sun; Dian‐Li Zhao; Andrew McMinn; Yin Chen; Xiu‐Lan Chen; Yu‐Zhong Zhang; et al. (Environmental Microbiology, 2022)
Summary Based on 16S rRNA gene analyses, the same bacterial operational taxonomic units (OTUs) are common to both the Arctic and Antarctic oceans, supporting the concept ‘everything is everywhere’. However, whether the same OTUs from both poles have identical genomes, i.e. whether ‘everything is still everywhere’ at the genomic level has not yet been examined systematically. Here, we isolated, sequenced and compared the genomes of 45 culturable marine bacteria belonging to three genera of Salinibacterium , Psychrobacter and Pseudoalteromonas from both polar oceans. The bacterial strains with identical 16S rRNA genes were common to both poles in every genus, and four identical genomes were detected in the genus Salinibacterium from the Arctic region. However, no identical genomes were observed from opposite poles in this study. Our data, therefore, suggest that ‘everything is not everywhere’ at the genomic level. The divergence time between bacteria is hypothesized to exert a strong impact on the bacterial biogeography at the genomic level. The geographical isolation between poles was observed for recently diverged, highly similar genomes, but not for moderately similar genomes. This study thus improves our understanding of the factors affecting the genomic‐level biogeography of marine microorganisms isolated from distant locations.

Effect of nano-CaCO3 on the physical and mechanical properties of analogue to silty mudstone materials - Hong-Yuan Fu; Shuang-Xing Qi; Zhen-Ning Shi; Ling Zeng; Hong-Bin Zhao (Arabian Journal of Geosciences, 2021)

Selection for low-cadmium cultivars and cadmium subcellular distribution comparison between two selected cultivars of eggplant (Solanum melongena L.) - Chuang Shen; Hui-Ling Fu; Qiong Liao; Bai-Fei Huang; Ying-Ying Huang; Jun-Liang Xin (Environmental Science and Pollution Research, 2021)

Differential metabolism-associated gene expression of duck pancreatic cells in response to two strains of duck hepatitis A virus type 1 - Zhen Chen; Shao-hua Shi; Yu Huang; Cui-qin Huang; Rong-chang Liu; Long-fei Cheng; Guang-hua Fu; Hong-mei Chen; Chun-he Wan; Qiu-ling Fu (Archives of Virology, 2021)
Several outbreaks of duck hepatitis A virus type 1 (DHAV-1), which were characterized by yellow coloration and hemorrhage in pancreatic tissues, have occurred in China. The causative agent is called pancreatitis-associated DHAV-1. The mechanisms involved in pancreatitis-associated DHAV-1 infection are still unclear. Transcriptome analysis of duck pancreas infected with classical-type DHAV-1 and pancreatitis-associated DHAV-1 was carried out. Deep sequencing with Illumina-Solexa resulted in a total of 53.9 Gb of clean data from the cDNA library of the pancreas, and a total of 29,597 unigenes with an average length of 993.43 bp were generated by de novo sequence assembly. The expression levels of D-3-phosphoglycerate dehydrogenase, phosphoserine aminotransferase, and phosphoserine phosphatase, which are involved in glycine, serine, and threonine metabolism pathways, were significantly downregulated in ducks infected with pancreatitis-associated DHAV-1 compared with those infected with classical-type DHAV-1. These findings provide information regarding differences in expression levels of metabolism-associated genes between ducks infected with pancreatitis-associated DHAV-1 and those infected with classical-type DHAV-1, indicating that intensive metabolism disorders may contribute to the different phenotypes of DHAV-1-infection.

A Case Study on MJO Energy Transport Path in a Local Multi-scale Interaction Framework - Yuanwen Zhang; Guiwan Chen; Jian Ling; Shenming Fu; Chongyin Li (Advances in Atmospheric Sciences, 2021)

Degraded polysaccharides from Porphyra haitanensis: purification, physico-chemical properties, antioxidant and immunomodulatory activities - Yun-Feng Huo; Yin-Ting Li; Wei Xia; Chong Wang; Yuan-Yuan Xie; Yan-Bo Wang; Tao Zhou; Ling-Lin Fu (Glycoconjugate Journal, 2021)

Molecular identification and characterization of ‘Candidatus Phytoplasma asteris’-related strain associated with pepper (Capsicum annuum L.) yellow crinkle disease in China - Shao-shuai Yu; Qing-hua Tang; Deng-qiang Fu; Rui-ling Zhao; Wei-wei Song; Wei Yan; Wei-quan Qin (Journal of General Plant Pathology, 2021)

Mercury horizontal spatial distribution in paddy field and accumulation of mercury in rice as well as their influencing factors in a typical mining area of Tongren City, Guizhou, China - Jingjing Du; Fang Liu; Ling Zhao; Chong Liu; Zhaocong Fu; Ying Teng (Journal of Environmental Health Science and Engineering, 2021)

The contrasting relationships of relative humidity with influenza A and B in a humid subtropical region - Qian Wu; Jun He; Wen-Yan Zhang; Ke-Fu Zhao; Jing Jin; Jun-Ling Yu; Qing-Qing Chen; Sai Hou; Meng Zhu; Zhiwei Xu; Hai-Feng Pan (Environmental Science and Pollution Research, 2021)

Marinifaba aquimaris gen. nov., sp. nov., a novel chitin‐degrading gammaproteobacterium in the family Alteromonadaceae isolated from seawater of the Mariana Trench - Xin Sui; Xiao-yan He; Ning-hua Liu; Yan-ru Dang; Qian-qian Cha; Mei-ling Sun; Chun-yang Li; Hui-hui Fu; Xiao-yan Song; Qi-long Qin; Xiu-lan Chen; Yu-zhong Zhang; et al. (Antonie van Leeuwenhoek, 2021)

Rhizosphere microbiome modulated effects of biochar on ryegrass 15N uptake and rhizodeposited 13C allocation in soil - Yingyi Fu; Amit Kumar; Lijun Chen; Yuji Jiang; Ning Ling; Runze Wang; Qiong Pan; Bhupinder Pal Singh; Marc Redmile-Gordon; Lu Luan; Qin Li; Quan Shi; et al. (Plant and Soil, 2021)

Tectono-magmatic events of the Qilian orogenic belt in northern Tibet: new insights from detrital zircon geochronology of river sands - Shuo Zhang; Xing Jian; Alex Pullen; Ling Fu; Hanghai Liang; Dongming Hong; Wei Zhang (International Geology Review, 2021)

Importation of taxadiene synthase into chloroplast improves taxadiene production in tobacco - Jinqiu Fu; Wenbo Xu; Wei Huang; Bipeng Wang; Shengchun Li; Jiang Zhang; Ling Chang (Planta, 2021)

B3GNT3 acts as a carcinogenic factor in endometrial cancer via facilitating cell growth, invasion and migration through regulating RhoA/RAC1 pathway-associated markers - Ji-Shui Wang; Fang Ruan; Li-Zhu Guo; Feng-Ge Wang; Fu-Ling Wang; Hong-Min An (Genes & Genomics, 2021)

The impact of biogenic emissions on ozone formation in the Yangtze River Delta region based on MEGANv3.1 - Yangjun Wang; Xingjian Tan; Ling Huang; Qian Wang; Hongli Li; Hongyan Zhang; Kun Zhang; Ziyi Liu; Dramane Traore; Elly Yaluk; Joshua S. Fu; Li Li (Air Quality, Atmosphere & Health, 2021)

Analysis of Local Creep Strain Field and Cracking Process in Claystone by X-Ray Micro-Tomography and Digital Volume Correlation - Hai-Ling Shi; Jerome Hosdez; Thomas Rougelot; Shou-Yi Xie; Jian-Fu Shao; Jean Talandier (Rock Mechanics and Rock Engineering, 2021)

A novel porous silica-zirconia coating for improving bond performance of dental zirconia - Zhiwei Su; Mingxing Li; Ling Zhang; Chaoyang Wang; Leiqing Zhang; Jingqiu Xu; Baiping Fu (Journal of Zhejiang University-SCIENCE B, 2021)

Testosterone deficiency accelerates early stage atherosclerosis in miniature pigs fed a high-fat and high-cholesterol diet: urine 1H NMR metabolomics targeted analysis - Liqun Deng; Danting Fu; Liang Zhu; Junjie Huang; Yun Ling; Zhaowei Cai (Molecular and Cellular Biochemistry, 2021)

The role of MYB proto-oncogene like 2 in tamoxifen resistance in breast cancer - Xia Li; Xi Zhang; Cong-Cong Wu; Ping-Ping Li; Yi-Mou Fu; Li-Hua Xie; Shuang-Shuang Sun; Ying-Ying Zhou; Bao-Ling Zhu (Journal of Molecular Histology, 2021)

Reliability and Validity of a Mobile Device for Assessing Head Control Ability - Mohammad Nikkhoo; Chi-Chien Niu; Chen-Ju Fu; Meng-Ling Lu; Wen-Chien Chen; Yang-Hua Lin; Chih-Hsiu Cheng (Journal of Medical and Biological Engineering, 2021)

Quantitatively determine the dominant driving factors of the spatial—temporal changes of vegetation NPP in the Hengduan Mountain area during 2000–2015 - Shu-ting Chen; Bing Guo; Rui Zhang; Wen-qian Zang; Cui-xia Wei; Hong-wei Wu; Xiao Yang; Xiao-yan Zhen; Xing Li; Da-fu Zhang; Bao-min Han; Hai-ling Zhang (Journal of Mountain Science, 2021)

Correction to: Involvement of proBDNF in Monocytes/Macrophages with Gastrointestinal Disorders in Depressive Mice - Yun-Qing Yu; Yan-Ling Zhang; Zhe Wang; Yu Liu; Hui Li; Chang-Qi Li; Xin-Fu Zhou; Zhao-Lan Hu; Ru-Ping Dai (Neurotoxicity Research, 2020)

Involvement of proBDNF in Monocytes/Macrophages with Gastrointestinal Disorders in Depressive Mice - Yun-Qing Yu; Yan-Ling Zhang; Zhe Wang; Yu Liu; Hui Li; Xin-Fu Zhou; Zhao-Lan Hu; Ru-Ping Dai (Neurotoxicity Research, 2020)

Safety of protease inhibitors and Arbidol for SARS-CoV-2 pneumonia in Zhejiang Province, China - Yong-zheng Guo; Kai-jin Xu; Yong-tao Li; Jia-dan Fu; Min Xu; Ling Yu; Ji-fang Sheng; Biao Zhu (Journal of Zhejiang University-SCIENCE B, 2020)

Stability Analysis of Unsaturated Slopes Considering Combined Influences of Strength Non-homogeneity and Non-saturation - Dan-ping Gu; Tong-hua Ling; Fu Huang; Liang Zhang (Geotechnical and Geological Engineering, 2020)

The effect of baicalin on microRNA expression profiles in porcine aortic vascular endothelial cells infected by Haemophilus parasuis - Shulin Fu; Jun Liu; Jianfeng Xu; Sanling Zuo; Yunfei Zhang; Ling Guo; Yinsheng Qiu; Chun Ye; Yu Liu; Zhongyuan Wu; Yongqing Hou; Chien-An Andy Hu (Molecular and Cellular Biochemistry, 2020)

Responses of Primary Afferent Fibers to Acupuncture-Like Peripheral Stimulation at Different Frequencies: Characterization by Single-Unit Recording in Rats - Ran Huo; Song-Ping Han; Feng-Yu Liu; Xiao-Jing Shou; Ling-Yu Liu; Tian-Jia Song; Fu-Jun Zhai; Rong Zhang; Guo-Gang Xing; Ji-Sheng Han (Neuroscience Bulletin, 2020)

Reversal of Social Recognition Deficit in Adult Mice with MECP2 Duplication via Normalization of MeCP2 in the Medial Prefrontal Cortex - Bin Yu; Bo Yuan; Jian-Kun Dai; Tian-lin Cheng; Sheng-Nan Xia; Ling-Jie He; Yi-Ting Yuan; Yue-Fang Zhang; Hua-Tai Xu; Fu-Qiang Xu; Zhi-Feng Liang; Zi-Long Qiu (Neuroscience Bulletin, 2020)

Genome-Wide Analysis of LAZ1 Gene Family from Maize - Bing Liang Liu; Hao Qiang Yu; Qian Wen; Feng Ling Fu; Wan Chen Li (Journal of Plant Growth Regulation, 2020)

Epidemiology and HBGA-susceptibility investigation of a G9P[8] rotavirus outbreak in a school in Lechang, China - Lun-Ai Guo; Meng Zhang; Yu-zhen Hou; Haitao Hu; Ling Fang; Ming Tan; Qiong Huang; Hui Li; Li-Mei Sun; Xi Jiang; Wen-Fang Tan; Shixing Tang; et al. (Archives of Virology, 2020)

Plastic pollution in croplands threatens long‐term food security - Dan Zhang; Ee Ling Ng; Wanli Hu; Hongyuan Wang; Pablo Galaviz; Hude Yang; Wentao Sun; Chongxiao Li; Xingwang Ma; Bin Fu; Peiyi Zhao; Fulin Zhang; et al. (Global Change Biology, 2020)
Plastic pollution is a global concern given its prevalence in aquatic and terrestrial ecosystems. Studies have been conducted on the distribution and impact of plastic pollution in marine ecosystems, but little is known on terrestrial ecosystems. Plastic mulch has been widely used to increase crop yields worldwide, yet the impact of plastic residues in cropland soils to soil health and crop production in the long term remained unclear. In this paper, using a global meta‐analysis, we found that the use of plastic mulch can indeed increase crop yields on average by 25%–42% in the immediate season due to the increase of soil temperature (+8%) and moisture (+17%). However, the unabated accumulation of film residues in the field negatively impacts its physicochemical properties linked to healthy soil and threatens food production in the long term. It has multiple negative impacts on plant growth including crop yield (at the mean rate of −3% for every additional 100 kg/ha of film residue), plant height (−2%) and root weight (−5%), and soil properties including soil water evaporation capacity (−2%), soil water infiltration rate (−8%), soil organic matter (−0.8%) and soil available phosphorus (−5%) based on meta‐regression. Using a nationwide field survey of China, the largest user of plastic mulch worldwide, we found that plastic residue accumulation in cropland soils has reached 550,800 tonnes, with an estimated 6%–10% reduction in cotton yield in some polluted sites based on current level of plastic residue content. Immediate actions should be taken to ensure the recovery of plastic film mulch and limit further increase in film residue loading to maintain the sustainability of these croplands.

Identification and characterization of two morphologically distinct stem cell subpopulations from human urine samples - An-Jing Chen; Jin-Kui Pi; Jun-Gen Hu; Yi-Zhou Huang; Hong-Wei Gao; Sheng-Fu Li; Jesse Li-Ling; Hui-Qi Xie (Science China Life Sciences, 2020)

Brain-Wide Shape Reconstruction of a Traced Neuron Using the Convex Image Segmentation Method - Shiwei Li; Tingwei Quan; Hang Zhou; Qing Huang; Tao Guan; Yijun Chen; Cheng Xu; Hongtao Kang; Anan Li; Ling Fu; Qingming Luo; Hui Gong; et al. (Neuroinformatics, 2020)

Disease progression model of 4T1 metastatic breast cancer - Liang Yang; Ling Yong; Xiao Zhu; Yaoyao Feng; Yu Fu; Daming Kong; Wei Lu; Tian-yan Zhou (Journal of Pharmacokinetics and Pharmacodynamics, 2020)

Regulation of Circadian Genes by the MAPK Pathway: Implications for Rapid Antidepressant Action - Xin-Ling Wang; Kai Yuan; Wen Zhang; Su-Xia Li; George Fu Gao; Lin Lu (Neuroscience Bulletin, 2020)

Toxicity and metabolism of 3-bromopyruvate in Caenorhabditis elegans - Qiao-ling Gu; Yan Zhang; Xi-mei Fu; Zhao-lian Lu; Yao Yu; Gen Chen; Rong Ma; Wei Kou; Yong-mei Lan (Journal of Zhejiang University-SCIENCE B, 2020)

Identification and Expression Pattern Analysis of Bacterial Blight Resistance Genes in Oryza officinalis Wall ex Watt Under Xanthomonas oryzae Pv. oryzae Stress - Chunmiao Jiang; Suqin Xiao; Dingqin Li; Ling Chen; Qiaofang Zhong; Fuyou Yin; Tengqiong Yu; Xue Ke; Dunyu Zhang; Jian Fu; Yue Chen; Bo Wang; et al. (Plant Molecular Biology Reporter, 2019)
Background Bacterial blight (BB) caused by Xanthomonas oryzae Pv. oryzae ( Xoo ) is one of the most serious diseases of rice worldwide. Oryza officinalis Wall ex Watt, harboring abundant genetic diversity and disease resistance features, are important resources of exploring resistance genes with broad-spectrum resistance to BB. However, the molecular mechanisms and genes of BB resistance in O. officinalis have been rarely explored. Results Here, the BB resistance of four different origin O. officinalis populations in Yunnan were identified by seven representative hypervirulent Xoo races, which exhibited different BB resistance among four populations, in which the BB resistance of the Gengma_Lincang population was the strongest. In addition, the pathogenetic ability of seven Xoo races to O. officinalis was different in that the pathogenicity of PXO99 was stronger than that of C5. There were no remarkable differences in leaf microstructures among four O. officinalis populations, revealing the differences in resistance of four O. officinalis to BB are caused by the endogenous resistance genes. Furthermore, our results proved that there were no nine cloned BB resistance genes in four populations but possessed dominant Xa5 , dominant Xa13 , and recessive xa3/xa26 homologous alleles of xa5 , xa13 , and Xa3 / Xa26 resistance genes. These three homologous genes were isolated and cloned from four populations and named OoXa5 , OoXa13 , and Ooxa3 / xa26 . The expression profile revealed that the expression levels of OoXa13 and Ooxa3/xa26 were significantly down-regulated under PXO99 and C5 stress, especially in the Gengma_Lincang population, suggesting the O. officinalis might enhance BB resistance by down-regulating the expression level of OoXa13 and Ooxa3 / xa26 . Conclusion The BB resistance genes of O. officinalis had its own characteristics by expression pattern and BLAST analysis of OoXa5 , OoXa13 , and Ooxa3 / xa26 , which indicated that there might be new genes or molecular mechanism of BB resistance in O. officinalis. Our studies provided a solid foundation and reference for revealing the molecular mechanism of BB resistance in O. officinalis .

Cholesterol 25-hydroxylase suppresses rabies virus infection by inhibiting viral entry - Yueming Yuan; Zongmei Wang; Bin Tian; Ming Zhou; Zhen F. Fu; Ling Zhao (Archives of Virology, 2019)

Stress associated protein 1 regulates the development of glandular trichomes in Artemisia annua - Yuting Wang; Xueqing Fu; Lihui Xie; Wei Qin; Ling Li; Xiaofen Sun; Shihai Xing; Kexuan Tang (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Two-factor ANOVA of SSH and RNA-seq analysis reveal development-associated Pi-starvation genes in oilseed rape - Zhong-Wei Zhang; Ling-Yang Feng; Jian-Hui Wang; Yu-Fan Fu; Xin Cai; Chang-Quan Wang; Jun-Bo Du; Ming Yuan; Yang-Er Chen; Pei-Zhou Xu; Ting Lan; Guang-Deng Chen; et al. (Planta, 2019)

Identifying Weak Signals in Inhomogeneous Neuronal Images for Large-Scale Tracing of Sparsely Distributed Neurites - Shiwei Li; Tingwei Quan; Hang Zhou; FangFang Yin; Anan Li; Ling Fu; Qingming Luo; Hui Gong; Shaoqun Zeng (Neuroinformatics, 2019)

RNA-Seq-based transcriptomic profiling of primary interstitial cells of Cajal in response to bovine viral diarrhea virus infection - Shengnan Li; Xinyan Hu; Ruixin Tian; Yanting Guo; Junzhen Chen; Zhen Li; Xinyan Zhao; Ling Kuang; Duoliang Ran; Hongqiong Zhao; Xiaohong Zhang; Jinquan Wang; et al. (Veterinary Research Communications, 2019)

Population Genetics of Calotropis gigantea, a Medicinal and Fiber Resource Plant, as Inferred from Microsatellite Marker Variation in two Native Countries - Md. Rabiul Islam; Zhi-Zhong Li; Andrew W. Gichira; Mohammad Nur Alam; Peng-Cheng Fu; Guang-Wan Hu; Qing-Feng Wang; Ling-Yun Chen (Biochemical Genetics, 2019)

Characterization and complete genomic analysis of two Salmonella phages, SenALZ1 and SenASZ3, new members of the genus Cba120virus - Ling Chen; Guoye Guan; Quan Liu; Shengjian Yuan; Tingwei Yan; Linyu Tian; Yan Zhou; Yixuan Zhao; Yingfei Ma; Ting Wei; Xiongfei Fu (Archives of Virology, 2019)

Skinfold thickness for rivastigmine patch application in Alzheimer’s disease - Ping-Song Chou; Kai-Ming Jhang; Ling-Chun Huang; Wen-Fu Wang; Yuan-Han Yang (Psychopharmacology, 2019)

Novel mutations in ZP1, ZP2, and ZP3 cause female infertility due to abnormal zona pellucida formation - Zhou Zhou; Caixia Ni; Ling Wu; Biaobang Chen; Yao Xu; Zhihua Zhang; Jian Mu; Bin Li; Zheng Yan; Jing Fu; Wenjing Wang; Lin Zhao; et al. (Human Genetics, 2019)

Effects of acclimation temperature on the thermal tolerance, hypoxia tolerance and swimming performance of two endangered fish species in China - Long-Yan Zhou; Shi-Jian Fu; Cheng Fu; Hong Ling; Xiu-Ming Li (Journal of Comparative Physiology B, 2019)

A Genome-Wide Association Study of α-Synuclein Levels in Cerebrospinal Fluid - Xiao-ling Zhong; Jie-Qiong Li; Li Sun; Ya-Qing Li; Hui-Fu Wang; Xi-Peng Cao; Chen-Chen Tan; Ling Wang; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2019)

Determination of dietary nitrite in patients with esophageal pre-cancerous lesion and normal people: a duplicate diet study - Ting Zhang; Da Pan; Ming Su; Ling-Meng Fu; Cai-Yun Miao; Qing-Yang Yan; Jing Wang; Li-Gang Yang; Shao-Kang Wang; Gui-Ju Sun (Food Additives & Contaminants: Part A, 2018)

Overexpression of two cold-responsive ATAF-like NAC transcription factors from fine-stem stylo (Stylosanthes guianensis var. intermedia) enhances cold tolerance in tobacco plants - Peng-Lin Zhan; Shan-Wen Ke; Pan-Yu Zhang; Cong-Cong Zhou; Bei-Ling Fu; Xiang-Qian Zhang; Tian-Xiu Zhong; Shu Chen; Xin-Ming Xie (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Phylogeographic analysis of porcine reproductive and respiratory syndrome virus 1 in Guangdong province, Southern China - Shao-Lun Zhai; Tao Lin; Xia Zhou; Zhang-Fu Pei; Zu-Zhang Wei; He Zhang; Xiao-Hui Wen; Qin-Ling Chen; Dian-Hong Lv; Wen-Kang Wei (Archives of Virology, 2018)

Pre-Injection of Small Interfering RNA (siRNA) Promotes c-Jun Gene Silencing and Decreases the Survival Rate of Axotomy-Injured Spinal Motoneurons in Adult Mice - Ying-qin Li; Fa-huan Song; Ke Zhong; Guang-yin Yu; Prince Last Mudenda Zilundu; Ying-ying Zhou; Rao Fu; Ying Tang; Ze-min Ling; Xiaoying Xu; Li-hua Zhou (Journal of Molecular Neuroscience, 2018)

Seismic prediction method of multiscale fractured reservoir - Ling-Ling Wang; Jian-Xin Wei; Ping Huang; Bang-Rang Di; Fu-Hong Zhang (Applied Geophysics, 2018)

Potentiation effects by usnic acid in combination with antibiotics on clinical multi-drug resistant isolates of methicillin-resistant Staphylococcus aureus (MRSA) - Guo-Ying Zuo; Rui-Chun Fu; Wei Yu; Yun-Ling Zhang; Gen-Chun Wang (Medicinal Chemistry Research, 2018)

Self-assembled microspheres feasibility study for conformance control in high temperature and high salinity reservoirs - Jirui Zou; Xiangan Yue; Junbin Zhang; Joseph Y. Fu; Jie He; Bin Kong; Qing Ling (Arabian Journal of Geosciences, 2018)

Cadmium and lead accumulations and agronomic quality of a newly bred pollution-safe cultivar (PSC) of water spinach - Ying-Ying Huang; Yang-Xiu Mu; Chun-Tao He; Hui-Ling Fu; Xue-Song Wang; Fei-Yue Gong; Zhong-Yi Yang (Environmental Science and Pollution Research, 2018)

Interaction network of core ABA signaling components in maize - Ying-Ge Wang; Feng-Ling Fu; Hao-Qiang Yu; Tao Hu; Yuan-Yuan Zhang; Yi Tao; Jian-Kang Zhu; Yang Zhao; Wan-Chen Li (Plant Molecular Biology, 2018)

Anti-complementary constituents of Anchusa italica - Yu-zhen Hou; Kui-kui Chen; Xi-ling Deng; Ze-long Fu; Dao-feng Chen; Qi Wang (Natural Product Research, 2017)

Effects of moso bamboo (Phyllostachys edulis) invasions on soil nitrogen cycles depend on invasion stage and warming - Zhenzhen Li; Ling Zhang; Bangliang Deng; Yuanqiu Liu; Fanqian Kong; Guoxian Huang; Qin Zou; Qian Liu; Xiaomin Guo; Yanqiu Fu; Dekui Niu; Evan Siemann (Environmental Science and Pollution Research, 2017)

Testing of antiviral characteristics of flammutoxin in transgenic tobacco - Li-Ping Wu; Xue-Ling Gao; Yuan-Dan Duan; Ye-Yu Bian; Tao Yang; Ming-Jia Fu (Journal of Plant Diseases and Protection, 2017)

Associations of rs3740677 within GAB2 Gene with LOAD in Chinese Han Population - Jing-Yu Zheng; Hui-Fu Wang; Yu Wan; Meng-Shan Tan; Chen-Chen Tan; Lin Tan; Wei Zhang; Zhan-Jie Zheng; Ling-Li Kong; Zi-Xuan Wang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Dynamic assessment of rainfall-induced shallow landslide hazard - Yang Tang; Kun-long Yin; Lei Liu; Ling Zhang; Xiao-lin Fu (Journal of Mountain Science, 2017)

Plant-soil feedback contributes to intercropping overyielding by reducing the negative effect of take-all on wheat and compensating the growth of faba bean - Guang Zhou Wang; Hai Gang Li; Peter Christie; Fu Suo Zhang; Jun Ling Zhang; James D. Bever (Plant and Soil, 2017)

Acyl-CoA oxidase 1 is involved in γ-decalactone release from peach (Prunus persica) fruit - Liping Zhang; Haiyan Li; Ling Gao; Yujie Qi; Wanyi Fu; Xiongwei Li; Xiang Zhou; Qikang Gao; Zhongshan Gao; Huijuan Jia (Plant Cell Reports, 2017)

Promotion of artemisinin content in Artemisia annua by overexpression of multiple artemisinin biosynthetic pathway genes - Pu Shi; Xueqing Fu; Meng Liu; Qian Shen; Weimin Jiang; Ling Li; Xiaofen Sun; Kexuan Tang (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Association of DISC1 Polymorphisms with Late-Onset Alzheimer’s Disease in Northern Han Chinese - Xiao-Yan Zhang; Hui-Fu Wang; Meng-Shan Tan; Yu Wan; Ling-Li Kong; Zhan-Jie Zheng; Chen-Chen Tan; Wei Zhang; Zi-Xuan Wang; Lin Tan; Teng Jiang; Lan Tan; et al. (Molecular Neurobiology, 2017)

SORL1 Is Associated with the Risk of Late-Onset Alzheimer’s Disease: a Replication Study and Meta-Analyses - Cheng-Cheng Zhang; Hui-Fu Wang; Meng-Shan Tan; Yu Wan; Wei Zhang; Zhan-Jie Zheng; Ling-Li Kong; Zi-Xuan Wang; Lin Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Electromagnetic holographic sensitivity field of two-phase flow in horizontal wells - Kuo Zhang; Xi-Ling Wu; Jing-Fu Yan; Jia-Tie Cai (Applied Geophysics, 2017)

First discovery of a Palaeoproterozoic A-type granite in southern Wuyishan terrane, Cathaysia Block: evidence from geochronology, geochemistry, and Nd–Hf–O isotopes - Zhi-Hong Chen; Ling Zhao; Dan-Dan Chen; Xi-Lin Zhao; Guang-Fu Xing (International Geology Review, 2017)

The anticancer and antiobesity effects of Mediterranean diet - Hiu Yee Kwan; Xiaojuan Chao; Tao Su; Xiuqiong Fu; Anfernee Kai Wing Tse; Wang fun Fong; Zhi-Ling Yu (Critical Reviews in Food Science and Nutrition, 2017)

Di-2-ethylhexyl phthalate induced oxidative damage involving FasL-associated apoptotic pathway in mouse spermatogenic GC-2spd cells - Xiao Tang; Kun Tong; Lishan Zhu; Guoqing Fu; Wei Chang; Ting Zhou; Zhibing Zhang; Ling Tong; Ling Zhang; Yuqin Shi (Molecular & Cellular Toxicology, 2016)

Geochemistry of Altungol cap dolostones from the Tarim Basin, NW China - Fan Feng; Ping Guan; Wenhui Liu; Wei Zhang; Peixian Liu; Xing Jian; Ling Fu (Arabian Journal of Geosciences, 2016)

Subinhibitory concentrations of phloretin repress the virulence of Salmonella typhimurium and protect against Salmonella typhimurium infection - Wu Shuai-Cheng; Fu Ben-Dong; Chu Xiu-Ling; Su Jian-Qing; Fu Yun-Xing; Cui Zhen-Qiang; Xu Dao-Xiu; Wu Zong-Mei (Antonie van Leeuwenhoek, 2016)

Comparison of the immunogenicity of two inactivated recombinant rabies viruses overexpressing the glycoprotein - Muhammad Tariq Navid; Yingying Li; Ming Zhou; Min Cui; Zhen F. Fu; Lijun Tang; Ling Zhao (Archives of Virology, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

Relationship between leaf reddening, ROS and antioxidants in Buxus microphylla during overwintering - Xue-ru Jiang; Jin-gen Peng; Meng-xue Jia; Yan Liu; Ling Guo; Rong-fu Gao (Acta Physiologiae Plantarum, 2016)

The Regulatory Roles of ncRNA Rli60 in Adaptability of Listeria monocytogenes to Environmental Stress and Biofilm Formation - Ye-long Peng; Qing-ling Meng; Jun Qiao; Kun Xie; Cheng Chen; Tian-li Liu; Zheng-xiang Hu; Yu Ma; Xue-peng Cai; Chuang-fu Chen (Current Microbiology, 2016)

A new plant assemblage from the Middle Triassic volcanic tuffs of Pingchuan, Gansu, northwestern China and its paleoenvironmental significance - Fu-Jun Ma; Qiu-Jun Wang; Jun-Ling Dong; Hao-Fei Wang; Zi-Xi Wang; Feng-Tai Zhang; Bai-Nian Sun (PalZ, 2016)

New material of Palaeocarya from the Oligocene of Ningming, Guangxi, South China - Jun-Ling Dong; Wen-Jia Wang; Peng Deng; Jin Wang; Fu-Jun Ma; Qiu-Jun Wang; Yi Yang; Bai-Nian Sun (PalZ, 2016)

Genome-wide identification of WRKY family genes in peach and analysis of WRKY expression during bud dormancy - Min Chen; Qiuping Tan; Mingyue Sun; Dongmei Li; Xiling Fu; Xiude Chen; Wei Xiao; Ling Li; Dongsheng Gao (Molecular Genetics and Genomics, 2016)

Relationship between SST anomalies and the intensity of intraseasonal variability - Fei Liu; Lei Zhou; Jian Ling; Xiouhua Fu; Gang Huang (Theoretical and Applied Climatology, 2016)

Neuroprotection of Sevoflurane Against Ischemia/Reperfusion-Induced Brain Injury Through Inhibiting JNK3/Caspase-3 by Enhancing Akt Signaling Pathway - Xiang-Ru Wen; Yan-Yan Fu; Hong-Zhi Liu; Jian Wu; Xiao-Ping Shao; Xun-Bao Zhang; Man Tang; Yue Shi; Kai Ma; Fang Zhang; Yi-Wen Wang; Hui Tang; et al. (Molecular Neurobiology, 2016)

Effects of induced pluripotent stem cells-derived conditioned medium on the proliferation and anti-apoptosis of human adipose-derived stem cells - Rui-Ling Lian; Xiao-Ling Guo; Jian-Su Chen; Yong-Long Guo; Jia-Fu Zheng; Yuan-Wen Chen (Molecular and Cellular Biochemistry, 2016)

Different Responses of an Invasive Clonal Plant Wedelia trilobata and its Native Congener to Gibberellin: Implications for Biological Invasion - Zhi-Cong Dai; Wei Fu; Shan-Shan Qi; De-Li Zhai; Si-Chong Chen; Ling-Yun Wan; Ping Huang; Dao-Lin Du (Journal of Chemical Ecology, 2016)

Overexpression of a phospholipase Dα gene from Ammopiptanthus nanus enhances salt tolerance of phospholipase Dα1-deficient Arabidopsis mutant - Hao Qiang Yu; Tai Ming Yong; Hong Jie Li; Yan Ping Liu; Shu Feng Zhou; Feng Ling Fu; Wan Chen Li (Planta, 2015)

CTRP3 attenuates post-infarct cardiac fibrosis by targeting Smad3 activation and inhibiting myofibroblast differentiation - Dan Wu; Hong Lei; Jin-Yu Wang; Cheng-Lin Zhang; Han Feng; Feng-Ying Fu; Li Li; Li-Ling Wu (Journal of Molecular Medicine, 2015)

Identification and structural elucidation of steroidal saponins from the root of Paris polyphylla by HPLC-ESI-QTOF-MS/MS - Yun Ling; Zhiwen Fu; Qing Zhang; Lingling Xu; Liang Liao (Natural Product Research, 2015)

miR-26a enhances autophagy to protect against ethanol-induced acute liver injury - Weidong Han; Xianghui Fu; Jiansheng Xie; Zhipeng Meng; Ying Gu; Xichun Wang; Ling Li; Hongming Pan; Wendong Huang (Journal of Molecular Medicine, 2015)

ALFF Value in Right Parahippocampal Gyrus Acts as a Potential Marker Monitoring Amyotrophic Lateral Sclerosis Progression: a Neuropsychological, Voxel-Based Morphometry, and Resting-State Functional MRI Study - Wenjia Zhu; Xiaoling Fu; Fang Cui; Fei Yang; Yuting Ren; Xiaoyun Zhang; Xiaolan Zhang; Zhaohui Chen; Li Ling; Xusheng Huang (Journal of Molecular Neuroscience, 2015)

Enzymatic hydrolysis of 7-xylosyltaxanes by an extracellular xylosidase from Cellulosimicrobium cellulans - Tong-Yi Dou; Hong-Wei Luan; Xing-Bao Liu; Shi-Yang Li; Xun-Fu Du; Ling Yang (Biotechnology Letters, 2015)

Direct cloning, expression of a thermostable xylanase gene from the metagenomic DNA of cow dung compost and enzymatic production of xylooligosaccharides from corncob - Ming-zhe Sun; Hong-chen Zheng; Ling-cai Meng; Jun-she Sun; Hui Song; Yun-juan Bao; Hai-sheng Pei; Zheng Yan; Xiu-qing Zhang; Jing-sheng Zhang; Yi-han Liu; Fu-ping Lu (Biotechnology Letters, 2015)

Assessment of the Altitudinal Atmospheric Metal(loid) Deposition in a Mountainous City by Mosses - Haixia Li; Guoping Zhang; Hong Liu; Ling Li; Zhiping Fu; Xiaoxue Ouyang; Jingjing Chen; Jian Hu (Bulletin of Environmental Contamination and Toxicology, 2015)

Cloning and functional validation of molybdenum cofactor sulfurase gene from Ammopiptanthus nanus - Hao Qiang Yu; Yuan Yuan Zhang; Tai Ming Yong; Yan Ping Liu; Shu Feng Zhou; Feng Ling Fu; Wan Chen Li (Plant Cell Reports, 2015)

Characterization of a novel thermostable patatin-like protein from a Guaymas basin metagenomic library - Ling Fu; Ying He; Fangdi Xu; Qun Ma; Fengping Wang; Jun Xu (Extremophiles, 2015)

Polyphenols in Regulation of Redox Signaling and Inflammation During Cardiovascular Diseases - Ling Niu; Xiu-hua He; Qing-wen Wang; Ming-yu Fu; Feng Xu; Ying Xue; Zhen-zhou Wang; Xin-jiang An (Cell Biochemistry and Biophysics, 2015)

Rifampicin Loaded Mannosylated Cationic Nanostructured Lipid Carriers for Alveolar Macrophage-specific Delivery - Xu Song; Qing Lin; Ling Guo; Yao Fu; Jianfeng Han; Huan Ke; Xun Sun; Tao Gong; Zhirong Zhang (Pharmaceutical Research, 2015)

A new phenylpropanoid from the roots of Euphorbia nematocypha - Hai-Yang Jia; Zhi-Xin Liao; Fu-Yue Liu; Ling Wu; Chen Xu; Bo Zuo (Natural Product Research, 2015)

Association of genetic variation in IKZF1, ARID5B, and CEBPE and surrogates for early-life infections with the risk of acute lymphoblastic leukemia in Hispanic children - Ling-I. Hsu; Anand P. Chokkalingam; Farren B. S. Briggs; Kyle Walsh; Vonda Crouse; Cecilia Fu; Catherine Metayer; Joseph L. Wiemels; Lisa F. Barcellos; Patricia A. Buffler (Cancer Causes & Control, 2015)

CXCL13-CXCR5 axis promotes the growth and invasion of colon cancer cells via PI3K/AKT pathway - Zhenyu Zhu; Xukui Zhang; Hongliang Guo; Ling Fu; Ganlin Pan; Yinggang Sun (Molecular and Cellular Biochemistry, 2015)

Historical development and future perspectives of Environmental Specimen Bank in China: a mini review - Fang Qiu; Xiang-Zhou Meng; Yan-Ling Qiu; Qing-Hui Huang; Ying Liu; Ling-Ling Wu; Qian-Fen Xiao; Ya-Jie Sun; Rui Wang; Yi-Hui Zhou; Zhen-Yang Yu; Da-Qiang Yin; et al. (Environmental Science and Pollution Research, 2015)

Genetic analysis of litchi (Litchi chinensis Sonn.) in southern China by improved random amplified polymorphic DNA (RAPD) and inter-simple sequence repeat (ISSR) - Yan Long; Jingliang Cheng; Zhiqiang Mei; Ling Zhao; Chunli Wei; Shelly Fu; Md. Asaduzzaman Khan; Junjiang Fu (Molecular Biology Reports, 2015)

Genetic tools for the piezophilic hyperthermophilic archaeon Pyrococcus yayanosii - Xuegong Li; Ling Fu; Zhen Li; Xiaopan Ma; Xiang Xiao; Jun Xu (Extremophiles, 2015)

MiR-218-targeting-Bmi-1 mediates the suppressive effect of 1,6,7-trihydroxyxanthone on liver cancer cells - Wei-Ming Fu; Li-Peng Tang; Xiao Zhu; Ying-Fei Lu; Yan-Ling Zhang; Wayne Yuk-Wai LEE; Hua Wang; Yang Yu; Wei-Cheng Liang; Chun-Hay Ko; Hong-Xi Xu; Hsiang-Fu Kung; et al. (Apoptosis, 2015)

Expression Profile of Maize MicroRNAs Corresponding to Their Target Genes Under Drought Stress - Ying-Ge Wang; Ming An; Shu-Feng Zhou; Yue-Hui She; Wan-Chen Li; Feng-Ling Fu (Biochemical Genetics, 2014)

Structure–activity relationships of anthocyanidin glycosylation - Chang Ling Zhao; Zhong Jian Chen; Xue Song Bai; Can Ding; Ting Ju Long; Fu Gang Wei; Kang Ru Miao (Molecular Diversity, 2014)

Comparison of complete genome sequences of dog rabies viruses isolated from China and Mexico reveals key amino acid changes that may be associated with virus replication and virulence - Fulai Yu; Guoqing Zhang; Xiangfu Zhong; Na Han; Yunfeng Song; Ling Zhao; Min Cui; Simon Rayner; Zhen F. Fu (Archives of Virology, 2014)

An Air Quality Management Model Based on an Interval Dual Stochastic-Mixed Integer Programming - Jiliang Zhen; Wei Li; Guohe Huang; Zhenghui Fu; Ling Ji (Water, Air, & Soil Pollution, 2014)

Effect of dietary lysine on growth, intestinal enzymes activities and antioxidant status of sub-adult grass carp (Ctenopharyngodon idella) - Xue-Yin Li; Ling Tang; Kai Hu; Yang Liu; Wei-Dan Jiang; Jun Jiang; Pei Wu; Gang-Fu Chen; Shu-Hong Li; Sheng-Yao Kuang; Lin Feng; Xiao-Qiu Zhou (Fish Physiology and Biochemistry, 2014)

MicroRNA-30c serves as an independent biochemical recurrence predictor and potential tumor suppressor for prostate cancer - Xiao-hui Ling; Zhao-dong Han; Dan Xia; Hui-chan He; Fu-neng Jiang; Zhuo-yuan Lin; Xin Fu; Ye-han Deng; Qi-shan Dai; Chao Cai; Jia-hong Chen; Yu-xiang Liang; et al. (Molecular Biology Reports, 2014)

Characterization of the Promoter of Artemisia annua Amorpha-4,11-diene Synthase (ADS) Gene Using Homologous and Heterologous Expression as well as Deletion Analysis - Mengmeng Zhu; Fangyuan Zhang; Zongyou Lv; Qian Shen; Ling Zhang; Xu Lu; Weimin Jiang; Xueqing Fu; Tingxiang Yan; Lingxian Chen; Guofeng Wang; Kexuan Tang (Plant Molecular Biology Reporter, 2014)

Physiological and morphological responses to the first bout of refeeding in southern catfish (Silurus meridionalis) - Ling-Qing Zeng; Shi-Jian Fu; Xiu-Ming Li; Feng-Jie Li; Bin Li; Zhen-Dong Cao; Yao-Guang Zhang (Journal of Comparative Physiology B, 2014)

Next generation sequencing-based molecular diagnosis of retinitis pigmentosa: identification of a novel genotype-phenotype correlation and clinical refinements - Feng Wang; Hui Wang; Han-Fang Tuan; Duy H. Nguyen; Vincent Sun; Vafa Keser; Sara J. Bowne; Lori S. Sullivan; Hongrong Luo; Ling Zhao; Xia Wang; Jacques E. Zaneveld; et al. (Human Genetics, 2014)

Purification and characterization of a thermostable aliphatic amidase from the hyperthermophilic archaeon Pyrococcus yayanosii CH1 - Ling Fu; Xuegong Li; Xiang Xiao; Jun Xu (Extremophiles, 2014)

A Novel Co-immunoprecipitation Protocol Based on Protoplast Transient Gene Expression for Studying Protein–protein Interactions in Rice - Jia Wei Yang; Jia Xin Fu; Jing Li; Xiao Ling Cheng; Feng Li; Jing Fang Dong; Zhen Lan Liu; Chu Xiong Zhuang (Plant Molecular Biology Reporter, 2014)

Molecular Cloning and Characterization of a Trichome-Specific Promoter of Artemisinic Aldehyde Δ11(13) Reductase (DBR2) in Artemisia annua - Weimin Jiang; Xu Lu; Bo Qiu; Fangyuan Zhang; Qian Shen; Zongyou Lv; Xueqing Fu; Tingxiang Yan; Erdi Gao; Mengmeng Zhu; Lingxian Chen; Ling Zhang; et al. (Plant Molecular Biology Reporter, 2014)

Microbial Source Tracking: A Tool for Identifying Sources of Microbial Contamination in the Food Chain - Ling-Lin Fu; Jian-Rong Li (Critical Reviews in Food Science and Nutrition, 2014)

The TNF-alpha -308G/A polymorphism is associated with type 2 diabetes mellitus: an updated meta-analysis - Yuliang Zhao; Zheng Li; Ling Zhang; Yonggang Zhang; Yingying Yang; Yi Tang; Ping Fu (Molecular Biology Reports, 2014)

Charlson comorbidity index helps predict the risk of mortality for patients with type 2 diabetic nephropathy - You-Qun Huang; Rong Gou; Yong-Shu Diao; Qing-Hua Yin; Wen-Xing Fan; Ya-Ping Liang; Yi Chen; Min Wu; Li Zang; Ling Li; Jing Zang; Lu Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Role of Angptl4 in vascular permeability and inflammation - Liang Guo; Shao-Ying Li; Fu-Yun Ji; Yun-Feng Zhao; Yu Zhong; Xue-Jun Lv; Xue-Ling Wu; Gui-Sheng Qian (Inflammation Research, 2014)

Organochlorine pesticides in the dust fall around Lake Chaohu, the fifth largest lake in China - Hui-Ling Ouyang; Qing-Mei Wang; Wei He; Ning Qin; Xiang-Zhen Kong; Wen-Xiu Liu; Qi-Shuang He; Yu-Jiao Jiang; Chen Yang; Bin Yang; Fu-Liu Xu (Environmental Monitoring and Assessment, 2014)

Influence of Electromagnetic Signal of Antibiotics Excited by Low-Frequency Pulsed Electromagnetic Fields on Growth of Escherichia coli - Yin-Lung Ke; Fu-Yu Chang; Ming-Kun Chen; Shun-Lai Li; Ling-Sheng Jang (Cell Biochemistry and Biophysics, 2013)

Molecular characterization of novel haplotypes of eIF4E family in Chinese cabbage (Brassica rapa L. ssp. pekinensis) - Shuan-Tao Liu; Zhi-Gang Zhang; Qiao-Yun Li; Shu-Fen Wang; Zhi-Zhong Zhao; Jin-Dong Lu; Wen-Ling Xu; Xian-Xian Liu; Wei-Min Fu (Genes & Genomics, 2013)

New 18-oxygenated polyhydroxy steroid from a South China Sea soft coral Sarcophyton sp. - Ling-Ling Sun; Xiu-Mei Fu; Xiu-Bao Li; Qian Xing; Chang-Yun Wang (Natural Product Research, 2013)

Improvement of enamel bond strengths for conventional and resin-modified glass ionomers: acid-etching vs. conditioning - Ling Zhang; Tian Tang; Zhen-liang Zhang; Bing Liang; Xiao-miao Wang; Bai-ping Fu (Journal of Zhejiang University-SCIENCE B, 2013)

Influence of HbA1c on short-term blood pressure variability in type 2 diabetic patients with diabetic nephropathy - Fang Liu; Min Wu; Yan-huan Feng; Hui Zhong; Tian-lei Cui; You-qun Huang; Ya-ping Liang; Yong-shu Diao; Li Zang; Ling Li; Jing Zang; Hong-yu Qiu; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

FFAs and adipokine-mediated regulation of hsa-miR-143 expression in human adipocytes - Lingling Zhu; Chunmei Shi; Chenbo Ji; Guangfeng Xu; Ling Chen; Lei Yang; Ziyi Fu; Xianwei Cui; Yibing Lu; Xirong Guo (Molecular Biology Reports, 2013)

The residual levels and health risks of hexachlorocyclohexanes (HCHs) and dichloro-diphenyl-trichloroethanes (DDTs) in the fish from Lake Baiyangdian, North China - Wen-Jing Wu; Ning Qin; Ying Zhu; Qi-Shuang He; Hui-Ling Ouyang; Wei He; Wen-Xiu Liu; Fu-Liu Xu (Environmental Science and Pollution Research, 2013)

Effects of nitric oxide on the germination of cucumber seeds and antioxidant enzymes under salinity stress - Huai-Fu Fan; Chang-Xia Du; Ling Ding; Yan-Li Xu (Acta Physiologiae Plantarum, 2013)

Overexpression of TFAM Protects 3T3-L1 Adipocytes from NYGGF4 (PID1) Overexpression-Induced Insulin Resistance and Mitochondrial Dysfunction - Chun-Mei Shi; Guang-Feng Xu; Lei Yang; Zi-Yi Fu; Ling Chen; Hai-Long Fu; Ya-Hui Shen; Lu Zhu; Chen-Bo Ji; Xi-Rong Guo (Cell Biochemistry and Biophysics, 2013)

RNA interference-mediated resistance to maize dwarf mosaic virus - Zhi-Yong Zhang; Ying-Ge Wang; Xiao-Juan Shen; Lei Li; Shu-Feng Zhou; Wan-Chen Li; Feng-Ling Fu (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Analysis of genetic diversity of Ruthenia Medic (Medicago ruthenica (L.) Trautv.) in Inner Mongolia using ISSR and SSR markers - Hong-yan Li; Zhi-yong Li; Li-yan Cai; Wen-gui Shi; Fu-gui Mi; Feng-ling Shi (Genetic Resources and Crop Evolution, 2013)

Down-regulation of the ErbB3 binding protein 1 in human bladder cancer promotes tumor progression and cell proliferation - Hui-chan He; Xiao-hui Ling; Jian-guo Zhu; Xin Fu; Zhao-dong Han; Yu-xian Liang; Ye-han Deng; Zhuo-yuan Lin; Guo Chen; Yan-fei Chen; Ru-jun Mo; Wei-de Zhong (Molecular Biology Reports, 2013)

Modulation of hsa-miR-26b levels following adipokine stimulation - Guangfeng Xu; Chenbo Ji; Chunmei Shi; Hailong Fu; Lingling Zhu; Lu Zhu; Lulian Xu; Ling Chen; Yueying Feng; Yaping Zhao; Xirong Guo (Molecular Biology Reports, 2013)

Intergeneric hybrid between Chrysanthemum × morifolium and Artemisia japonica achieved via embryo rescue shows salt tolerance - Wen-ying Zhu; Jia-fu Jiang; Su-mei Chen; Liang Wang; Li-li Xu; Hai-bin Wang; Pei-ling Li; Zhi-yong Guan; Fa-di Chen (Euphytica, 2013)

The Influence of Cu(II) on the Formation and Distribution of Disinfection By-Products during the Chlorination of Drinking Water - Shao-gang Liu; Zhi-liang Zhu; Xue-cai Tan; Xin-hui Feng; Zai-yin Huang; Yan-ling Qiu; Jian-fu Zhao (Water, Air, & Soil Pollution, 2013)

Screening Chinese soybean genotypes for Agrobacterium-mediated genetic transformation suitability - Zhang-yue Song; Jing-luan Tian; Wei-zhe Fu; Lin Li; Ling-hong Lu; Lian Zhou; Zhi-hui Shan; Gui-xiang Tang; Hui-xia Shou (Journal of Zhejiang University-SCIENCE B, 2013)

The residues, distribution, and partition of organochlorine pesticides in the water, suspended solids, and sediments from a large Chinese lake (Lake Chaohu) during the high water level period - Wen-Xiu Liu; Wei He; Ning Qin; Xiang-Zhen Kong; Qi-Shuang He; Hui-Ling Ouyang; Fu-Liu Xu (Environmental Science and Pollution Research, 2013)

Water–gas exchange of organochlorine pesticides at Lake Chaohu, a large Chinese lake - Hui-Ling Ouyang; Wei He; Ning Qin; Xiang-Zhen Kong; Wen-Xiu Liu; Qi-Shuang He; Chen Yang; Yu-Jiao Jiang; Qing-Mei Wang; Bin Yang; Fu-Liu Xu (Environmental Science and Pollution Research, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Temporal and Spatial Variation in Regional Climate and its Impact on Runoff in Xinjiang, China - Hongbo Ling; Hailiang Xu; Jinyi Fu (Water Resources Management, 2013)

Association between mandibular posterior alveolar morphology and growth pattern in a Chinese population with normal occlusion - Min Han; Rong-yang Wang; Hong Liu; Xiu-juan Zhu; Fu-lan Wei; Tao Lv; Na-na Wang; Li-hua Hu; Guo-ju Li; Dong-xu Liu; Chun-ling Wang (Journal of Zhejiang University-SCIENCE B, 2013)

Grain and shoot zinc accumulation in winter wheat affected by nitrogen management - Yan-Fang Xue; Shan-Chao Yue; Yue-Qiang Zhang; Zhen-Ling Cui; Xin-Ping Chen; Fu-Chun Yang; Ismail Cakmak; Steve P. McGrath; Fu-Suo Zhang; Chun-Qin Zou (Plant and Soil, 2012)

The reduction in zinc concentration of wheat grain upon increased phosphorus-fertilization and its mitigation by foliar zinc application - Yue-Qiang Zhang; Yan Deng; Ri-Yuan Chen; Zhen-Ling Cui; Xin-Ping Chen; Russell Yost; Fu-Suo Zhang; Chun-Qin Zou (Plant and Soil, 2012)

Differential responses of peripheral circadian clocks to a short-term feeding stimulus - Tao Wu; Ou Fu; Ling Yao; Lu Sun; Fen ZhuGe; Zhengwei Fu (Molecular Biology Reports, 2012)

Effect of feeding on the function and structure of the digestive system in juvenile southern catfish (Silurus meridionalis Chen) - Ling-Qing Zeng; Feng-Jie Li; Shi-Jian Fu; Zhen-Dong Cao; Yao-Guang Zhang (Fish Physiology and Biochemistry, 2012)

Carboxylate-Terminated Double-Hydrophilic Block Copolymer as an Effective and Environmentally Friendly Inhibitor for Carbonate and Sulfate Scales in Cooling Water Systems - Guangqing Liu; Yuming Zhou; Jingyi Huang; Qingzhao Yao; Lei Ling; Peixin Zhang; Xiaofeng Zhong; Change Fu; Wendao Wu; Wei Sun; Zhengjun Hu (Water, Air, & Soil Pollution, 2012)

Spatial variation of bacterial community structure of the Northern South China Sea in relation to water chemistry - Juan Ling; Jun-De Dong; You-Shao Wang; Yan-Ying Zhang; Chao Deng; Li Lin; Mei-Lin Wu; Fu-Lin Sun (Ecotoxicology, 2012)

Gastrin inhibits a novel, pathological colon cancer signaling pathway involving EGR1, AE2, and P-ERK - Ling-Jun Song; Rui-Jun Liu; Zhi Zeng; Seth L. Alper; Heng-Jing Cui; Yang Lu; Lin Zheng; Zhao-Wen Yan; Guo-Hui Fu (Journal of Molecular Medicine, 2012)

Computational prediction and experimental assessment of an HLA-A*0201-restricted cytotoxic T lymphocyte epitope from neutral endopeptidase - Jingbo Zhang; Zhengcai Jia; Zhihua Lin; Jingyi Li; Xiaolan Fu; Yunjian Huang; Jinghong Zhao; Ling Nie; Weiping Hou; Fahuan Yuan; Yuzhang Wu (Immunologic Research, 2012)

Mapping of BnMs4 and BnRf to a common microsyntenic region of Arabidopsis thaliana chromosome 3 using intron polymorphism markers - Shengqian Xia; Ling Cheng; Feng Zu; Xiaoling Dun; Zhengfu Zhou; Bin Yi; Jing Wen; Chaozhi Ma; Jinxiong Shen; Jinxing Tu; Tingdong Fu (Theoretical and Applied Genetics, 2012)

Spontaneous retroperitoneal hemorrhage after hemodialysis involving anticoagulant agents - Wen-xing Fan; Zheng-xu Deng; Fang Liu; Rong-bo Liu; Ling He; Bogati Amrit; Li Zang; Jing-wen Li; Xian-rong Liu; Song-min Huang; Ping Fu (Journal of Zhejiang University-SCIENCE B, 2012)

Spermidine affects the transcriptome responses to high temperature stress in ripening tomato fruit - Lin Cheng; Rong-rong Sun; Fei-yan Wang; Zhen Peng; Fu-ling Kong; Jian Wu; Jia-shu Cao; Gang Lu (Journal of Zhejiang University-SCIENCE B, 2012)

The monitoring results of electromagnetic radiation of 110-kV high-voltage lines in one urban location in Chongqing P.R. China - Qi-zhong Qin; Yu Chen; Ting-ting Fu; Li Ding; Ling-li Han; Jian-chao Li (Environmental Monitoring and Assessment, 2012)

CDH1 promoter polymorphism and stomach cancer susceptibility - Yi-Ling Li; Zhong Tian; Jian-Bing Zhang; Bao-Yu Fu (Molecular Biology Reports, 2012)

Association between ATM 5557G>A polymorphism and breast cancer risk: a meta-analysis - Chen Mao; Vincent C. H. Chung; Ben-Fu He; Rong-Cheng Luo; Jin-Ling Tang (Molecular Biology Reports, 2012)

Systematic assessment and meta-analysis of the efficacy and safety of fasudil in the treatment of cerebral vasospasm in patients with subarachnoid hemorrhage - Guang Jian Liu; Zheng Jun Wang; Yun Fu Wang; Li Li Xu; Xiao Ling Wang; Yong Liu; Guo Jun Luo; Guo Hou He; Yan Jun Zeng (European Journal of Clinical Pharmacology, 2012)

Effect of dirhamnolipid on the removal of phenol catalyzed by laccase in aqueous solution - Zhi-Feng Liu; Guang-Ming Zeng; Hua Zhong; Xing-Zhong Yuan; Hai-Yan Fu; Mei-Fang Zhou; Xiao-Ling Ma; Hui Li; Jian-Bing Li (World Journal of Microbiology and Biotechnology, 2012)

Overexpression of a vacuolar H+-pyrophosphatase and a B subunit of H+-ATPase cloned from the halophyte Halostachys caspica improves salt tolerance in Arabidopsis thaliana - You-zhen Hu; You-ling Zeng; Bo Guan; Fu-chun Zhang (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

Comparative full-length sequence analysis of Marek’s disease virus vaccine strain 814 - Feng Zhang; Chang-Jun Liu; Yan-Ping Zhang; Zhi-Jie Li; Ai-Ling Liu; Fu-Hai Yan; Feng Cong; Yun Cheng (Archives of Virology, 2012)

Three-dimensional evaluation of upper anterior alveolar bone dehiscence after incisor retraction and intrusion in adult patients with bimaxillary protrusion malocclusion - Qing-yuan Guo; Shi-jie Zhang; Hong Liu; Chun-ling Wang; Fu-lan Wei; Tao Lv; Na-na Wang; Dong-xu Liu (Journal of Zhejiang University-SCIENCE B, 2011)

17beta-estradiol attenuates pressure overload-induced myocardial hypertrophy through regulating caveolin-3 protein in ovariectomized female rats - Yu-Hong Cui; Zhi Tan; Xiao-Dong Fu; Qiu-Ling Xiang; Jin-Wen Xu; Ting-Huai Wang (Molecular Biology Reports, 2011)

Inhibitory Effect of Delphinidin on Monocyte–Endothelial Cell Adhesion Induced by Oxidized Low-Density Lipoprotein via ROS/p38MAPK/NF-κB Pathway - Chun-ye Chen; Long Yi; Xin Jin; Ting Zhang; Yu-jie Fu; Jun-dong Zhu; Man-tian Mi; Qian-yong Zhang; Wen-hua Ling; Bin Yu (Cell Biochemistry and Biophysics, 2011)

Chemical composition and antioxidant activity of the essential oil of endemic Viola tianshanica - Jin Yang; Zhen Qu; Yu-Ling Xiao; Guo-Fu Qiu; Tao Zhang; Zhong-Yuan Wu; Xian-Ran He; Xian-Ming Hu (Natural Product Research, 2011)

Overexpression of survivin and cyclin D1 in CHO cells confers apoptosis resistance and enhances growth in serum-free suspension culture - Xinghui Zhao; Junwei Guo; Yingqun Yu; Shaoqiong Yi; Ting Yu; Ling Fu; Lihua Hou; Wei Chen (Biotechnology Letters, 2011)

A novel direct equipartition ray design (EquRay) procedure for toxicity interaction between ionic liquid and dichlorvos - Rong-Ni Dou; Shu-Shen Liu; Ling-Yun Mo; Hai-Ling Liu; Fu-Cai Deng (Environmental Science and Pollution Research, 2011)

Differentiation of Fecal Escherichia coli from Human, Livestock, and Poultry Sources by rep-PCR DNA Fingerprinting on the Shellfish Culture Area of East China Sea - Hong-Jia Ma; Ling-Lin Fu; Jian-Rong Li (Current Microbiology, 2011)

Characterization of Exserohilum rostratum, a new causal agent of banana leaf spot disease in China - Shan-Hai Lin; Si-Liang Huang; Qi-Qin Li; Chun-Jin Hu; Gang Fu; Li-Ping Qin; Yue-Feng Ma; Ling Xie; Zhen-Lu Cen; Wei-Hong Yan (Australasian Plant Pathology, 2011)

Isolation and characterization of polymorphic microsatellite markers for the ariake icefish (Salanx ariakensis kishinouye) - Juan Hu; Sheng-Jie Ren; Cui-Zhang Fu; Xiao-Ling Gong (Conservation Genetics Resources, 2011)

Identification of QTLs for maize seed vigor at three stages of seed maturity using a RIL population - Liu Jing-bao; Fu Zhi-yuan; Xie Hui-ling; Hu Yan-min; Liu Zong-hua; Duan Liu-jing; Xu Shang-zhong; Tang Ji-hua (Euphytica, 2011)

A haplotype in the CCR5 gene promoter was associated with the susceptibility to HIV-1 infection in a northern Chinese population - Lidan Xu; Yuandong Qiao; Xuelong Zhang; Haiming Sun; Jingwei Wang; Donglin Sun; Xueyuan Jia; Chao Shen; Yanling Zhao; Yan Jin; Yang Yu; Hong Ling; et al. (Molecular Biology Reports, 2011)

Effect of temperature on excess post-exercise oxygen consumption in juvenile southern catfish (Silurus meridionalis Chen) following exhaustive exercise - Ling-Qing Zeng; Yao-Guang Zhang; Zhen-Dong Cao; Shi-Jian Fu (Fish Physiology and Biochemistry, 2010)

The Removal of Ocular Artifacts from EEG Signals Using Adaptive Filters Based on Ocular Source Components - Hsiao-Lung Chan; Yu-Tai Tsai; Ling-Fu Meng; Tony Wu (Annals of Biomedical Engineering, 2010)

Spatio-Temporal Variability of Soil Respiration of Forest Ecosystems in China: Influencing Factors and Evaluation Model - Ze-Mei Zheng; Gui-Rui Yu; Xiao-Min Sun; Sheng-Gong Li; Yue-Si Wang; Ying-Hong Wang; Yu-Ling Fu; Qiu-Feng Wang (Environmental Management, 2010)

RNA Interference-Based Transgenic Maize Resistant to Maize Dwarf Mosaic Virus - Zhi-Yong Zhang; Feng-Ling Fu; Lin Gou; Han-Guang Wang; Wan-Chen Li (Journal of Plant Biology, 2010)

Design and implementation of an adaptive code discriminator in a DSP/FPGA-based Galileo receiver - Jyh-Ching Juang; Yu-Hsuan Chen; Tsai-Ling Kao; Yung-Fu Tsai (GPS Solutions, 2010)

Multiple shoots induction in wild cotton (Gossypium bickii) through organogenesis and the analysis of genetic homogeneity of the regenerated plants - Xi-Yan Yang; Xian-Long Zhang; Li-Li Fu; Ling Min; Guan-ze Liu (Biologia, 2010)

Cationic liposome coupled endostatin gene for treatment of peritoneal colon cancer - Keng-Li Lan; Fu Ou-Yang; Sang-Hue Yen; How-Ling Shih; Keng-Hsin Lan (Clinical & Experimental Metastasis, 2010)

Free radical scavenging activity and antiproliferative potential of Polygonum cuspidatum root extracts - Yun-Wei Lin; Fu-Jung Yang; Chia-Ling Chen; Wei-Ting Lee; Ruey-Shyang Chen (Journal of Natural Medicines, 2010)

Cloning and Characterization of Functional Trehalose-6-Phosphate Synthase Gene in Maize - Wei Jiang; Feng-Ling Fu; Su-Zhi Zhang; Ling Wu; Wan-Chen Li (Journal of Plant Biology, 2010)

Molecular cloning and characterization of hatching enzyme-like gene in the silkworm, Bombyx mori - Fu-hao Lu; Shun-ming Tang; Xing-jia Shen; Na Wang; Qiao-ling Zhao; Guo-zheng Zhang; Xi-jie Guo (Molecular Biology Reports, 2010)

Effects of moniliformin and selenium on human articular cartilage metabolism and their potential relationships to the pathogenesis of Kashin-Beck disease - An Zhang; Jun-ling Cao; Bo Yang; Jing-hong Chen; Zeng-tie Zhang; Si-yuan Li; Qiang Fu; Clare E. Hugnes; Bruce Caterson (Journal of Zhejiang University-SCIENCE B, 2010)

Arsenic-Induced QT Dispersion is Associated with Atherosclerotic Diseases and Predicts Long-Term Cardiovascular Mortality in Subjects with Previous Exposure to Arsenic: A 17-Year Follow-Up Study - Chih-Hao Wang; Chi-Ling Chen; Chuhsing Kate Hsiao; Fu-Tien Chiang; Ling-I Hsu; Hung-Yi Chiou; Yu-Mei Hsueh; Meei-Maan Wu; Chien-Jen Chen (Cardiovascular Toxicology, 2010)

CCR2-64I allele is associated with the progression of AIDS in a Han Chinese population - Lidan Xu; Yuandong Qiao; Xuelong Zhang; Haiming Sun; Jingwei Wang; Donglin Sun; Yan Jin; Yang Yu; Feng Chen; Jing Bai; Hong Ling; Kaili Wang; et al. (Molecular Biology Reports, 2010)

Fractionated evaluation of immunohistochemical hormone receptor expression enhances prognostic prediction in breast cancer patients treated with tamoxifen as adjuvant therapy - Ching-hung Lin; Huang-chun Lien; Fu-chang Hu; Yen-shen Lu; Sung-hsin Kuo; Ling-chu Wu; San-lin You; Ann-lii Cheng; King-jen Chang; Chiun-sheng Huang (Journal of Zhejiang University-SCIENCE B, 2010)

Prostasin inhibits cell invasion in human choriocarcinomal JEG-3 cells - Xiao-jie Ma; Ya-yuan Fu; Yu-xia Li; Li-mei Chen; Karl Chai; Yan-ling Wang (Histochemistry and Cell Biology, 2009)

Eleven novel microsatellite markers developed from the living fossil Ginkgo biloba (Ginkgoaceae) - Xiao-Ling Yan; Ye-Ye Chen; Bi-Cai Guan; Cheng-Xin Fu (Conservation Genetics, 2009)

Secretory expression of K88 (F4) fimbrial adhesin FaeG by recombinant Lactococcus lactis for oral vaccination and its protective immune response in mice - Chun Xia Hu; Zi Rong Xu; Wei Fen Li; Dong Niu; Ping Lu; Ling Lin Fu (Biotechnology Letters, 2009)

Chronic fatigue of the small enterprise workers participating in an occupational health checkup center in southern Taiwan - Fu-Wei Wang; Yu-Wen Chiu; Ming-Shium Tu; Ming-Yueh Chou; Chao-Ling Wang; Hung-Yi Chuang (International Archives of Occupational and Environmental Health, 2009)

Secretory expression of K88 (F4) fimbrial adhesin FaeG by recombinant Lactococcus lactis for oral vaccination and its protective immune response in mice - Chun Xia Hu; Zi Rong Xu; Wei Fen Li; Niu Dong; Ping Lu; Ling Lin Fu (Biotechnology Letters, 2009)

Effect of meal size on excess post-exercise oxygen consumption in fishes with different locomotive and digestive performance - Shi-Jian Fu; Ling-Qing Zeng; Xiu-Ming Li; Xu Pang; Zhen-Dong Cao; Jiang-Lan Peng; Yu-Xiang Wang (Journal of Comparative Physiology B, 2009)

Host‐associated speciation in the coral barnacle Wanella milleporae (Cirripedia: Pyrgomatidae) inhabiting the Millepora coral - LING MING TSANG; BENNY KWOK KAN CHAN; FU‐LONG SHIH; KA HOU CHU; CHAOLUN ALLEN CHEN (Molecular Ecology, 2009)
Speciation by host shift is a common phenomenon observed in many symbiotic animals. The symbiont–host interaction is highly dynamic, but it is poorly documented in the marine realm. In the present study, we examined the genetic and morphological differentiation of the coral barnacle Wanella milleporae (obligate to fire corals) collected from four different Millepora host species in Taiwan to investigate the host specificity of this barnacle. Phylogenetic analysis of mitochondrial COI gene for 241 individuals of Wanella revealed five distinct clades, whose sequence divergences are comparable to values between other cogeneric barnacle species. The five clades also differ in shell and opercular plate morphology and colour. Genetic and morphological differentiations together strongly suggest the presence of cryptic species. Although the five clades do not display species‐level host specificity, they showed a significant difference in preference on host growth form. Clades 1 and 2 were predominantly found on encrusting Millepora exaesa and Millepora platyphylla , while clades 3, 4 and 5 live exclusively on branching‐form fire corals Millepora dichotoma and Millepora tenella . Phylogeny inferred from the combined mitochondrial COI, 16S and 12S (2182 bp) analysis suggests the division of the five clades into two major lineages congruent with the morphology of the host coral. Multiple independent invasions to the same form of host and subsequent speciation are evident in the Red Sea and Taiwan. Our results indicate that ecological/sympatric speciation could occur in marine symbiotic invertebrates through host shift and specialization. It appears that, as in their terrestrial counterparts, host–symbiont radiations in the marine realm are more prevalent than we expected and thus warrant further investigation.

Differential Expression of Serine/Threonine Protein Phosphatase Type-2C Under Drought Stress in Maize - Fu-Hua Li; Feng-Ling Fu; Li-Na Sha; Liang He; Wan-Chen Li (Plant Molecular Biology Reporter, 2009)

Synthesis and Evaluation of a Well-defined HPMA Copolymer–Dexamethasone Conjugate for Effective Treatment of Rheumatoid Arthritis - Xin-Ming Liu; Ling-Dong Quan; Jun Tian; Yazen Alnouti; Kai Fu; Geoffrey M. Thiele; Dong Wang (Pharmaceutical Research, 2008)

Environmental controls over carbon exchange of three forest ecosystems in eastern China - GUI‐RUI YU; LEI‐MING ZHANG; XIAO‐MIN SUN; YU‐LING FU; XUE‐FA WEN; QIU‐FENG WANG; SHENG‐GONG LI; CHUAN‐YOU REN; XIA SONG; YUN‐FEN LIU; SHI‐JIE HAN; JUN‐HUA YAN (Global Change Biology, 2008)
Net ecosystem productivity (NEP) was continuously measured using the eddy covariance (EC) technique from 2003 to 2005 at three forest sites of ChinaFLUX. The forests include Changbaishan temperate mixed forest (CBS), Qianyanzhou subtropical coniferous plantation (QYZ), and Dinghushan subtropical evergreen broad‐leaved forest (DHS). They span wide ranges of temperature and precipitation and are influenced by the eastern Asian monsoon climate to varying extent. In this study, we estimated ecosystem respiration (RE) and gross ecosystem productivity (GEP). Comparison of ecosystem carbon exchange among the three forests shows that RE was mainly determined by temperature, with the forest at CBS exhibiting the highest temperature sensitivity among the three ecosystems. The RE was highly dependent on GEP across the three forests, and the ratio of RE to GEP decreased along the North–South Transect of Eastern China (NSTEC) (i.e. from the CBS to the DHS), with an average of 0.77 ± 0.06. Daily GEP was mainly influenced by temperature at CBS, whereas photosynthetic photon flux density was the dominant factor affecting the daily GEP at both QYZ and DHS. Temperature mainly determined the pattern of the interannual variations of ecosystem carbon exchange at CBS. However, water availability primarily controlled the interannual variations of ecosystem carbon exchange at QYZ. At DHS, NEP attained the highest values at the beginning of the dry seasons (autumn) rather than the rainy seasons (summer), probably because insufficient radiation and frequent fog during the rainy seasons hindered canopy photosynthesis. All the three forest ecosystems acted as a carbon sink from 2003 to 2005. The annual average values of NEP at CBS, QYZ, and DHS were 259 ± 19, 354 ± 34, and 434 ± 66 g C m −2 yr −1 , respectively. The slope of NEP that decreased with increasing latitude along the NSTEC was markedly different from that observed on the forest transect in the European continent. Long‐term flux measurements over more forest ecosystems along the NSTEC will further help verify such a difference between the European forest transect and the NSTEC and provide insights into the responses of ecosystem carbon exchange to climate change in China.

Genome sequence and characterization of a new virus infecting Mikania micrantha H.B.K. - Rui-Long Wang; Ling-Wen Ding; Qiao-Yang Sun; Jing Li; Zeng-Fu Xu; Shao-Lin Peng (Archives of Virology, 2008)

The sweet potato sporamin promoter confers high-level phytase expression and improves organic phosphorus acquisition and tuber yield of transgenic potato - Ya-Fang Hong; Chang-Yeu Liu; Kuo-Joan Cheng; Ai-Ling Hour; Min-Tsair Chan; Tung-Hai Tseng; Kai-Yi Chen; Jei-Fu Shaw; Su-May Yu (Plant Molecular Biology, 2008)

Construction of recombinant industrial Saccharomyces cerevisiae strain with bglS gene insertion into PEP4 locus by homologous recombination - Qiang Zhang; Qi-he Chen; Ming-liang Fu; Jin-ling Wang; Hong-bo Zhang; Guo-qing He (Journal of Zhejiang University-SCIENCE B, 2008)

High-Level Secretion of a Chimeric Thermostable Lichenase from Bacillus subtilis by Screening of Site-Mutated Signal Peptides with Structural Alterations - Ling-lin Fu; Zi-rong Xu; Jiang-bing Shuai; Chun-xia Hu; Wei Dai; Wei-fen Li (Current Microbiology, 2008)

Polymorphisms in genes involved in folate metabolism as maternal risk factors for Down syndrome in China - Shao-shuai Wang; Fu-yuan Qiao; Ling Feng; Juan-juan Lv (Journal of Zhejiang University-SCIENCE B, 2008)

Identification of functional candidate genes for drought tolerance in rice - Bin-Ying Fu; Jian-Hua Xiong; Ling-Hua Zhu; Xiu-Qin Zhao; Hua-Xue Xu; Yong-Ming Gao; Yang-Sheng Li; Jian-Long Xu; Zhi-Kang Li (Molecular Genetics and Genomics, 2007)

Hedgehog signaling in the murine melanoma microenvironment - Ling Geng; Kyle C. Cuneo; Michael K. Cooper; Hong Wang; Konjeti Sekhar; Allie Fu; Dennis E. Hallahan (Angiogenesis, 2007)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

Using EEFM (Excitation Emission Fluorescence Matrix) to Differentiate the Organic Properties of the Effluents from the Ozonated Biofilters - Wen-Liang Lai; Lih-Fu Chen; Shao-Wei Liao; Shu-Lin Hsu; Li-Ho Tseng; Chang-Ling Miaw (Water, Air, & Soil Pollution, 2007)

Edaravone neuroprotection effected by suppressing the gene expression of the Fas signal pathway following transient focal ischemia in rats - Bo Xiao; Fang -Fang Bi; Yue -Qiang Hu; Fa -Fa Tian; Zhi -Guo Wu; Hadi M. Mujlli; Ling Ding; Xin -Fu Zhou (Neurotoxicity Research, 2007)

Characterization of symbiotic and endophytic bacteria isolated from root nodules of herbaceous legumes grown in Qinghai–Tibet plateau and in other zones of China - Feng Ling Kan; Zhong Yi Chen; En Tao Wang; Chang Fu Tian; Xin Hua Sui; Wen Xin Chen (Archives of Microbiology, 2007)

Production and characterization of asymmetric hybrids between upland cotton Coker 201 (Gossypium hirsutum) and wild cotton (G. klozschianum Anderss) - Xi-yan Yang; Xian-long Zhang; Shuang-xia Jin; Li-li Fu; Ling-gang Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2007)

Effects of moderate and severe intermittent hypoxia on vascular endothelial function and haemodynamic control in sedentary men - Jong-Shyan Wang; Liang-Yu Chen; Li-Lan Fu; Mei-Ling Chen; May-Kuen Wong (European Journal of Applied Physiology, 2007)

Expression of SWAP-70 in the uterus and feto-maternal interface during embryonic implantation and pregnancy in the rhesus monkey (Macaca mulatta) - Jing Liu; Ya-Yuan Fu; Xiao-Yang Sun; Fei-Xue Li; Yu-Xia Li; Yan-Ling Wang (Histochemistry and Cell Biology, 2006)

Phylogenetic Relationships and Possible Hybrid Origin of Lycoris Species (Amaryllidaceae) Revealed by ITS Sequences - Shude Shi; Yingxiong Qiu; Enxiang Li; Ling Wu; Chengxin Fu (Biochemical Genetics, 2006)

Arsenic Uptake and Accumulation in Rice (Oryza sativa L.) at Different Growth Stages following Soil Incorporation of Roxarsone and Arsanilic Acid - Fu-Min Wang; Zhang-Liu Chen; Lu Zhang; Yan-Ling Gao; Yong-Xue Sun (Plant and Soil, 2006)

Genome-wide Introgression Lines and their Use in Genetic and Molecular Dissection of Complex Phenotypes in Rice (Oryza sativa L.) - Zhi-Kang Li; Bin-Ying Fu; Yong-Ming Gao; Jian-Long Xu; J. Ali; H. R. Lafitte; Yun-Zhu Jiang; J. Domingo Rey; C. H. M. Vijayakumar; R. Maghirang; Tian-Qing Zheng; Ling-Hua Zhu (Plant Molecular Biology, 2005)

Evaluation of five ab initio gene prediction programs for the discovery of maize genes - Hong Yao; Ling Guo; Yan Fu; Lisa A. Borsuk; Tsui-Jung Wen; David S. Skibbe; Xiangqin Cui; Brian E. Scheffler; Jun Cao; Scott J. Emrich; Daniel A. Ashlock; Patrick S. Schnable (Plant Molecular Biology, 2005)

The receptor tyrosine kinase inhibitor SU11248 impedes endothelial cell migration, tubule formation, and blood vessel formation in vivo, but has little effect on existing tumor vessels - Katherine L. Osusky; Dennis E. Hallahan; Allie Fu; Fei Ye; Yu Shyr; Ling Geng (Angiogenesis, 2004)

The serotonergic system may be involved in the sleep-inducing action of oleamide in rats - Jing-Yu Yang; Chun-Fu Wu; Fang Wang; Hong-Rui Song; Wen-Jun Pan; Yu-Ling Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2003)

Vulnerability Analysis in Earthquake Loss Estimate - Chen Yong; Chen Qi-fu; Chen Ling (Natural Hazards, 2001)

Retroviral gene transfer for the assignment of Fanconi anemia (FA) patients to a FA complementation group - Kai-Ling Fu; Peter C. Thuß; Tadahiro Fujino; Martin Digweed; Johnson M. Liu; Christopher E. Walsh (Human Genetics, 1998)

Quick and Approximate Estimation of Earthquake Loss Based on Macroscopic Index of Exposure and Population Distribution - Qi-Fu Chen; Yong Chen; Jie Liu; Ling Chen (Natural Hazards, 1997)